Accuracy of bone mineral density quantification using dual-layer spectral detector CT: a phantom study - Van Hamersvelt, Robbert W.; Schilham, Arnold M. R.; Engelke, Klaus; Den Harder, Annemarie M.; De Keizer, Bart; Verhaar, Harald J.; Leiner, Tim; De Jong, Pim A.; Willemink, Martin J. (European Radiology, 2017)
OBJECTIVES: To investigate the accuracy of bone mineral density (BMD) quantification using dual-layer spectral detector CT (SDCT) at various scan protocols. METHODS: Two validated anthropomorphic phantoms containing inserts of 50-200 mg/cm3calcium hydroxyapatite (HA) were scanned using a 64-slice SDCT scanner at various acquisition protocols (120 and 140 kVp, and 50, 100 and 200 mAs). Regions of interest (ROIs) were placed in each insert and mean attenuation profiles at monochromatic energy levels (90-200 keV) were constructed. These profiles were fitted to attenuation profiles of pure HA and water to calculate HA concentrations. For comparison, one phantom was scanned using dual energy X-ray absorptiometry (DXA). RESULTS: At both 120 and 140 kVp, excellent correlations (R = 0.97, P < 0.001) were found between true and measured HA concentrations. Mean error for all measurements at 120 kVp was -5.6 ± 5.7 mg/cm3(-3.6 ± 3.2%) and at 140 kVp -2.4 ± 3.7 mg/cm3(-0.8 ± 2.8%). Mean measurement errors were smaller than 6% for all acquisition protocols. Strong linear correlations (R2 ≥ 0.970, P < 0.001) with DXA were found. CONCLUSIONS: SDCT allows for accurate BMD quantification and potentially opens up the possibility for osteoporosis evaluation and opportunistic screening in patients undergoing SDCT for other clinical indications. However, patient studies are needed to extend and translate our findings. KEY POINTS: • Dual-layer spectral detector CT allows for accurate bone mineral density quantification. • BMD measurements on SDCT are strongly linearly correlated to DXA. • SDCT, acquired for several indications, may allow for evaluation of osteoporosis. • This potentially opens up the possibility for opportunistic osteoporosis screening.
EVALuna2:33266

Accuracy of trabecular structure by HR-pQCT compared to gold standard ?CT in the radius and tibia of patients with osteoporosis and long-term bisphosphonate therapy - Krause, M.; Museyko, Oleg; Breer, S.; Wulff, B.; Duckstein, C.; Vettorazzi, Eik; Glueer, C.; Pueschel, K.; Engelke, Klaus; Amling, M. (Osteoporosis international, 2014)
Despite an increasing use of high-resolution peripheral quantitative computed tomography (HR-pQCT) to evaluate bone morphology in vivo, there are reservations about its applicability in patients with osteoporosis and antiresorptive therapy. This study shows that HR-pQCT provides acceptable in vivo accuracy for bone volume fraction (BV/TV) in patients with osteoporosis and bisphosphonate (BP) treatment.The primary aim was to analyze agreement of trabecular structure between HR-pQCT and gold standard microtomography (?CT) in patients with osteoporosis and long-term BP therapy.In the BioAsset study, we analyzed cadaver radii and tibiae of 34 postmenopausal females (81.1 ± 7.1 years) with osteoporosis (no BP n = 22, 1-5 years BP n = 5, >5 years BP n = 7). Two HR-pQCT protocols (patient-mode and ?CT-mode) were compared with gold standard ?CT after image registration. Undecalcified histological sections were obtained to quantify nonmineralized bone matrix. Bland-Altman plots illustrated methodological agreement. Multiple regression analysis was used to test for variables associated with method agreement.In the radius and tibia, patient-mode HR-pQCT derived indices including bone volume fraction, trabecular number, and trabecular separation correlated well with gold standard ?CT (R(2) = 0.78 - 0.88) except for trabecular thickness (R(2) = 0.11). Bland-Altman plots illustrated adequate agreement for bone volume fraction. Lower agreement of trabecular number and trabecular separation improved with decreasing structural impairment at the tibia only. Trabecular thickness was not appropriately assessed with HR-pQCT at both skeletal sites. Higher agreement for bone volume fraction was associated with increasing tissue mineral density in the tibia.HR-pQCT provides acceptable in vivo accuracy for BV/TV in patients with osteoporosis and BP treatment. Higher TMD was associated with higher BV/TV accuracy in vivo. Overall, methodological agreement got less accurate with increasing structural impairment in the tibia.
EVALuna2:10096

ACCURATE DETERMINATION OF PERIARTICULAR BONE COMPOSITION IN HEALTHY INDIVIDUALS AND COMPARISON TO ACPA-POSITIVE RHEUMATOID ARTHRITIS PATIENTS - Simon, David; Kleyer, Arnd; Stemmler, F.; Simon, C.; Hueber, Axel; Kampylafka, E.; Englbrecht, Matthias; Figueiredo, C.; Engelke, Klaus; Berlin, Andreas; Haschka, J.; Rech, Jürgen; et al. (2016)
EVALuna2:13492

A comparative analysis of articular bone in large cohort of patients with chronic inflammatory diseases of the joints, the gut and the skin - Simon, David; Kleyer, Arnd; Englbrecht, Matthias; Stemmler, Fabian; Simon, Christoph; Berlin, Andreas; Kocijan, Roland; Haschka, Judith; Hirschmann, Simon; Atreya, Raja; Neurath, Markus; Sticherling, Michael; et al. (Bone, 2018)
Chronic inflammatory diseases are associated with bone loss. While the occurrence of systemic bone loss is well described in chronic inflammatory diseases, the impact of these conditions on articular bone has not been systematically investigated. Recent refinements in high-resolution CT assessment of the joints now allow the accurate measure of articular bone composition. In this study 476 subjects comprising healthy individuals and patients with anticitrullinated protein antibody (ACPA)-positive rheumatoid arthritis (RA), ACPA-negative RA, Crohn's disease (CD), ulcerative colitis (UC), psoriasis (PsO) and psoriatic arthritis (PsA) were subjected to high-resolution quantitative computed tomography (HR-pQCT) of the hand. Metacarpal heads were assessed for total, trabecular and cortical volumetric bone mineral density (vBMD). Only ACPA+RA, but not the remaining inflammatory diseases (ACPA-RA, CD, UC, PsO, PsA) showed significant (p < 0.001) loss of articular bone affecting both the trabecular and the cortical compartments. Age and body mass index were also associated with articular bone changes, the former with lower, the latter with higher articular bone mass. In multivariate models, presence of ACPA+RA was an independent factor for articular bone loss. Among chronic inflammatory diseases ACPA+RA is the most potent precipitator for articular bone loss pointing out the role of autoimmunity in the development of articular bone disease in the context of chronic inflammatory disease.
EVALuna2:34480

A COMPARISON BETWEEN 6-POINT DIXON MRI AND MR SPECTROSCOPY TO QUANTIFY MUSCLE FAT IN THE THIGH OF SUBJECTS WITH SARCOPENIA - Grimm, Alexandra; Meyer, H.; Nickel, M. D.; Nittka, M.; Raithel, E.; Chaudry, Oliver; Friedberger, Andreas; Uder, Michael; Kemmler, Wolfgang; Engelke, Klaus; Quick, H. H. (Journal of Frailty & Aging, 2019)
Background: Changes in muscle fat composition as for example observed in sarcopenia, affect physical performance and muscular function, like strength and power. Objectives: The purpose of this study was to compare 6-point Dixon magnetic resonance imaging and multi-echo magnetic resonance spectroscopy sequences to quantify muscle fat. Setting, participants and measurements: Two groups were recruited (G1: 23 healthy young men (28 +/- 4 years), G2: 56 men with sarcopenia (80 +/- 5 years)). Proton density fat fraction was measured with a 6-point product and a 6-point prototype Dixon sequence in the left thigh muscle and with a highspeed multi-echo T2*-corrected H1 magnetic resonance spectroscopy sequence within the semitendinosus muscle of the left thigh. To evaluate the comparability among the different methods, Bland-Altman and linear regression analyses of the proton density fat fraction results were performed. Results: Mean differences +/- 1.96 * standard deviation between spectroscopy and 6pt Dixon sequences were 1.9 +/- 3.3% and 1.5 +/- 3.6% for the product and prototype sequences, respectively. High correlations were measured between the proton density fat fraction results of the 6-point Dixon sequences and spectroscopy (R = 0.95 for the product sequence and R = 0.97 for the prototype sequence). Conclusions: Dixon imaging and spectroscopy sequences show comparable accuracy for fat measurements in the thigh. Spectroscopy is a local measurement, whereas Dixon sequences provide maps of the fat distribution. The high correlations of the 6-point Dixon sequences with spectroscopy support their clinical use. They provide higher spatial resolution than spectroscopy, but are not suitable for a more complicated spectral analysis to separate extra-and intramyocellular lipids.
CRIS-Team WoS Importer:2019-03-06

A COMPARISON OF TWO METHODS TO SEGMENT BONE EROSIONS IN THE METACARPOPHALANGEAL JOINTS OF RHEUMATOID ARTHRITIS PATIENTS - Figueiredo, C.; Simon, David; Stemmler, F.; Weißenfels, Anja; Weishäupl, Dirk; Museyko, Oleg; Friedberger, Andreas; Rech, Jürgen; Hueber, Axel; Haschka, J.; Schett, Georg; Engelke, Klaus; et al. (2016)
EVALuna2:13471

Additive effect of anti-citrullinated protein antibodies and rheumatoid factor on bone erosions in patients with RA - Hecht, Carolin; Englbrecht, Matthias; Rech, Juergen; Schmidt, Sarah; Araujo, Elizabeth; Engelke, Klaus; Finzel, Stephanie; Schett, Georg (Annals of the Rheumatic Diseases, 2015)
To determine whether there is an additive effect of anticitrullinated protein antibodies (ACPA) and rheumatoid factor (RF) on the number and size of bone erosions in patients with rheumatoid arthritis (RA) METHODS: 242 patients with RA received high-resolution peripheral quantitative CT (HR-pQCT) scans of the metacarpophalangeal joints. Demographic and disease-specific parameters including ACPA and RF levels were recorded from all patients. Erosion numbers and their size were assessed in 238 patients at 714 individual joints (MCP 2, 3 and 4) and 5712 sites (each 4 quadrants in metacarpal heads and phalangeal bases). The volume of erosions was calculated by a semiellipsoid formula.Of the 238 patients, 112 patients showed RF and ACPAs (ACPAs+RF+), 28 only RF (RF+), 29 only ACPAs (ACPA+) and 69 were antibody negative (NEG). Erosion number and size were highest in RF+ACPAs+ patient group with significant differences compared with NEG patients with respect to erosion number (p=0.001) and to ACPA-negative patients with respect to erosion size (p<0.001). Results maintained significance in a linear mixed model showing ACPAs+RF+ status and disease duration being associated with higher number (p=0.017 and p=0.005, respectively), and larger size (p=0.014 and p=0.013, respectively) of bone erosions. Furthermore, erosion size was influenced by the presence and titre of RF only in ACPA-positive patients with RA but not in ACPA-negative patients.ACPAs and RF show an additive effect on erosion number and erosion size. Concomitant presence of ACPAs and RF is associated with higher erosive disease burden in patients with RA. Furthermore, RF influences erosion size only in ACPA-positive but not in ACPA-negative patients.
EVALuna2:10081

A degenerative medial meniscus retains some protective effect against osteoarthritis-induced subchondral bone changes - Mitton, G.; Engelke, Klaus; Uk, S.; Laredo, J. D.; Chappard, C. (Bone Reports, 2020)
Objectives: The objective was to estimate the impact of the meniscus on cartilage and subchondral bone in knee osteoarthritis (OA). Methods: In a sample of 46 knee specimens (26 females), 13 (7 females) were classified as OA according to the Kellgren-Lawrence classification. Outerbridge and meniscal grading were performed. Using micro-computed tomography images, we analyzed the cartilage thickness, subchondral plate thickness and micro-architecture of trabecular subchondral bone at different depths and in two different locations of the medial tibial plateau: one peripheral (PER) covered by the meniscus and one central (CENT) uncovered by the meniscus. Results: Uncoverage by the meniscus was associated with bone sclerosis, defined as higher bone volume to total volume (BV/TV), higher trabecular number, thicker trabeculae with lower spacing, and anisotropy and a more plate-like architecture. The protective effect of meniscal coverage was observed in the uppermost 5 to 6 mm of the subchondral bone. As compared with normal knees, knees with OA showed significantly higher bone sclerosis (P <0.05–0.001) at the PER location, but only BV/TV (P=0.03) and trabecular number (P=0.02) differed between OA and non-OA knees at the CENT location uncovered by meniscus. Conclusions: OA results showed a partial dedifferentiation of the subchondral bone micro-architecture between PER and CENT locations probably due to menisci that still retain some of their protective effects on the subchondral bone.
CRIS-Team Scopus Importer:2020-06-02
Keywords: Cartilage; Meniscus; Micro-computed tomography; Osteoarthritis; Subchondral trabecular bone

A dual role for UCMA in osteoarthritis-Inhibition of aggrecanases and promotion of bone turnover - Stock, Michael; Menges, Stefanie; Eitzinger, Nicole; Gesslein, Maria; Botschner, Renate; Wormser, Laura; Distler, Alfiya; Schlötzer-Schrehardt, Ursula; Dietel, Katharina; Distler, Jörg; Beyer, Christian; Gelse, Kolja; et al. (Arthritis and Rheumatology, 2017)
Cartilage damage and subchondral bone changes are closely connected in osteoarthritis. How these processes are interlinked is however incompletely understood to date. Here, we investigate the mechanistic role of the cartilage-derived protein UCMA in osteoarthritis-related cartilage and bone changes.UCMA expression was assessed in healthy and osteoarthritic human and mouse cartilage. DMM-induced osteoarthritis was performed in WT and Ucma-deficient mice analysing cartilage and bone changes. UCMA-collagen interactions, effect of UCMA on aggrecanase activity and the impact of recombinant UCMA on osteoclast differentiation were studied in vitro.UCMA was found overexpressed in human and mouse osteoarthritic cartilage. DMM-triggered cartilage changes were aggravated in Ucma-deficient mice compared to WT littermates, showing increased structural damage, proteoglycan loss and chondrocyte cell death indicating chondroprotective effects of UCMA. Moreover, UCMA inhibited ADAMTS-dependent aggrecanase activity and directly interacted with cartilage-specific collagen types. In contrast, osteoarthritis-related bone changes were significantly reduced in Ucma-deficient mice, showing less pronounced osteophyte formation and subchondral bone sclerosis. Mechanistically, UCMA directly promoted osteoclast differentiation in vitro.UCMA links cartilage with bone changes in osteoarthritis, supporting cartilage integrity as an endogenous inhibitor of aggrecanases on the one hand, and promoting osteoclastogenesis and subchondral bone turnover on the other hand. Hence, UCMA represents an important link between cartilage and bone in osteoarthritis. This article is protected by copyright. All rights reserved.
EVALuna2:10230

ADVANCED 3D REGISTRATION FOR MONITORING PERIPHERAL BMD AND BMC CHANGES IN GROWING BONES IN CHILDREN - Friedberger, Andreas; Museyko, Oleg; Genant, H. H.; Engelke, Klaus (2018)
EVALuna2:36401

Advanced Knee Structure Analysis (AKSA): a comparison of bone mineral density and trabecular texture measurements using computed tomography and high-resolution peripheral quantitative computed tomography of human knee cadavers - Lowitz, Torsten; Museyko, Oleg; Bousson, Valerie; Chappard, Christine; Laouisset, Liess; Laredo, Jean-Denis; Engelke, Klaus (Arthritis Research & Therapy, 2017)
BACKGROUND: A change of loading conditions in the knee causes changes in the subchondral bone and may be a cause of osteoarthritis (OA). However, quantification of trabecular architecture in vivo is difficult due to the limiting spatial resolution of the imaging equipment; one approach is the use of texture parameters. In previous studies, we have used digital models to simulate changes of subchondral bone architecture under OA progression. One major result was that, using computed tomography (CT) images, subchondral bone mineral density (BMD) in combination with anisotropy and global homogeneity could characterize this progression. The primary goal of this study was a comparison of BMD, entropy, anisotropy, variogram slope, and local and global inhomogeneity measurements between high-resolution peripheral quantitative CT (HR-pQCT) and CT using human cadaveric knees. The secondary goal was the verification of the spatial resolution dependence of texture parameters observed in the earlier simulations, two important prerequisites for the interpretation of in vivo measurements in OA patients. METHOD: The applicability of texture analysis to characterize bone architecture in clinical CT examinations was investigated and compared to results obtained from HR-pQCT. Fifty-seven human knee cadavers (OA status unknown) were examined with both imaging modalities. Three-dimensional (3D) segmentation and registration processes, together with automatic positioning of 3D analysis volumes of interest (VOIs), ensured the measurement of BMD and texture parameters at the same anatomical locations in CT and HR-pQCT datasets. RESULTS: According to the calculation of dice ratios (>0.978), the accuracy of VOI locations between methods was excellent. Entropy, anisotropy, and global inhomogeneity showed significant and high linear correlation between both methods (0.68 < R2 < 1.00). The resolution dependence of these parameters simulated earlier was confirmed by the in vitro measurements. CONCLUSION: The high correlation of HR-pQCT- and CT-based measurements of entropy, global inhomogeneity, and anisotropy suggests interchangeability between devices regarding the quantification of texture. The agreement of the experimentally determined resolution dependence of global inhomogeneity and anisotropy with earlier simulations is an important milestone towards their use to quantify subchondral bone structure. However, an in vivo study is still required to establish their clinical relevance.
EVALuna2:33267

Age and BMI have different effects on subcutaneous, visceral, liver, bone marrow, and muscle adiposity, as measured by CT and MRI - Wang, Ling; Liu, Yandong; Li, Kai; Zhang, Wenshuang; Yuan, Yi; Ma, Kangkang; Zhou, Fengyun; Cheng, Zitong; Geng, Jian; Su, Yongbin; Guo, Zhe; Blake, Glen M.; et al. (Obesity, 2024)
Objective: We analyzed quantitative computed tomography (CT) and chemical shift–encoded magnetic resonance imaging (MRI) data from a Chinese cohort to investigate the effects of BMI and aging on different adipose tissue (AT) depots. Methods: In 400 healthy, community-dwelling individuals aged 22 to 83 years, we used MRI to quantify proton density fat fraction (PDFF) of the lumbar spine (L2–L4) bone marrow AT (BMAT), the psoas major and erector spinae (ES) muscles, and the liver. Abdominal total AT, visceral AT (VAT), and subcutaneous AT (SAT) areas were measured at the L2-L3 level using quantitative CT. Partial correlation analysis was used to evaluate the relationship of each AT variable with age and BMI. Multiple linear regression analysis was performed in which each AT variable was evaluated in turn as a function of age and the other five independent AT measurements. Results: Of the 168 men, 29% had normal BMI (<24.0 kg/m2), 47% had overweight (24.0–27.9 kg/m2), and 24% had obesity (≥ 28.0 kg/m2). In the 232 women, the percentages were 46%, 32%, and 22%, respectively. Strong or very strong correlations with BMI were found for total AT, VAT, and SAT in both sexes. BMAT and ES PDFF was strongly correlated with age in women and moderately correlated in men. In both sexes, BMAT PDFF correlated only with age and not with any of the other AT depots. Psoas PDFF correlated only with ES PDFF and not with age or the other AT depots. Liver PDFF correlated with BMI and VAT and weakly with SAT in men. VAT and SAT correlated with age and each other in both sexes. Conclusions: Age and BMI are both associated with adiposity, but their effects differ depending on the type of AT.
CRIS-Team Scopus Importer:2024-05-31

Age- and Sex-Dependent Changes of Intra-articular Cortical and Trabecular Bone Structure and the Effects of Rheumatoid Arthritis - Simon, David; Kleyer, Arnd; Stemmler, Fabian; Simon, Christoph; Berlin, Andreas; Hueber, Axel; Haschka, Judith; Renner, Nina; Figueiredo, Camille; Neuhuber, Winfried; Buder, Thomas; Englbrecht, Matthias; et al. (Journal of Bone and Mineral Research, 2016)
The objective of this cross-sectional study was to define normal sex- and age-dependent values of intra-articular bone mass and microstructures in the metacarpal heads of healthy individuals by high-resolution peripheral quantitative computed tomography (HR-pQCT) and test the effect of rheumatoid arthritis (RA) on these parameters. Human cadaveric metacarpal heads were used to exactly define intra-articular bone. Healthy individuals of different sex and age categories and RA patients with similar age and sex distribution received HR-pQCT scans of the second metacarpal head and the radius. Total, cortical, and trabecular bone densities as well as microstructural parameters were compared between 1) the different ages and sexes in healthy individuals; 2) between metacarpal heads and the radius; and 3) between healthy individuals and RA patients. The cadaveric study allowed exact definition of the intra-articular (intracapsular) bone margins. These data were applied in measuring intra-articular and radial bone parameters in 214 women and men (108 healthy individuals, 106 RA patients). Correlations between intra-articular and radial bone parameters were good (r = 0.51 to 0.62, p < 0.001). In contrast to radial bone, intra-articular bone remained stable until age 60 years (between 297 and 312 mg HA/cm(3) ) but decreased significantly (p < 0.001) in women thereafter (237.5 ± 44.3) with loss of both cortical and trabecular bone. Similarly, RA patients showed significant (p < 0.001) loss of intra-articular total (263.0 ± 44.8), trabecular (171.2 ± 35.6), and cortical bone (610.2 ± 62.0) compared with sex- and age-adjusted controls. Standard sex- and age-dependent values for physiological intra-articular bone were defined. Postmenopausal state and RA led to significant decrease of intra-articular bone. © 2016 American Society for Bone and Mineral Research.
EVALuna:33251

Age Related Increase of Intermuscular Adipose Tissue of the Thigh can be Prevented by Exercise in Sarcopenic Men - Engelke, Klaus; Chaudry, Oliver; Ghasemikaram, Mansour; Nagel, Armin Michael; Jakob, Franz; Kemmler, Wolfgang (JOURNAL OF BONE AND MINERAL RESEARCH, 2022)
CRIS-Team WoS Importer:2022-05-27

AGN1 local osteo-enhancement procedure increases proximal femur volumetric bone mineral density of women with post-menopausal osteoporosis as assessed by quantitative computed tomography analysis - Chin, Michelle; Hill, Ronald; Huber, Bryan; Howe, James; Engelke, Klaus (JBMR Plus, 2025)
In this study, QCT was used to analyze the AGN1 Local Osteo-Enhancement Procedure (LOEP) as a treatment to form bone in the proximal femurs of patients with osteoporosis. Using this minimally invasive procedure, a resorbable triphasic AGN1 implant material was injected into the left femurs of 12 women with post-menopausal osteoporosis. Computed tomography scans were taken before treatment (baseline) and at 12 wk, 24 wk, and 5-7 yr after treatment. Quantitative computed tomography was used to investigate the resorption of AGN1 within the treated proximal femurs and to analyze the treatment’s impact on integral, trabecular, and cortical bone. The untreated right femurs were used as controls. Data illustrated an increase in trabecular volumetric BMD (trab vBMD) of treated hips at all timepoints (baseline: 22 ± 21 mg/cm3 vs 217 ± 56 mg/cm3, 161 ± 18 mg/cm3, and 121 ± 37 mg/cm3 at 12-wk, 24-wk, and 5- to 7-yr timepoints, respectively), and an increase in integral vBMD of 65% at the 12-wk timepoint and 34% at the 5- to 7-yr timepoint. The increase in trab vBMD was observed in the location where the AGN1 implant material bolus was injected, and at the 5- to 7-yr timepoint, no significant BMD change was observed in the trabecular regions surrounding the original implantation zone (treated: 32 ± 16 mg/cm3, control: 31 ± 16 mg/cm3). This QCT study provides a more detailed understanding of the resorption and transformation of the AGN1 implant material into bone and supports, with some limitations, that the AGN1 LOEP treatment can locally increase trabecular bone density in weakened areas of the proximal femur where strength increase is most needed to reduce the risk of hip fragility fracture.
CRIS-Team Scopus Importer:2025-05-16
Keywords: bone QCT; clinical trials; fracture prevention; orthopedics; osteoporosis

A low-radiation exposure protocol for 3D QCT of the spine - Museyko, Oleg; Heinemann, A.; Krause, M.; Wulff, B.; Amling, M.; Pueschel, K.; Glueer, C. C.; Kalender, Willi Alfred; Engelke, Klaus (Osteoporosis international, 2014)
Cadaver and phantom measurements and simulations confirmed that radiation exposure in 3D QCT of the spine can be reduced if 80 kV instead of 120 kV protocols are used; 120 mAs and slice thicknesses of 1-1.3 mm should be usable but obese patient will require higher milliampere-second settings.To develop a low-radiation exposure CT acquisition protocol for 3D QCT of the thoracolumbar spine.Twenty-six cadavers were scanned with a standard protocol of 120 kV, 100 mAs and with a low-dose protocol using 90 kV, 150 mAs. The scan range included the vertebrae T6 to L4. Each vertebra was segmented and the integral volume and BMD of the total vertebral body were determined. Effective dose values were estimated. The impact of milliampere-second reduction on image quality was simulated by adding noise.One hundred ninety-six vertebrae were analyzed. Integral volume as well as integral BMD correlated significantly (p < 0.001) between standard and low-dose protocols (volume, r (2) = 0.991, residual root mean square (RMS) error, 0.77 cm(3); BMD, r (2) = 0.985, RMS error, 4.21 mg/cm(3)). The slope significantly differed from 1 for integral BMD but not for volume hinting at residual field inhomogeneity differences between the two voltage settings that could be corrected by cross-calibration. Compared to the standard protocol, effective dose was reduced by over 50 % in the low-dose protocol. Adding noise in the 90 kV images to simulate a reduction from 150 to 100 mAs did not affect the results for integral volume or BMD.For 3D QCT of the spine, depending on scanner type, 80 or 90 kV instead of 120 kV protocols may be considered as an important option to reduce radiation exposure; 120 mAs and slice thicknesses of 1-1.5 mm are usable if segmentation is robust to noise. In obese patients, higher milliampere-second settings will be required.
EVALuna2:10069

A new CT based approach to quantify adipose tissue in paraspinal muscle - Engelke, Klaus; Museyko, Oleg; Guenzel, Daniel; Maier, Andreas; Laredo, Jean-Denis (2018)
EVALuna2:36396

A new method for quantitative assessment of hand muscle volume and fat in magnetic resonance images - Friedberger, Andreas; Figueiredo, Camille; Bäuerle, Tobias; Schett, Georg; Engelke, Klaus (BMC Rheumatology, 2020)
Background: Rheumatoid arthritis (RA) is characterized by systemic inflammation and bone and muscle loss. Recent research showed that obesity facilitates inflammation, but it is unknown if obesity also increases the risk or severity of RA. Further research requires an accurate quantification of muscle volume and fat content. Methods: The aim was to develop a reproducible (semi) automated method for hand muscle segmentation and quantification of hand muscle fat content and to reduce the time consuming efforts of manual segmentation. T1 weighted scans were used for muscle segmentation based on a random forest classifier. Optimal segmentation parameters were determined by cross validation with 30 manually segmented hand datasets (gold standard). An operator reviewed the automatically created segmentation and applied corrections if necessary. For fat quantification, the segmentation masks were automatically transferred to MRI Dixon sequences by rigid registration. In total 76 datasets from RA patients were analyzed. Accuracy was validated against the manual gold standard segmentations. Results: Average analysis time per dataset was 10 min, more than 10 times faster compared to manual outlining. All 76 datasets could be analyzed and were accurate as judged by a clinical expert. 69 datasets needed minor manual segmentation corrections. Segmentation accuracy compared to the gold standard (Dice ratio 0.98 ± 0.04, average surface distance 0.04 ± 0.10 mm) and reanalysis precision were excellent. Intra- and inter-operator precision errors were below 0.3% (muscle) and 0.7% (fat). Average Hausdorff distances were higher (1.09 mm), but high values originated from a shift of the analysis VOI by one voxel in scan direction. Conclusions: We presented a novel semi-automated method for quantitative assessment of hand muscles with excellent accuracy and operator precision, which highly reduced a traditional manual segmentation effort. This method may greatly facilitate further MRI image based muscle research of the hands.
CRIS-Team Scopus Importer:2021-04-19
Keywords: Fat quantification; Hand muscle; Random forest segmentation; Rheumatoid arthritis

A NEW METHOD FOR THE QUANTITATIVE ANALYSIS OF HAND MUSCLE VOLUME FOR PATIENTS WITH RHEUMATOID ARTHRITIS - Friedberger, Andreas; Museyko, Oleg; Figueiredo, C.; Bäuerle, Tobias; Chaudry, Oliver; Grimm, Alexandra; Schett, Georg; Engelke, Klaus (2016)
EVALuna2:13491

A new method to determine cortical bone thickness in CT images using a hybrid approach of parametric profile representation and local adaptive thresholds: Accuracy results - Museyko, Oleg; Gerner, Bastian; Engelke, Klaus (PLoS ONE, 2017)
MOTIVATION: Cortical bone is an important contributor to bone strength and is pivotal to understand the etiology of osteoporotic fractures and the specific mechanisms of antiosteoporotic treatment regimen. 3D computed tomography (CT) can be used to measure cortical thickness, density, and mass in the proximal femur, lumbar vertebrae, and distal forearm. However, the spatial resolution of clinical whole body CT scanners is limited by radiation exposure; partial volume artefacts severely impair the accurate assessment of cortical parameters, in particular in locations where the cortex is thin such as in the lumbar vertebral bodies or in the femoral neck. METHOD: Model-based deconvolution approaches recover the cortical thickness by numerically deconvolving the image along 1D profiles using an estimated scanner point spread function (PSF) and a hypothesized uniform cortical bone mineral density (reference density). In this work we provide a new essentially analytical unique solution to the model-based cortex recovery problem using few characteristics of the measured profile and thus eliminate the non-linear optimization step for deconvolution. Also, the proposed approach allows to get rid of the PSF in the model and reduces sensitivity to errors in the reference density. Additionally, run-time and memory effective computation of cortical thickness was achieved with the help of a lookup table. RESULTS: The method accuracy and robustness was validated and compared to that of a deconvolution approach recently proposed for cortical bone and of the 50% relative threshold technique: in a simulated environment with noise and various error levels in the reference density and using CT acquisitions of the European Forearm Phantom (EFP II), a modification of a widely used anthropomorphic standard of cortical and trabecular bone compartments that was scanned with various scan protocols. CONCLUSION: Results of simulations and of phantom data analysis verified the following properties of the new method: 1) Robustness against errors in the reference density. 2) Excellent accuracy on ground truth data with various noise levels. 3) Very fast computation using a lookup table.
EVALuna2:33264

A randomized, double-blind, placebo-controlled clinical study to evaluate the efficacy of the synbiotic medical food, SBD111, for the clinical dietary management of bone loss in menopausal women - Schott, Eric M.; Charbonneau, Mark R.; Kiel, Douglas P.; Bukata, Susan; Zuscik, Michael J.; Rosen, Clifford; Ballok, Alicia; Toledo, Gerardo V.; Steels, Elizabeth; Huntress, Harry; Rao, Amanda; Ebelt, Phillippa; et al. (Osteoporosis international, 2025)
Summary: This 12-month study in 286 early postmenopausal women evaluated the efficacy and safety of SBD111, a synbiotic medical food, in reducing bone loss. SBD111 did not significantly reduce bone loss for the full cohort, but did produce evidence of reduced bone loss in women with osteopenia and BMI ≥ 30. Purpose: To determine the efficacy of SBD111, a synbiotic medical food comprising probiotics and prebiotics, in reducing bone loss in women post-menopause, including prespecified subpopulations of women with osteopenia or elevated BMI. Methods: In this prospective, multicenter, double-blind, randomized, placebo-controlled clinical food trial (NCT05009875), 286 healthy, non-osteoporotic women between 1 and 6 years post-menopause were enrolled and consumed SBD111 (4.75 × 1010 colony forming units) or placebo (maltodextrin) capsules twice daily for 12 months. The primary endpoint was change in areal BMD at the lumbar spine (LS). Secondary endpoints included change in areal BMD at the femoral neck (FN) and total hip (TH), trabecular volumetric BMD at the LS, markers of bone turnover and inflammation, and safety. Changes in gut microbiome composition were exploratory. The hypotheses being tested were formulated before data collection. Results: Two hundred eighty-six women [age 55 ± 3 years (mean ± standard deviation)] were enrolled, with 221 (77%) completing the study. For the primary outcome, SBD111 administration was not associated with significantly less bone loss in the LS after 12 months [0.15% (− 0.52%, 0.82%), mean effect size (95% CI) by linear mixed-effects regression]. However, SBD111 was associated with reduced BMD loss in the TH for women with BMI ≥ 30 [0.97% (0.015%, 1.925%)] and modestly reduced BMD loss in the FN for women with osteopenia [0.89% (− 0.277%, 2.051%)]. Conclusions: These findings indicate SBD111 did not significantly reduce BMD loss for the full cohort. However, the trial produced evidence that SBD111 reduced bone loss in women with osteopenia and BMI ≥ 30.
CRIS-Team Scopus Importer:2025-08-29
Keywords: Bone mineral density (BMD); Osteoporosis; Short-chain fatty acids (SCFA); Tumor necrosis factor alpha (TNF-α)

A reproducible semi-automatic method to quantify the muscle-lipid distribution in clinical 3D CT images of the thigh - Mühlberg, Alexander; Museyko, Oleg; Laredo, Jean-Denis; Engelke, Klaus (PLoS ONE, 2017)
Many studies use threshold-based techniques to assess in vivo the muscle, bone and adipose tissue distribution of the legs using computed tomography (CT) imaging. More advanced techniques divide the legs into subcutaneous adipose tissue (SAT), anatomical muscle (muscle tissue and adipocytes within the muscle border) and intra- and perimuscular adipose tissue. In addition, a so-called muscle density directly derived from the CT-values is often measured. We introduce a new integrated approach to quantify the muscle-lipid system (MLS) using quantitative CT in patients with sarcopenia or osteoporosis. The analysis targets the thigh as many CT studies of the hip do not include entire legs The framework consists of an anatomic coordinate system, allowing delineation of reproducible volumes of interest, a robust semi-automatic 3D segmentation of the fascia and a comprehensive method to quantify of the muscle and lipid distribution within the fascia. CT density-dependent features are calibrated using subject-specific internal CT values of the SAT and external CT values of an in scan calibration phantom. Robustness of the framework with respect to operator interaction, image noise and calibration was evaluated. Specifically, the impact of inter- and intra-operator reanalysis precision and addition of Gaussian noise to simulate lower radiation exposure on muscle and AT volumes, muscle density and 3D texture features quantifying MLS within the fascia, were analyzed. Existing data of 25 subjects (age: 75.6 ± 8.7) with porous and low-contrast muscle structures were included in the analysis. Intra- and inter-operator reanalysis precision errors were below 1% and mostly comparable to 1% of cohort variation of the corresponding features. Doubling the noise changed most 3D texture features by up to 15% of the cohort variation but did not affect density and volume measurements. The application of the novel technique is easy with acceptable processing time. It can thus be employed for a comprehensive quantification of the muscle-lipid system enabling radiomics approaches to musculoskeletal disorders.
EVALuna2:33265

Assessing muscle-specific potassium concentrations in human lower leg using potassium magnetic resonance imaging - Gast, Lena; Baier, Laura-Marie; Chaudry, Oliver; Meixner, Christian; Müller, Max; Engelke, Klaus; Uder, Michael; Heiß, Rafael; Nagel, Armin Michael (NMR in Biomedicine, 2022)
Noninvasively assessing tissue potassium concentrations (TPCs) using potassium magnetic resonance imaging (39K MRI) could give valuable information on physiological processes connected to various pathologies. However, because of inherently low 39K MR image resolution and strong signal blurring, a reliable measurement of the TPC is challenging. The aim of this work was to investigate the feasibility of a muscle-specific TPC determination with a focus on the influence of a varying residual quadrupolar interaction in human lower leg muscles. The quantification accuracy of a muscle-specific TPC determination was first assessed using simulated 39K MRI data. In vivo 39K and corresponding sodium (23Na) MRI data of healthy lower leg muscles (n = 14, seven females) were acquired on a 7-T MR system using a double-resonant 23Na/39K birdcage Tx/Rx RF coil. Additional 1H MR images were acquired on a 3-T MR system and used for tissue segmentation. Quantification of TPC was performed after a region-based partial volume correction (PVC) using five external reference phantoms. Simulations not only underlined the importance of PVC for correctly assessing muscle-specific TPC values, but also revealed the strong impact of a varying residual quadrupolar interaction between different muscle regions on the measured TPC. Using 39K T2* decay curves, we found significantly higher residual quadrupolar interaction in tibialis anterior muscle (TA; ωq = 194 ± 28 Hz) compared with gastrocnemius muscle (medial/lateral head, GM/GL; ωq = 151 ± 25 Hz) and soleus muscle (SOL; ωq = 102 ± 32 Hz). If considered in the PVC, TPC in individual muscles was similar (TPC = 98 ± 11/96 ± 14/99 ± 8/100 ± 12 mM in GM/GL/SOL/TA). Comparison with tissue sodium concentrations suggested that residual quadrupolar interactions might also influence the 23Na MRI signal of lower leg muscles. A TPC determination of individual lower leg muscles is feasible and can therefore be applied in future studies. Considering a varying residual quadrupolar interaction for PVC of 39K MRI data is essential to reliably assess potassium concentrations in individual muscles.
CRIS-Team Scopus Importer:2022-09-16
Keywords: 7 T; muscle MRI; potassium (; sodium (; tissue potassium concentration; tissue sodium concentration; ultrahigh field strengths

Assessment of bone densitometry using radiography with a step-wedge phantom: a pilot study of the forearm - Wang, Ling; Huang, Pengju; Du, Hui; Geng, Jian; Yin, Xinghua; Liu, Yandong; Puri, Tanuj; He, Bo; Lyu, Liang; Cheng, Xiaoguang; Jiang, Xieyuan; Engelke, Klaus; et al. (Quantitative Imaging in Medicine and Surgery, 2022)
Background: Radiographic absorptiometry (RA) is one of the earliest methods of bone densitometry and has been used to measure the phalanges and metacarpals where soft tissue attenuation is minimal. The aim of this study was to determine whether the technique can be adapted to correct for soft tissue attenuation and measure areal bone mineral density (aBMD) in the forearm.
CRIS-Team WoS Importer:2022-03-04

Associations of Muscle Size and Density With Proximal Femur Bone in a Community Dwelling Older Population - Yin, Lu; Xu, Zhengyang; Wang, Ling; Li, Wei; Zhao, Yue; Su, Yongbin; Sun, Wei; Liu, Yandong; Yang, Minghui; Yu, Aihong; Blake, Glen Mervyn; Wu, Xinbao; et al. (Frontiers in Endocrinology, 2020)
Background and Purpose: Muscle weakness and bone fragility are both associated with hip fracture. In general, muscle contractions create forces to the bone, and bone strength adapts to mechanical loading through changes in bone architecture and mass. However, the relationship between impairment of muscle and bone function remain unclear. In particular, the associations of muscle with properties of proximal femur cortical and trabecular bone are still not well understood. The aim of this study was to explore the associations of hip/thigh muscle density (CT attenuation value in Hounsfield units) and size with cortical and trabecular bone mineral density (BMD) of the proximal femur. Materials and Methods: Three-dimensional quantitative computed tomography (QCT) imaging of the lumber, hip and mid-thigh was performed in a total of 301 participants (mean age 68.4 ± 6.1 years, 194 women and 107 men) to derive areal BMD (aBMD) and volumetric BMD (vBMD). Handgrip strength (HGS) and the Timed Up and Go (TUG) test were also performed. From the CT images, cross-sectional area (CSA), and density were determined for the gluteus maximus muscle (G.MaxM), trunk muscle at the vertebrae L2 level, and mid-thigh muscle. Multivariate generalized linear models were applied to assess associations. Results: Total hip (TH) aBMD was associated significantly with G.MaxM CSA (men: P = 0.042; women: P < 0.001) and density (men: P = 0.012; women: P = 0.043). In women, 0.035 cm2 of mid-thigh CSA (95% CI, 0.014–0.057; P = 0.002) increased per SD increase in TH aBMD, but this significance was not observed in men (P = 0.095). Trunk muscle density and CSA were not associated with proximal femur BMD. The associations of hip/thigh muscle parameters with femoral neck BMD were weaker than those with trochanter and intertrochanter BMD. Furthermore, compared to muscle density, muscle CSA showed better associations with vBMD. G.MaxM CSA was associated with trochanter (TR) Cort. vBMD in men (β, 19.898; 95% CI, 0.924–38.871; P = 0.040) and in women (β, 15.426; 95% CI, 0.893–29.958; P = 0.038). Handgrip strength was only associated with TR aBMD (β, 0.038; 95% CI, 0.006–0.070; P = 0.019) and intertrochanter aBMD (β, 0.049; 95% CI, 0.009–0.090; P = 0.016) in men. Conclusions: We observed positive associations of the gluteus and thigh muscle size with proximal femur volumetric BMD. Specifically, the gluteus maximus muscle CSA was associated with trochanter cortical vBMD in both men and women.
CRIS-Team Scopus Importer:2020-08-21
Keywords: cortical bone; muscle cross-sectional area; muscle density; proximal femur; quantitative computed tomography (QCT); trabecular bone

Automated quantitative morphometry of vertebral heights on spinal radiographs: comparison of a clinical workflow tool with standard 6-point morphometry - Engelke, Klaus; Stampa, B.; Steiger, P.; Fuerst, T.; Genant, H. K. (Archives of Osteoporosis, 2019)
A workflow tool for measurements of vertebral heights on lateral spine radiographs based on automated placements of 6 points per vertebra was evaluated. The tool helps to standardize point placement among operators. Its success rate is very good in normal vertebrae but lower in vertebrae with more severe fractures. Manual corrections were required in 192 of 1257 analyzed vertebrae.IntroductionTo evaluate a new workflow tool (SA) for the automated measurements of vertebral heights on lateral spine radiographs.MethodologyLateral radiographs from 200 postmenopausal women were evaluated at two visits. Genant's semi-quantitative fracture assessment (SQ) and manual quantitative morphometry (QM) results were available from prior analyses. Vertebral heights from point placements using SA were compared with manual 6-point placement QM. Differences were quantified as RMS coefficient of variations (rmsCV) and standard deviations (rmsSD).Results and conclusionsSA required manual corrections in 192 of 1257 vertebrae. SA heights were larger than QM ones by 2.2-3.6%. Correlations (r(2)>0.92) between SA and QM were very high. Differences between QM and SA were higher for fractured (SQ=2; rmsCV% 14.5%) than for unfractured vertebrae (rmsCV% 4.2-4.7%). rmsCV% for QM varied between 3 and 6% and for SA between 2.5 and 7.5%. For SA, highest rmsCV% was obtained for T4 and L4. Manual correction mostly affected the end vertebrae T4 and L4. SA helps to standardize point placement among operators. The algorithm success rate is very good in normal vertebrae but lower in vertebrae with more severe fractures, which are of greater clinical interest but are more readily recognized without morphometric measurements.
CRIS-Team WoS Importer:2019-02-21

Automated three-dimensional registration of high-resolution peripheral quantitative computed tomography data to quantify size and shape changes of arthritic bone erosions - Toepfer, Dominique; Gerner, Bastian; Finzel, Stephanie; Kraus, Sebastian; Museyko, Oleg; Schett, Georg; Engelke, Klaus (Rheumatology, 2015)
To monitor size and shape changes of bone erosions and changes in BMD in the vicinity of the erosion and in the periarticular trabecular compartment of patients with RA using high-resolution peripheral quantitative CT (HR-pQCT) imaging and to compare an automated three-dimensional (3D) image processing technique with manual measurements of erosion width and depth.The shape of 40 bone erosions and composition of bone around the erosions were analysed in the MCP joints of 22 RA patients both manually and by semi-automated 3D image processing at two different time points. Periosteal segmentation was performed using volume growing and morphological operations. Image registration was applied for transfer of baseline segmentations to follow-up datasets.Eight erosions decreased in size, 6 increased and 28 remained stable. Increasing erosions were more spherical and smaller at baseline compared with decreasing or stable erosions. BMD in the vicinity of shrinking erosions increased, while it decreased next to expanding erosions. There was moderate agreement in the determination of erosion volume between semi-automated and manual measurements, but agreement was poor when assessing changes in volume over time.Longitudinal changes in erosion size and shape and of BMD in the vicinity of an erosion can be measured. BMD changes are associated with progression and regression of erosions. However, the semi-automated and manual approaches did not classify longitudinal changes of erosion volume in the same way. Further research is necessary to define the nature of these differences.
EVALuna2:10105

Biomechanical properties of bone are impaired in patients with ACPA-positive rheumatoid arthritis and associated with the occurrence of fractures - Stemmler, Fabian; Simon, David; Liphardt, Anna-Maria; Englbrecht, Matthias; Rech, Jürgen; Hueber, Axel; Engelke, Klaus; Schett, Georg; Kleyer, Arnd (Annals of the Rheumatic Diseases, 2018)
OBJECTIVES: Bone loss is a well-established consequence of rheumatoid arthritis (RA). To date, bone disease in RA is exclusively characterised by bone density measurements, while the functional properties of bone in RA are undefined. This study aimed to define the impact of RA on the functional properties of bone, such as failure load and stiffness. METHODS: Micro-finite element analysis (µFEA) was carried out to measure failure load and stiffness of bone based on high-resolution peripheral quantitative CT data from the distal radius of anti-citrullinated protein antibody (ACPA)-positive RA (RA+), ACPA-negative RA (RA-) and healthy controls (HC). In addition, total, trabecular and cortical bone densities as well as microstructural parameters of bone were recorded. Correlations and multivariate models were used to determine the role of demographic, disease-specific and structural data of bone strength as well as its relation to prevalent fractures. RESULTS: 276 individuals were analysed. Failure load and stiffness (both P<0.001) of bone were decreased in RA+, but not RA-, compared with HC. Lower bone strength affected both female and male patients with RA+, was related to longer disease duration and significantly (stiffness P=0.020; failure load P=0.012) associated with the occurrence of osteoporotic fractures. Impaired bone strength was correlated with altered bone density and microstructural parameters, which were all decreased in RA+. Multivariate models showed that ACPA status (P=0.007) and sex (P<0.001) were independently associated with reduced biomechanical properties of bone in RA. CONCLUSION: In summary, µFEA showed that bone strength is significantly decreased in RA+ and associated with fractures.
EVALuna2:34448

BIOMECHANICAL PROPERTIES OF RADIAL BONE ARE DIFFERENT BETWEEN AUTO-ANTIBODY POSITIVE AND NEGATIVE RHEUMATOID ARTHRITIS - Stemmler, F.; Simon, David; Liphardt, Anna-Maria; Englbrecht, Matthias; Rech, Jürgen; Hueber, Axel; Engelke, Klaus; Schett, Georg; Kleyer, Arnd (2018)
EVALuna2:34998

BMD ACCURACY ERRORS IN PHANTOMLESS CALIBRATION OF CT SCANS: A SIMULATION STUDY - Bartenschlager, Stefan; Chaudry, Oliver; Dankerl, Peter; Uder, Michael; Engelke, Klaus (OSTEOPOROSIS INTERNATIONAL, 2021)
Opportunistic screening using existing CT images may be a new strategy to identify subjects at increased risk for osteoporotic fracture. Low bone mineral density (BMD) is a key parameter but routine clinical CT scans do not include a calibration phantom to calculate BMD from the measured CT values. An alternative is internal or phantomless calibration, which is based on the CT values of air and of internal tissues of the subject such as blood, muscle or adipose tissue. However, the composition and as a consequence the CT values of these so-called internal calibration materials vary among subjects, which introduces additional BMD accuracy errors compared to phantom based calibration. The objective of this study was to quantify these accuracy errors and to identify optimum combinations of internal calibration materials (IM) for BMD assessments in opportunistic screening. Based on the base material decomposition theory we demonstrate how BMD can be derived from the CT values of the internal calibration materials. 121 CT datasets of the lumbar spine form postmenopausal women were used to determine the population variance of blood assessed in the aorta or the inferior vena cava, skeletal muscle of the erector spinae or psoas, subcutaneous adipose tissue (SAT) and air. The corresponding standard deviations were used for error propagation to determine phantomless calibration related BMD accuracy errors. Using a CT value of 150 HU, a typical value of trabecular bone, simulated BMD accuracy errors for most IM combinations containing air as one of the two base materials were below 5% or 6 mg/cm3. The lowest errors were determined for the combination of blood and air (<2 mg/cm3). The combination of blood and skeletal muscle resulted in higher errors (>10.5% or >12 mg/cm3) and is not recommended. Due to possible age-related differences in tissue composition, the selection of IMs is suggested to be adapted according to the measured subject. In younger subjects without significant aortic calcifications, air and blood of the aorta may be the best combination whereas in elderly subjects, air and SAT (error of 4%) may be preferable. The use of skeletal muscle as one of the two IMs is discouraged, in particular in elderly subjects because of varying fatty infiltration. A practical implementation of the internal calibration with different IM pairs confirmed the theoretical results. In summary, compared to a phantom based calibration the phantomless approach used for opportunistic screening creates additional BMD accuracy errors of 2% or more, dependent on the used internal reference tissues. The impact on fracture prediction still must be evaluate
CRIS-Team WoS Importer:2022-03-04
Keywords: Opportunistic screening; BMD; Phantomless calibration; QCT; Accuracy errors; Base material decomposition

BMD accuracy errors specific to phantomless calibration of CT scans of the lumbar spine - Bartenschlager, Stefan; Dankerl, Peter; Chaudry, Oliver; Uder, Michael; Engelke, Klaus (Bone, 2022)
Opportunistic screening using existing CT images may be a new strategy to identify subjects at increased risk for osteoporotic fracture. Low bone mineral density (BMD) is a key parameter but routine clinical CT scans do not include a calibration phantom to calculate BMD from the measured CT values. An alternative is internal or phantomless calibration, which is based on the CT values of air and of internal tissues of the subject such as blood, muscle or adipose tissue. However, the composition and as a consequence the CT values of these so-called internal calibration materials vary among subjects, which introduces additional BMD accuracy errors compared to phantom based calibration. The objective of this study was to quantify these accuracy errors and to identify optimum combinations of internal calibration materials (IM) for BMD assessments in opportunistic screening. Based on the base material decomposition theory we demonstrate how BMD can be derived from the CT values of the internal calibration materials. 121 CT datasets of the lumbar spine form postmenopausal women were used to determine the population variance of blood assessed in the aorta or the inferior vena cava, skeletal muscle of the erector spinae or psoas, subcutaneous adipose tissue (SAT) and air. The corresponding standard deviations were used for error propagation to determine phantomless calibration related BMD accuracy errors. Using a CT value of 150 HU, a typical value of trabecular bone, simulated BMD accuracy errors for most IM combinations containing air as one of the two base materials were below 5% or 6 mg/cm3. The lowest errors were determined for the combination of blood and air (<2 mg/cm3). The combination of blood and skeletal muscle resulted in higher errors (>10.5% or >12 mg/cm3) and is not recommended. Due to possible age-related differences in tissue composition, the selection of IMs is suggested to be adapted according to the measured subject. In younger subjects without significant aortic calcifications, air and blood of the aorta may be the best combination whereas in elderly subjects, air and SAT (error of 4%) may be preferable. The use of skeletal muscle as one of the two IMs is discouraged, in particular in elderly subjects because of varying fatty infiltration. A practical implementation of the internal calibration with different IM pairs confirmed the theoretical results. In summary, compared to a phantom based calibration the phantomless approach used for opportunistic screening creates additional BMD accuracy errors of 2% or more, dependent on the used internal reference tissues. The impact on fracture prediction still must be evaluated.
CRIS-Team Scopus Importer:2022-01-28
Keywords: Accuracy errors; Base material decomposition; BMD; Opportunistic screening; Phantomless calibration; QCT

Bone anabolic changes progress in psoriatic arthritis patients despite treatment with methotrexate or tumour necrosis factor inhibitors - Finzel, Stephanie; Kraus, Sebastian; Schmidt, Sarah; Hueber, Axel; Rech, Jürgen; Engelke, Klaus; Englbrecht, Matthias; Schett, Georg (Annals of the Rheumatic Diseases, 2013)
Objectives: To investigate whether methotrexate or tumour necrosis factor inhibitors (TNFi) affect osteophyte formation in patients with psoriatic arthritis (PsA). Methods: 41 patients with PsA were examined for the presence of osteophytes and erosions at the metacarpophalangeal joints by high-resolution micro-CT imaging. The size of each individual lesion was quantified at baseline and 1-year follow-up in PsA patients treated with TNFi (N=28) or methotrexate (N=13). Groups were comparable for age, sex, disease duration and activity and baseline burden of osteophytes. Results: In total, 415 osteophytes (TNFi N=284, methotrexate N=131) were detected. Osteophyte size increased significantly from baseline to follow-up in the TNFi group (mean±SEM change +0.23±0.02 mm; p<0.0001) and the methotrexate group (+0.27±0.03 mm, p<0.0001). In both treatment groups, the majority of osteophytes showed progression (TNFi 54.3%, methotrexate 61.1%), whereas regression of lesions was rare (less than 10%). In contrast to osteophytes, clinical disease activity decreased in both groups of PsA patients and erosions showed an arrest of progression in both groups. Conclusions: Osteophytes progress in PsA patients treated with either methotrexate or TNFi. These data provide the first evidence that pathological bone formation in the appendicular skeleton of patients with PsA is not affected by current antirheumatic treatment strategies.
CRIS-Team Scopus Importer:2021-02-03

Bone changes in early inflammatory arthritis assessed with High-Resolution peripheral Quantitative Computed Tomography (HR-pQCT): A 12-month cohort study - Brunet, Scott Cameron; Finzel, Stephanie; Engelke, Klaus; Boyd, Steven Kyle; Barnabe, Cheryl; Manske, Sarah Lynn (Joint Bone Spine, 2020)
Objectives: Erosion development is of crucial significance as it impacts prognosis and therapy decisions in patients with inflammatory joint diseases. Our study aimed to determine the sensitivity of high-resolution peripheral quantitative computed tomography (HR-pQCT) to detect change of bone surface over time and to identify erosion development in early inflammatory arthritis (EIA) patients. Moreover, the contribution of prognostic factors on periarticular bone damage in the first year of diagnosis assessed by HR-pQCT was explored. Methods: 46 patients with arthritic symptoms for less than one year, and a clinical diagnosis of inflammatory arthritis were prospectively imaged at baseline and 12-months. HR-pQCT scans of the 2nd and 3rd MCP joints and CR of the hands and feet were performed. Joint space width (JSW), total bone mineral density (Tt.BMD), erosion presence and volume were assessed with HR-pQCT. Scan-rescan precision was assessed to define an individual-level least significant change (LSC) criterion. Regression analyses explored prognostic factors for bone damage progression. Results: We observed no significant group-level changes in JSW, Tt.BMD or erosion volume. 20% or fewer joints demonstrated individual-level changes greater than the LSC criterion for mean JSW, Tt.BMD and erosion volume. HR-pQCT detected more erosions than CR in the 2nd and 3rd MCP. Increased symptom duration at diagnosis was weakly associated (P < 0.10) with lower JSW minimum and higher JSW standard deviation. Conclusions: Gradual degradation of JSW, proportional to symptom duration, was detected by HR-pQCT. EIA patients need to be closely monitored for exacerbation of arthritis and progression of periarticular bone damage.
CRIS-Team Scopus Importer:2020-12-11
Keywords: Bone erosions; Bone mineral density; Early inflammatory arthritis; High resolution peripheral quantitative computed tomography (HR-pQCT); Rheumatoid arthritis

Bone loss before the clinical onset of rheumatoid arthritis in subjects with anticitrullinated protein antibodies - Kleyer, Arnd; Finzel, Stephanie; Rech, Jürgen; Manger, Bernhard; Krieter, Manuel; Faustini, Francesca; Araujo, Elisabeth; Hueber, Axel; Harre, Ulrike; Engelke, Klaus; Schett, Georg (Annals of the Rheumatic Diseases, 2014)
Anticitrullinated protein antibodies (ACPA) are a major risk factor for bone loss in rheumatoid arthritis (RA). We have recently shown that ACPA directly induce bone loss by stimulating osteoclast differentiation. As ACPA precede the clinical onset of RA by years, we hypothesised that ACPA positive healthy individuals may already show skeletal changes.We performed a comparative micro-CT analysis of the bone microstructure in the metacarpophalangeal joints of ACPA positive and ACPA negative healthy individuals without clinical signs of arthritis.ACPA positive (n=15) and negative (n=15) healthy individuals were not different in age (48.2±4.1 vs 51.4±3.8 years, p=0.57) or gender (eight women and two men in both groups). Bone mineral density was significantly reduced in ACPA positive individuals (mean±SEM 280±11 mg/cm(3)) compared with controls (327±6). Bone loss was based on cortical bone changes, with significant (p=0.044) reduction in cortical thickness in the ACPA positive group (mean±SEM 0.22±0.03 mm) compared with controls (0.32±0.03 mm). Areas of cortical porosity were significantly (p=0.0005) more widespread in ACPA positive (mean±SEM 7.4±1.4%) than in ACPA negative individuals (1.0±0.3%).Structural bone damage starts before the clinical onset of arthritis in subjects with ACPA. These findings revise the concept that bone damage is an exclusive consequence of synovitis in patients with R
EVALuna2:10080

Cartilage morphology assessed by high resolution micro-computed tomography in non OA knees - Delecourt, C.; Relier, M.; Touraine, S.; Bouhadoun, H.; Engelke, Klaus; Laredo, J. D.; Chappard, C. (Osteoarthritis and Cartilage, 2016)
OBJECTIVE: At the microscopic level, there is no established 3D method to measure cartilage volume and thickness. An easy, precise and accurate volume and thickness measurements of human cartilage has been developed from micro-computed tomography (micro-CT) images. DESIGN: In the medial tibial plateau of twenty nine left cadaveric knees classified as normal, vertical cores (7 mm in diameter) were extracted in three locations: lateral (LAT), medial posterior (MP) and medial anterior (MA). The cores were imaged in mineral oil with micro-CT (voxel size 10.2 μm) and were measured cartilage volume (Cart.Vol, mm(3)) and cartilage thickness (Cart.Th, mm) using a thickness plugin. Short term reproducibility and standard deviation (ST_RMSCV%, ST_RMSSD, mm) were determined. To assess accuracy, holes with diameters of 2 mm, 3 mm, and 4 mm were artificially generated and nominal and measured hole sizes were compared. RESULTS: Precision of Cart.Vol_ST_RMSCV% was 1.35%. The mean biases between nominal hole volume and measurements were -0.49 ± 1.5 mm(3) (2 mm), -0.41 ± 4.2 mm(3) (3 mm) and +0.34 ± 4.4 mm(3) (4 mm). ST_RMSSD was 100 times lower than the biological variation and the highest bias to measure volume was 24 times lower. Cart.Th results statistically differed among core extraction locations: 1.75 ± 0.28 mm (LAT), 1.84 ± 0.40 mm (MP) and 2.32 ± 0.41 mm (MA). CONCLUSION: With a standard laboratory micro-CT system, it was possible to measure cartilage volume and thickness with good precision and accuracy relative to the biological variation of the specimen cohort. Cartilage measurements from micro-CT probably will improve the knowledge of the relationship between cartilage and subchondral bone and may allow to better understand the OA process.
EVALuna2:33282

Catabolic and anabolic periarticular bone changes in patients with rheumatoid arthritis: A computed tomography study on the role of age, disease duration and bone markers - Aschenberg, Sophie; Finzel, Stephanie; Schmidt, Sarah; Kraus, Sebastian; Engelke, Klaus; Englbrecht, Matthias; Rech, Jürgen; Schett, Georg (Arthritis Research & Therapy, 2013)
Introduction: The aim of this study was to determine the factors, including markers of bone resorption and bone formation, which determine catabolic and anabolic periarticular bone changes in patients with rheumatoid arthritis (RA).Methods: Forty RA patients received high-resolution peripheral quantitative computed tomography (HR-pQCT) analysis of the metacarpophalangeal joints II and III of the dominantly affected hand at two sequential time points (baseline, one year follow-up). Erosion counts and scores as well as osteophyte counts and scores were recorded. Simultaneously, serum markers of bone resorption (C-terminal telopeptide of type I collagen (CTX I), tartrate-resistant acid phosphatase 5b (TRAP5b)), bone formation (bone alkaline phosphatase (BAP), osteocalcin (OC)) and calcium homeostasis (parathyroid hormone (PTH), 25-hydroxyvitamin D3 (Vit D)) were assessed. Bone biomarkers were correlated to imaging data by partial correlation adjusting for various demographic and disease-specific parameters. Additionally, imaging data were analyzed by mixed linear model regression.Results: Partial correlation analysis showed that TRAP5b levels correlate significantly with bone erosions, whereas BAP levels correlate with osteophytes at both time points. In the mixed linear model with erosions as the dependent variable, disease duration (P <0.001) was the key determinant for these catabolic bone changes. In contrast, BAP (P = 0.001) as well as age (P = 0.018), but not disease duration (P = 0.762), were the main determinants for the anabolic changes (osteophytes) of the periarticular bone in patients with RA.Conclusions: This study shows that structural bone changes assessed with HR-pQCT are accompanied by alterations in systemic markers of bone resorption and bone formation. Besides, it can be shown that bone erosions in RA patients depend on disease duration, whereas osteophytes are associated with age as well as serum level of BAP. Therefore, these data not only suggest that different variables are involved in formation of bone erosions and osteophytes in RA patients, but also that periarticular bone changes correlate with alterations in systemic markers of bone metabolism, pointing out BAP as an important parameter. © 2013 Aschenberg et al.; licensee BioMed Central Ltd.
CRIS-Team Scopus Importer:2021-02-03
Keywords: Bone biomarkers; Bone formation; Bone resorption; Computed tomography; Rheumatoid arthritis

Changements osseux évalués par tomodensitométrie quantitative périphérique haute résolution (HR-pQCT) dans l'arthrite inflammatoire précoce: étude longitudinale sur 12 mois - Brunet, Scott C.; Finzel, Stephanie; Engelke, Klaus; Boyd, Steven K.; Barnabe, Cheryl; Manske, Sarah L. (Revue du Rhumatisme (Edition Francaise), 2021)
Objectifs: L'apparition d’érosions dans les arthropathies inflammatoires revêt une importance majeure car elles ont une incidence sur le pronostic et les décisions thérapeutiques. Notre étude visait à déterminer la sensibilité de la tomodensitométrie quantitative périphérique haute résolution (HR-pQCT) pour détecter des changements de la surface osseuse au cours du temps et identifier l'apparition d’érosions chez les patients présentant une arthrite inflammatoire précoce (AIP). Nous avons également exploré la contribution de facteurs de pronostic aux dommages osseux périarticulaires évalués par HR-pQCT dans l'année suivant le diagnostic. Méthodes: Quarante-six patients présentant des symptômes d'arthrites depuis moins d'un an et ayant reçu un diagnostic clinique d'arthrite inflammatoire ont passé un examen d'imagerie prospectif à l'inclusion et à 12 mois. Une HR-pQCT de la deuxième et de la troisième articulation MCP et des radiographies conventionnelles (RC) des mains et des pieds ont été réalisées. La largeur de l'interligne articulaire, la densité minérale osseuse totale (DMOt), la présence d’érosions et leur volume ont été évalués par HR-pQCT. La précision des analyses scan–rescan a été évaluée afin de définir un critère de plus petite variation significative (PPVS) au niveau individuel. Des analyses de régression ont exploré les facteurs de pronostic de progression des dommages osseux. Résultats: Nous n'avons pas constaté de changements significatifs au niveau du groupe concernant la largeur de l'interligne, la DMOt ou le volume des érosions. Jusqu’à 20 % d'articulations ont présenté des changements individuels supérieurs au critère PPVS pour la largeur d'interligne moyenne, la DMOt et le volume des érosions. L'HR-pQCT a détecté davantage d’érosions que la RC dans la 2e et la 3e MCP. Une durée des symptômes plus longue au moment du diagnostic a été faiblement associée (p < 0,10) à une largeur d'interligne minimale plus faible et à un écart-type d'interligne plus élevé. Conclusions: Une dégradation progressive de l'interligne proportionnelle à la durée des symptômes a été détectée par HR-pQCT. Les patients présentant une AIP doivent faire l'objet d'une surveillance étroite pour détecter l'exacerbation de l'arthrite et la progression des dommages osseux périarticulaires.
CRIS-Team Scopus Importer:2021-10-01
Keywords: Arthrite inflammatoire précoce; Densité minérale osseuse; Polyarthrite rhumatoïde; Tomodensitométrie quantitative périphérique haute résolution (HR-pQCT); Érosions osseuses

Characterization and quantification of angiogenesis in rheumatoid arthritis in a mouse model using ?CT - Gayetskyy, Svitlana; Museyko, Oleg; Käßer, Johannes; Heß, Andreas; Schett, Georg; Engelke, Klaus (BMC Musculoskeletal Disorders, 2014)
Angiogenesis is an important pathophysiological process of chronic inflammation, especially in inflammatory arthritis. Quantitative measurement of changes in vascularization may improve the diagnosis and monitoring of arthritis. The aim of this work is the development of a 3D imaging and analysis framework for quantification of vascularization in experimental arthritis.High-resolution micro-computed tomography (?CT) was used to scan knee joints of arthritic human tumor necrosis factor transgenic (hTNFtg) mice and non-arthritic wild-type controls previously perfused with lead-containing contrast agent Microfil MV-122. Vessel segmentation was performed by combination of intensity-based (local adaptive thresholding) and form-based (multi-scale method) segmentation techniques. Four anatomically defined concentric spherical shells centered in the knee joint were used as analysis volumes of interest. Vessel density, density distribution as well as vessel thickness, surface, spacing and number were measured. Simulated digital vessel tree models were used for validation of the algorithms.High-resolution ?CT allows the quantitative assessment of the vascular tree in the knee joint during arthritis. Segmentation and analysis were highly automated but occasionally required manual corrections of the vessel segmentation close to the bone surfaces. Vascularization was significantly increased in arthritic hTNFtg mice compared to wild type controls. Precision errors for the morphologic parameters were smaller than 3% and 6% for intra- and interoperator analysis, respectively. Accuracy errors for vessel thickness were around 20% for vessels larger than twice the resolution of the scanner.Arthritis-induced changes of the vascular tree, including detailed and quantitative description of the number of vessel branches, length of vessel segments and the bifurcation angle, can be detected by contrast-enhanced high-resolution ?CT.
EVALuna2:8512

Clinical Use of Quantitative Computed Tomography-Based Advanced Techniques in the Management of Osteoporosis in Adults: the 2015 ISCD Official Positions-Part III - Engelke, Klaus; Lang, Thomas; Khosla, Sundeep; Qin, Ling; Zysset, Philippe; Leslie, William D.; Shepherd, John A.; Shousboe, John T. (Journal of Clinical Densitometry, 2015)
The International Society for Clinical Densitometry (ISCD) has developed new official positions for the clinical use of computed tomography (CT) scans acquired without a calibration phantom, for example, CT scans obtained for other diagnosis such as colonography. This also addresses techniques suggested for opportunistic screening of osteoporosis. The ISCD task force for quantitative CT reviewed the evidence for clinical applications of these new techniques and presented a report with recommendations at the 2015 ISCD Position Development Conference. Here we discuss the agreed upon ISCD official positions with supporting medical evidence, rationale, controversy, and suggestions for further study. Advanced techniques summarized as statistical parameter mapping methods were also reviewed. Their future use is promising but the clinical application is premature. The clinical use of QCT of the hip is addressed in part I and of finite element analysis of the hip and spine in part II.
EVALuna2:10115

Clinical Use of Quantitative Computed Tomography-Based Finite Element Analysis of the Hip and Spine in the Management of Osteoporosis in Adults: the 2015 ISCD Official Positions-Part II - Zysset, Philippe; Qin, Ling; Lang, Thomas; Khosla, Sundeep; Leslie, William D.; Shepherd, John A.; Schousboe, John T.; Engelke, Klaus (Journal of Clinical Densitometry, 2015)
The International Society for Clinical Densitometry (ISCD) has developed new official positions for the clinical use of quantitative computed tomography (QCT)-based finite element analysis of the spine and hip. The ISCD task force for QCT reviewed the evidence for clinical applications and presented a report with recommendations at the 2015 ISCD Position Development Conference. Here we discuss the agreed upon ISCD official positions with supporting medical evidence, rationale, controversy, and suggestions for further study. Parts I and III address the clinical use of QCT of the hip, and the clinical feasibility of existing techniques for opportunistic screening of osteoporosis using CT scans obtained for other diagnosis such as colonography was addressed.
EVALuna2:10119

Clinical Use of Quantitative Computed Tomography (QCT) of the Hip in the Management of Osteoporosis in Adults: the 2015 ISCD Official Positions-Part I - Engelke, Klaus; Lang, Thomas; Khosla, Sundeep; Qin, Ling; Zysset, Philippe; Leslie, William D.; Shepherd, John A.; Schousboe, John T. (Journal of Clinical Densitometry, 2015)
The International Society for Clinical Densitometry (ISCD) has developed new official positions for the clinical use of quantitative computed tomography of the hip. The ISCD task force for quantitative computed tomography reviewed the evidence for clinical applications and presented a report with recommendations at the 2015 ISCD Position Development Conference. Here, we discuss the agreed on ISCD official positions with supporting medical evidence, rationale, controversy, and suggestions for further study. Parts II and III address the advanced techniques of finite element analysis applied to computed tomography scans and the clinical feasibility of existing techniques for opportunistic screening of osteoporosis using computed tomography scans obtained for other diagnosis such as colonography was addressed.
EVALuna2:10114

Comparison of proximal femur and vertebral body strength improvements in the FREEDOM trial using an alternative finite element methodology - Zysset, Philippe; Pahr, Dieter; Engelke, Klaus; Genant, Harry K.; Mcclung, Michael R.; Kendler, David L.; Recknor, Christopher; Kinzl, Michael; Schwiedrzik, Jakob; Museyko, Oleg; Wang, Andrea; Libanati, Cesar (Bone, 2015)
Denosumab reduced the incidence of new fractures in postmenopausal women with osteoporosis by 68% at the spine and 40% at the hip over 36months compared with placebo in the FREEDOM study. This efficacy was supported by improvements from baseline in vertebral (18.2%) strength in axial compression and femoral (8.6%) strength in sideways fall configuration at 36months, estimated in Newtons by an established voxel-based finite element (FE) methodology. Since FE analyses rely on the choice of meshes, material properties, and boundary conditions, the aim of this study was to independently confirm and compare the effects of denosumab on vertebral and femoral strength during the FREEDOM trial using an alternative smooth FE methodology. Unlike the previous FE study, effects on femoral strength in physiological stance configuration were also examined. QCT data for the proximal femur and two lumbar vertebrae were analyzed by smooth FE methodology at baseline, 12, 24, and 36months for 51 treated (denosumab) and 47 control (placebo) subjects. QCT images were segmented and converted into smooth FE models to compute bone strength. L1 and L2 vertebral bodies were virtually loaded in axial compression and the proximal femora in both fall and stance configurations. Denosumab increased vertebral body strength by 10.8%, 14.0%, and 17.4% from baseline at 12, 24, and 36months, respectively (p<0.0001). Denosumab also increased femoral strength in the fall configuration by 4.3%, 5.1%, and 7.2% from baseline at 12, 24, and 36months, respectively (p<0.0001). Similar improvements were observed in the stance configuration with increases of 4.2%, 5.2%, and 5.2% from baseline (p<=0.0007). Differences between the increasing strengths with denosumab and the decreasing strengths with placebo were significant starting at 12months (vertebral and femoral fall) or 24months (femoral stance). Using an alternative smooth FE methodology, we confirmed the significant improvements in vertebral body and proximal femur strength previously observed with denosumab. Estimated increases in strength with denosumab and decreases with placebo were highly consistent between both FE techniques.
EVALuna2:10112

CT Imaging: Basics and New Trends - Peyrin, F.; Engelke, Klaus (Handbook of Particle Detection and Imaging, 2021)
This chapter presents the principles of X-ray CT and its evolution during the last 50 years. The first section describes the physical basis, tomographic image reconstruction algorithms, and the source of artifacts in X-ray CT images. The second section is devoted to the evolution of CT technology from the first translation-rotation systems to multi-detector row spiral CTs currently used today. The next section addresses specific developments of CT technology and applications, like cone-beam, dual energy, and quantitative CT. Section “New Developments in CT Technology and Applications” covers radiation exposure delivered to the patient and its evaluation. Finally, the last section addresses developments in micro- and nano-CT, which is a rapidly evolving area in preclinical imaging and biology.
CRIS-Team Scopus Importer:2024-12-16

Decreased muscle strength and thigh muscle area assessed with CT imaging in older Chinese adults with long duration of type 2 diabetes - Yuan, Yi; Li, Sidong; Yin, Lu; Su, Yongbin; Guo, Zhe; Liu, Yandong; Blake, Glen M.; Wang, Ling; Liu, Yajun; Cheng, Xiaoguang; Engelke, Klaus; Vlug, Annegreet G. (Journal of Nutrition, Health & Aging, 2025)
Objective: We aimed to compare muscle strength, physical performance, and muscle parameters in non-diabetic and type 2 diabetes mellitus (T2DM) older adults and to determine the association of the duration of diabetes with these outcomes. Design: A cross-sectional study. Setting: The China Action on Spine and Hip Status study (CASH). Participants: 301 participants enrolled from a subcohort of CASH, of which 114 were diagnosed with well-controlled type 2 diabetes mellitus, Measurements: We measured physical performance and muscle strength with the timed up-and-go test (TUG) and handgrip strength (HGS) and measured the area and density of the thigh, gluteus and trunk muscles (core muscles) using quantitative CT scans. Results: Participants with long-term (≥10 years) diabetes had a longer TUG (β coefficient: 0.64 [95% CI, 0.06, 1.22]; P = 0.030) and a lower HGS (−2.29 [−4.48, −0.10]; P = 0.041) as well as a lower muscle area of the thigh (−7.10 [−13.44, −0.76]; P = 0.028). The lower HGS among patients with long-term (≥10 years) diabetes was largely mediated by muscle area of the thigh (compared with non-diabetic controls: percentage mediated, 38.3%; P = 0.023; compared with <10 years diabetes: percentage mediated, 51.8%; P = 0.039). Conclusions: Older adults with long-term (≥10 years) diabetes had lower TUG and HGS than either non-diabetic participants, and the difference in HGS was largely mediated by a decrease in muscle area of the thigh muscles. Our finding suggested that long duration of diabetes, even in well-controlled subjects, may be associated with poor physical functions.
CRIS-Team Scopus Importer:2025-02-28
Keywords: Grip strength; Muscle density; Muscle size; Timed up and go test; Type 2 diabetes

Decreased Quantity and Quality of the Periarticular and Nonperiarticular Bone in Patients With Rheumatoid Arthritis: A Cross-Sectional HR-pQCT Study - Kocijan, Roland; Finzel, Stephanie; Englbrecht, Matthias; Engelke, Klaus; Rech, Juergen; Schett, Georg (Journal of Bone and Mineral Research, 2014)
Rheumatoid arthritis (RA) is a highly bone destructive disease. Although it is well established that RA leads to bone loss and increased fracture risk, current knowledge on the microstructural changes of bone in RA is still limited. The purpose of this study was to assess the microstructure of periarticular and nonperiarticular bone in female and male RA patients and compare it with respective healthy controls. We performed two high-resolution peripheral quantitative computed tomography (HR-pQCT; Xtreme-CT) scans, one of the distal radius and one of the ultradistal radius in 90 patients with RA (60 females, 30 males) and 70 healthy controls (40 females, 30 males) matched for sex, age, and body mass index. Volumetric bone mineral density (vBMD), bone geometry, and bone microstructure including trabecular bone volume fraction (BV/TV), trabecular number (Tb.N), trabecular thickness (Tb.Th), cortical thickness (Ct.Th) and cortical porosity (Ct.Po) were assessed. At the distal and ultradistal radius, trabecular (p = 0.005 and p < 0.001) and cortical BMD (p < 0.001 and p < 0.001) were significantly decreased in male and female patients with RA, respectively. BV/TV was also decreased at both sites, based on lower Tb.N in female RA (p < 0.001 for both sites) and lower Tb.Th (p = 0.034 and p = 0.005) in male RA patients compared with respective healthy controls. Cortical thinning (p = 0.018 and p = 0.002) but not Ct.Po (p = 0.070 and p = 0.275) was pronounced in male and female RA patients at the distal radius. Cortical perimeter was increased in male and female RA patients at both sites. Multiple regression models showed that bone geometry (cortical perimeter) is predominantly influenced by age of the RA patient, cortical thickness by both age and disease duration, and trabecular microstructure predominantly by the disease duration. In summary, these data show profound deterioration of bone microstructure in the appendicular skeleton of RA patients at both periarticular and nonperiarticular sites. © 2014 American Society for Bone and Mineral Research.
EVALuna2:10056

Deletion of the receptor tyrosine kinase Tyro3 inhibits synovial hyperplasia and bone damage in arthritis - Ruiz-Heiland, Gisela; Zhao, Yi; Derer, Anja; Braun, Timm; Engelke, Klaus; Neumann, Elena; Mueller-Ladner, Ulf; Liu, Yi; Zwerina, Jochen; Schett, Georg (Annals of the Rheumatic Diseases, 2014)
To test whether the tyrosine kinase Tyro3 affects arthritis. Tyro3, the ligand of growth arrest-specific protein 6 (GAS6) is a receptor tyrosine kinase involved in cell survival. Tyro3 and GAS6 are expressed in the arthritic synovium, and in vitro studies have shown their role in osteoclast differentiation.Bone was assessed by micro CT and histomorphometry in Tyro3-deficient (Tyro3(-/-)) and wild-type mice. Arthritis was induced in both genotypes, and Gas6 level was measured by ELISA. Synovitis, synovial hyperplasia, bone erosion, osteoclast activation and osteoclast gene expression were assessed by histomorphometry and reverse transcriptase-PCR, respectively. In vitro osteoclast differentiation assays were performed in Tyro3(-/-) and wild-type mice. Furthermore, effects of Tyro3 and GAS6 on human synovial fibroblast proliferation and osteoclastogenesis were assessed in human cells.Tyro3(-/-) mice had significantly higher bone mass than wild-type littermates. Induction of arthritis increased GAS6 serum levels. Arthritic Tyro3(-/-) mice showed less synovial hyperplasia, osteoclast numbers and bone damage compared with controls. In vivo expression of osteoclast-associated receptor and receptor activator of nuclear factor-?B and in vitro osteoclastogenesis were impaired in Tyro3(-/-) mice. GAS6 also induced synovial fibroblast proliferation and osteoclast differentiation in human cells in Tyro3-dependent manner.These findings indicate that Tyro3 is a critical signal for synovial hyperplasia, osteoclast differentiation and bone erosion during arthritis. GAS6 and Tyro3 therefore constitute therapeutic targets to inhibit synovial hyperplasia and associated bone erosion.
EVALuna2:10050

Detraining Effects on Muscle Quality in Older Men with Osteosarcopenia. Follow-Up of the Randomized Controlled Franconian Osteopenia and Sarcopenia Trial (FrOST) - Ghasemikaram, Mansour; Engelke, Klaus; Kohl, Matthias; von Stengel, Simon; Kemmler, Wolfgang (Nutrients, 2021)
The present study aimed to determine the effect of detraining on muscle quality (MQ) in older men with osteosarcopenia. Forty-three community-dwelling older men (78 ± 4 years) were randomly allocated to a consistently supervised high-intensity resistance exercise training (HIRT) group (n = 21) or a control group (CG, n = 22). The HIRT scheduled a periodized single set protocol twice weekly. After the intervention, the men were subjected to six months of detraining. Muscle quality (MQ), defined as maximum isokinetic hip/leg extensor strength per unit of mid-thigh intra-fascia volume, was determined by magnetic resonance imaging (MRI) or per unit of thigh muscle mass assessed by dual-energy X-ray absorptiometry (DXA). Intention-to-treat analysis with multiple imputations was applied. We observed significant exercise effects for MQ (p = 0.001). During detraining, the HIRT group lost about one-third of the intervention-induced gain and displayed significantly (p = 0.001) higher MQ reductions compared to the CG. Nevertheless, after training and detraining, the overall intervention effect on MQ remained significant (p ≤ 0.004). In summary, six months of absence from HIRT induce a significant deleterious effect on MQ in older osteosarcopenic men. We conclude that intermitted training programs with training breaks of six months and longer should be replaced by largely continuous exercise programs, at least when addressing MQ parameters.
CRIS-Team Scopus Importer:2021-06-18
Keywords: detraining; exercise training; muscle mass; muscle strength; resistance training

Differences in bone structure between rheumatoid arthritis and psoriatic arthritis patients relative to autoantibody positivity - Kocijan, Roland; Finzel, Stephanie; Englbrecht, Matthias; Engelke, Klaus; Rech, Juergen; Schett, Georg (Annals of the Rheumatic Diseases, 2014)
To investigate whether trabecular and cortical bone structure differ between patients with rheumatoid arthritis (RA) and psoriatic arthritis (PsA). So far, no study has performed a detailed comparative analysis of bone structure in patients with RA and PsA.110 patients (60 RA, 50 PsA) received high-resolution peripheral quantitative CT of the distal radius. Demographic and disease-specific parameters including anti-rheumatic treatment, bone erosion status and previous fractures were recorded.RA and PsA patients were comparable in age, gender, body mass index, disease duration, disease activity, functional status, antirheumatic treatment and bone erosion status. No significant differences were found for volumetric bone mineral density (BMD), including total BMD (300±77 vs 316±62 mgHA/cm(3)), trabecular BMD (152±46 vs 165±40 mgHA/cm(3)) and cortical BMD (787±113 vs 818±76 mgHA/cm(3)) when comparing RA patients to PsA patients, respectively. However, in contrast to seronegative RA, seropositive RA showed significantly reduced trabecular BMD (p=0.007), bone volume per tissue volume (p=0.007) and trabecular number (p=0.044), as well as a strong trend towards higher trabecular inhomogeneity compared to PsA patients. In the regression analysis, higher age, female gender and presence of autoantibodies were independently associated with trabecular bone loss.Seropositive RA exhibits more profound changes in trabecular bone architecture than seronegative RA or PsA. The data support the concept that seropositive RA is a disease entity that is distinct from seronegative RA and PsA.
EVALuna2:10051

Differences in Hip Geometry Between Female Subjects With and Without Acute Hip Fracture: A Cross-Sectional Case-Control Study - Wang, Ling; Yang, Minghui; Liu, Yandong; Ge, Yufeng; Zhu, Shiwen; Su, Yongbin; Cheng, Xiaoguang; Wu, Xinbao; Blake, Glen M.; Engelke, Klaus (Frontiers in Endocrinology, 2022)
Background and Purpose: Although it is widely recognized that hip BMD is reduced in patients with hip fracture, the differences in geometrical parameters such as cortical volume and thickness between subjects with and without hip fracture are less well known. Materials and Methods: Five hundred and sixty two community-dwelling elderly women with hip CT scans were included in this cross-sectional study, of whom 236 had an acute hip fracture. 326 age matched women without hip fracture served as controls. MIAF-Femur software was used for the measurement of the intact contralateral femur in patients with hip fracture and the left femur of the controls. Integral and cortical volumes (Vols) of the total hip (TH), femoral head (FH), femoral neck (FN), trochanter (TR) and intertrochanter (IT) were analyzed. In the FH and FN the volumes were further subdivided into superior anterior (SA) and posterior (SP) as well as inferior anterior (IA) and posterior (IP) quadrants. Cortical thickness (CortThick) was determined for all sub volumes of interest (VOIs) listed above. Results: The average age of the control and fracture groups was 71.7 and 72.0 years, respectively. The fracture patients had significantly lower CortThick and Vol of all VOIs except for TRVol. In the fracture patients, cortical thickness and volume at the FN were significantly lower in all quadrants except for cortical volume of quadrant SA (p= 0.635). Hip fracture patients had smaller integral FN volume and cross-sectional area (CSA) before and after adjustment of age, height and weight. With respect to hip fracture discrimination, cortical volume performed poorer than cortical thickness across the whole proximal femur. The ratio of Cort/TrabMass (RCTM), a measure of the internal distribution of bone, performed better than cortical thickness in discriminating hip fracture risk. The highest area under curve (AUC) value of 0.805 was obtained for the model that included THCortThick, FHVol, THRCTM and FNCSA. Conclusion: There were substantial differences in total and cortical volume as well as cortical thickness between fractured and unfractured women across the proximal femur. A combination of geometric variables resulted in similar discrimination power for hip fracture risk as aBMD.
CRIS-Team Scopus Importer:2022-03-25
Keywords: cortical thickness; discrimination; geometry; hip fracture; volume

DIFFERENCES IN HIP GEOMETRY BETWEEN FEMALE SUBJECTS WITH AND WITHOUT ACUTE HIP FRACTURE - Wang, L.; Su, Y.; Cheng, X.; Wu, X.; Yang, M.; Yang, R.; Engelke, Klaus (OSTEOPOROSIS INTERNATIONAL, 2019)
CRIS-Team WoS Importer:2019-08-02

Dose-efficient assessment of trabecular microstructure using ultra-high-resolution photon-counting CT - Peña, Jaime A.; Klein, Laura; Maier, Joscha; Damm, Timo; Schlemmer, Heinz Peter; Engelke, Klaus; Glüer, Claus Christian; Kachelrieß, Marc; Sawall, Stefan (Zeitschrift für Medizinische Physik, 2022)
Photon-counting (PC) detectors for clinical computed tomography (CT) may offer improved imaging capabilities compared to conventional energy-integrating (EI) detectors, e.g. superior spatial resolution and detective efficiency. We here investigate if PCCT can reduce the administered dose in examinations aimed at quantifying trabecular bone microstructure. Five human vertebral bodies were scanned three times in an abdomen phantom (QRM, Germany) using an experimental dual-source CT (Somatom CounT, Siemens Healthineers, Germany) housing an EI detector (0.60 mm pixel size at the iso-center) and a PC detector (0.25 mm pixel size). A tube voltage of 120 kV was used. Tube current-time product for EICT was 355 mAs (23.8 mGy CTDI32 cm). Dose-matched UHR-PCCT (UHRdm, 23.8 mGy) and noise-matched acquisitions (UHRnm, 10.5 mGy) were performed and reconstructed to a voxel size of 0.156 mm using a sharp kernel. Measurements of bone mineral density (BMD) and trabecular separation (Tb.Sp) and Tb.Sp percentiles reflecting the different scales of the trabecular interspacing were performed and compared to a gold-standard measurement using a peripheral CT device (XtremeCT, SCANCO Medical, Switzerland) with an isotropic voxel size of 0.082 mm and 6.6 mGy CTDI10 cm. The image noise was quantified and the relative error with respect to the gold-standard along with the agreement between CT protocols using Lin's concordance correlation coefficient (rCCC) were calculated. The Mean ± StdDev of the measured image noise levels in EICT was 109.6 ± 3.9 HU. UHRdm acquisitions (same dose as EICT) showed a significantly lower noise level of 78.6 ± 4.6 HU (p = 0.0122). UHRnm (44% dose of EICT) showed a noise level of 115.8 ± 3.7 HU, very similar to EICT at the same spatial resolution. For BMD the overall Mean ± StdDev for EI, UHRdm and UHRnm were 114.8 ± 28.6 mgHA/cm3, 121.6 ± 28.8 mgHA/cm3 and 121.5 ± 28.6 mgHA/cm3, respectively, compared to 123.1 ± 25.5 mgHA/cm3 for XtremeCT. For Tb.Sp these values were 1.86 ± 0.54 mm, 1.80 ± 0.56 mm and 1.84 ± 0.52 mm, respectively, compared to 1.66 ± 0.48 mm for XtremeCT. The ranking of the vertebrae with regard to Tb.Sp data was maintained throughout all Tb.Sp percentiles and among the CT protocols and the gold-standard. The agreement between protocols was very good for all comparisons: UHRnm vs. EICT (BMD rCCC = 0.97; Tb.Sp rCCC = 0.998), UHRnm vs. UHRdm (BMD rCCC = 0.998; Tb.Sp rCCC = 0.993) and UHRdm vs. EICT (BMD rCCC = 0.97; Tb.Sp rCCC = 0.991). Consequently, the relative RMS-errors from linear regressions against the gold-standard for EICT, UHRdm and UHRnm were very similar for BMD (7.1%, 5.2% and 5.4%) and for Tb.Sp (3.3%, 3.3% and 2.9%), with a much lower radiation dose for UHRnm. Short-term reproducibility for BMD measurements was similar and below 0.2% for all protocols, but for Tb.Sp showed better results for UHR (about 1/3 of the level for EICT). In conclusion, CT with UHR-PC detectors demonstrated lower image noise and better reproducibility for assessments of bone microstructure at similar dose levels. For UHRnm, radiation exposure levels could be reduced by 56% without deterioration of performance levels in the assessment of bone mineral density and bone microstructure.
CRIS-Team Scopus Importer:2022-12-23
Keywords: CT; Image noise reduction; Osteoporosis; Photon-counting CT; Radiation dose; Trabecular bone microstructure

EFFECT OF AGEING ON FAT INFILTRATION OF THIGH AND PARASPINAL MUSCLES IN MEN - Engelke, Klaus; Ghasemikaram, Mansour; Chaurdy, O.; Uder, Michael; Nagel, Armin Michael; Jacob, F.; Kemmler, Wolfgang (AGING CLINICAL AND EXPERIMENTAL RESEARCH, 2022)
CRIS-Team WoS Importer:2022-10-14

Effect of Denosumab Compared With Risedronate on Bone Strength in Patients Initiating or Continuing Glucocorticoid Treatment - Geusens, Piet; Bevers, Melissa S. A. M.; Van Rietbergen, Bert; Messina, Osvaldo D.; Lespessailles, Eric; Oliveri, Beatriz; Chapurlat, Roland; Engelke, Klaus; Chines, Arkadi; Huang, Shuang; Saag, Kenneth G.; Van Den Bergh, Joop P. (Journal of Bone and Mineral Research, 2022)
In a randomized clinical trial in patients initiating glucocorticoid therapy (GC-I) or on long-term therapy (GC-C), denosumab every 6 months increased spine and hip bone mineral density at 12 and 24 months significantly more than daily risedronate. The aim of this study was to evaluate the effects of denosumab compared with risedronate on bone strength and microarchitecture measured by high-resolution peripheral quantitative computed tomography (HR-pQCT) in GC-I and GC-C. A subset of 110 patients had high-resolution peripheral quantitative computed tomography (HR-pQCT) scans of the distal radius and tibia at baseline and at 12 and 24 months. Cortical and trabecular microarchitecture were assessed with standard analyses and failure load (FL) with micro-finite element analysis. At the radius at 24 months, FL remained unchanged with denosumab and significantly decreased with risedronate in GC-I (-4.1%, 95% confidence interval [CI] -6.4, -1.8) and, in GC-C, it significantly increased with denosumab (4.3%, 95% CI 2.1, 6.4) and remained unchanged with risedronate. Consequently, FL was significantly higher with denosumab than with risedronate in GC-I (5.6%, 95% CI 2.4, 8.7, p < 0.001) and in GC-C (4.1%, 95% CI 1.1, 7.2, p = 0.011). We also found significant differences between denosumab and risedronate in percentage changes in cortical and trabecular microarchitectural parameters in GC-I and GC-C. Similar results were found at the tibia. To conclude, this HR-pQCT study shows that denosumab is superior to risedronate in terms of preventing FL loss at the distal radius and tibia in GC-I and in increasing FL at the radius in GC-C, based on significant differences in changes in the cortical and trabecular bone compartments between treatment groups in GC-I and GC-C. These results suggest that denosumab could be a useful therapeutic option in patients initiating GC therapy or on long-term GC therapy and may contribute to treatment decisions in this patient population. (c) 2022 The Authors. Journal of Bone and Mineral Research published by Wiley Periodicals LLC on behalf of American Society for Bone and Mineral Research (ASBMR).
CRIS-Team WoS Importer:2022-04-29

Effects of 16 months of high intensity resistance training on thigh muscle fat infiltration in elderly men with osteosarcopenia - Ghasemikaram, Mansour; Chaudry, Oliver; Nagel, Armin Michael; Uder, Michael; Jakob, Franz; Kemmler, Wolfgang; Kohl, Matthias; Engelke, Klaus (GeroScience, 2021)
Osteosarcopenia is characterized by a progressive decline in muscle function and bone strength and associated with muscle fat accumulation. This study aimed to determine the effect of long-term high intensity resistance training (HIRT) on thigh muscle fat infiltration in older men with osteosarcopenia. Forty-three community-dwelling men (72 years and older) were randomly assigned to either an exercise group (EG, n = 21) or an inactive control group (CG, n = 22). EG participants performed a supervised single-set exercise training with high effort two times per week. Participants of both groups were individually provided with dietary protein to reach a cumulative intake of 1.5-1.6 g/kg/day or 1.2-1.3 g/kg/day (EG/CG), respectively, and Up to 10,000 IE/week of Vitamin-D were supplemented in participants with 25 OH Vitamin-D 3 levels below 100 nmol/l. Magnetic resonance (MR) imaging was performed to determine muscle and adipose tissue volume and fat fraction of the thigh. At baseline, there were no significant differences between the two groups. After 16 month,, there were significant training effects of 15% (p = 0.004) on intermuscular adipose tissue (IMAT) volume, which increased in the CG (p = 0.012) and was stable in the EG. In parallel, fat fraction within the deep fascia of the thigh (Baseline, EG: 18.2 vs CG: 15.5, p = 0.16) significantly differed between the groups (Changes, EG: 0.77% vs. CG: 7.7%, p = 0.009). The study confirms the role of fat infiltration of the muscles as an advanced imaging marker in osteosarcopenia and the favorable effects of HIRT on adipose tissue volume of the thigh, in men with osteosarcopenia.
CRIS-Team WoS Importer:2021-02-05

Effects of Active Spinal Orthosis on Fatty Infiltration in Paraspinal Muscles in Kyphotic Women with Osteoporotic Vertebral Fracture—Sub-Analysis of a Randomized Controlled Trial - Hiller, Marco; Kohl, Matthias; Chaudry, Oliver; Engelke, Klaus; von Stengel, Simon; Kemmler, Wolfgang (Healthcare, 2025)
Background/Objectives: Fatty infiltration of muscle is a predictor of degeneration. The present study determined the effect of an active spinal orthosis on muscle quality as determined by fatty infiltration in paraspinal muscles in older women with vertebral fractures and kyphosis. Methods: Twenty-one community-dwelling women ≥65 years with chronic back pain and vertebral fractures ≥3 months were randomly allocated to a group which wore the Spinomed active orthoses 2 × 2–3 h/d for 16 weeks (SOG: n = 11) or an untreated control group (CG: n = 10). Outcomes of the present study were parameters related to fatty infiltration of the musculi erector spinae and psoas major as determined by Magnetic Resonance Imaging (MRI). We applied a per protocol analysis; data were consistently adjusted for baseline values applying an ANCOVA. Results: Despite positive trends for all MRI parameters, no significant effects of the active spinal orthosis on fat infiltration of the musculus erector spinae were observed. Significant positive effects were, however, determined for musculus psoas major intra-fascial volume (p = 0.021; d’: 1.18) and muscle tissue volume (p = 0.001; d’: 1.80). No further significant effects on m. psoas major intra-fascial or muscle tissue average fat fraction or m. psoas major intramuscular adipose tissue volume were assessed. Of importance, no changes in variables that might have confounded the present result were reported. Conclusions: In line with recent exercise studies, the present high-volume, low-intensity back-strengthening intervention, induced by an active spinal orthosis, failed to generate significant effects on MRI measures of the m. erector spinae. On the other hand, significant effects on m. psoas major hypertrophy, albeit not fatty muscle infiltration, were determined. This new and unexpected finding should be confirmed by future studies.
CRIS-Team Scopus Importer:2025-06-20
Keywords: active orthosis; fat fraction; intermuscular adipose tissue; magnetic resonance imaging; muscle volume; postmenopausal women

Effects of High Intensity Dynamic Resistance Exercise and Whey Protein Supplements on Osteosarcopenia in Older Men with Low Bone and Muscle Mass. Final Results of the Randomized Controlled FrOST Study - Kemmler, Wolfgang; Kohl, Matthias; Jakob, Franz; Engelke, Klaus; von Stengel, Simon (Nutrients, 2020)
The present study aimed to evaluate the effect of high intensity dynamic resistance exercise (HIT-DRT) and whey protein supplementation (WPS) on bone mineral density (BMD) and sarcopenia parameters in osteosarcopenic men. Men ≥ 72 years with osteosarcopenia (n = 43) were randomly assigned to a HIT-RT (HIT-RT: n = 21) or a non-training control group (n = 22). Supervised HIT-RT twice/week was applied for 18 months, while the control group maintained their habitual lifestyle. Supplying WPS, total protein intake amounted to 1.5-1.6 (HIT-RT) and 1.2 g/kg/body mass/d (control). Both groups were supplied with calcium and vitamin D. Primary study outcomes were BMD and the sarcopenia Z-score. After adjusting for multiplicity, we observed significant positive effects for sarcopenia Z-score (standardized mean difference (SMD): 1.40), BMD at lumbar spine (SMD: 0.72) and total hip (SMD: 0.72). In detail, effect sizes for skeletal muscle mass changes were very pronounced (1.97, p < 0.001), while effects for functional sarcopenia parameters were moderate (0.87, p = 0.008; handgrip strength) or low (0.39, p = 0.209; gait velocity). Apart from one man who reported short periods of temporary worsening of existing joint pain, no HIT-RT/WPS-related adverse effects or injuries were reported. We consider HIT-RT supported by whey protein supplementation as a feasible, attractive, safe and highly effective option to fight osteosarcopenia in older men.
CRIS-Team Scopus Importer:2020-08-21
Keywords: bone mineral density; osteopenia; resistance exercise; sarcopenia

Effects of High-Intensity Resistance Training on Fitness and Fatness in Older Men With Osteosarcopenia - Kemmler, Wolfgang; Kohl, Matthias; Froehlich, Michael; Engelke, Klaus; von Stengel, Simon; Schöne, Daniel (Frontiers in Physiology, 2020)
To date, there has been no study on the long-term effects of resistance exercise on sarcopenia and obesity indices for people with sarcopenia. The present study thus aimed to determine the effect of 18 months of periodized, high-velocity/intensity/effort progressive resistance training (HIT-RT) on body composition and strength in older men with osteosarcopenia. Using a single-blind, two-group parallel design, 43 community-dwelling men, 72 years and older, with osteopenia and sarcopenia in Erlangen-Nürnberg, Germany, were randomly assigned to two study arms by drawing lots: (1) an exercise group that conducted a consistently supervised periodized high-velocity/intensity/effort protocol (HIT-RT; n = 21) on machines twice a week for 18 months or (2) a control group (CG; n = 22) that maintained their physical activity/exercise habits. Both groups were supplied with protein, cholecalciferol, and calcium according to current recommendations. The study outcomes were lean body mass (LBM), total and abdominal body fat as determined by dual-energy X-ray absorptiometry and maximum hip/leg extensor strength as assessed on an isokinetic leg press at baseline and after 8, 12, and 18 months of follow-up. The intention-to-treat principle and multiple imputation were applied to calculated study outcomes. After 18 months of HIT-RT, altogether five participants were lost to follow up (HIT-RT: n = 2, CG: n = 3). The attendance rates (95%) for HIT-RT were high; relevant adverse effects were not observed. Significant effects (i.e., differences between HIT-RT vs. CG) in favor of HIT-RT were determined for LBM (+1.73 kg, 95% CI: +1.13 to +2.32 kg), total body fat mass (−2.44 kg, 95% CI: −1.28 to 3.60 kg), abdominal body fat percentage (−2.68, 95% CI: −1.70 to −3.66), and maximum hip/leg extensor strength (+533 N, 95% CI: +397 to +670 N; all p < 0.001). Even after adjusting for multiple testing, all effects remained significant. Of note, after 8 months of HIT-RT, only slight (LBM and fat indices) to moderate (maximum strength) ongoing effects were observed. Carefully introduced, continuously supervised HIT-RT is an effective, attractive, feasible, and safe method to improve body composition and muscle strength in older community-dwelling men with sarcopenia. However, even when consequently applying principles of exercise intensity progression within the RT protocol, only slight further positive changes were observed after 8 months of exercise.
CRIS-Team Scopus Importer:2020-10-02
Keywords: body composition; exercise; older men; sarcopenia; strength

Effects of High-Intensity Resistance Training on Osteopenia and Sarcopenia Parameters in Older Men with Osteosarcopenia—One-Year Results of the Randomized Controlled Franconian Osteopenia and Sarcopenia Trial (FrOST) - Kemmler, Wolfgang; Kohl, Matthias; Froehlich, Michael; Jakob, Franz; Engelke, Klaus; von Stengel, Simon; Schöne, Daniel (Journal of Bone and Mineral Research, 2020)
Dynamic resistance exercise (DRT) might be the most promising agent for fighting sarcopenia in older people. However, the positive effect of DRT on osteopenia/osteoporosis in men has still to be confirmed. To evaluate the effect of low-volume/high-intensity (HIT)-DRT on bone mineral density (BMD) and skeletal muscle mass index (SMI) in men with osteosarcopenia, we initiated the Franconian Osteopenia and Sarcopenia Trial (FrOST). Forty-three sedentary community-dwelling older men (aged 73 to 91 years) with osteopenia/osteoporosis and SMI-based sarcopenia were randomly assigned to a HIT-RT exercise group (EG; n = 21) or a control group (CG; n = 22). HIT-RT provided a progressive, periodized single-set DRT on machines with high intensity, effort, and velocity twice a week, while CG maintained their lifestyle. Both groups were adequately supplemented with whey protein, vitamin D, and calcium. Primary study endpoint was integral lumbar spine (LS) BMD as determined by quantitative computed tomography. Core secondary study endpoint was SMI as determined by dual-energy X-ray absorptiometry. Additional study endpoints were BMD at the total hip and maximum isokinetic hip−/leg-extensor strength (leg press). After 12 months of exercise, LS-BMD was maintained in the EG and decreased significantly in the CG, resulting in significant between-group differences (p < 0.001; standardized mean difference [SMD] = 0.90). In parallel, SMI increased significantly in the EG and decreased significantly in the CG (p < 0.001; SMD = 1.95). Total hip BMD changes did not differ significantly between the groups (p = 0.064; SMD = 0.65), whereas changes in maximum hip−/leg-extensor strength were much more prominent (p < 0.001; SMD = 1.92) in the EG. Considering dropout (n = 2), attendance rate (95%), and unintended side effects/injuries (n = 0), we believe our HIT-RT protocol to be feasible, attractive, and safe. In summary, we conclude that our combined low-threshold HIT-RT/protein/vitamin D/calcium intervention was feasible, safe, and effective for tackling sarcopenia and osteopenia/osteoporosis in older men with osteosarcopenia. © 2020 American Society for Bone and Mineral Research. © 2020 American Society for Bone and Mineral Research.
CRIS-Team Scopus Importer:2020-05-12
Keywords: AGING; BONE QCT; EXERCISE; OSTEOPOROSIS; SARCOPENIA

Effects of High-Intensity Resistance Training on Visceral Adipose Tissue and Abdominal Aortic Calcifications in Older Men with Osteosarcopenia – Results from the FrOST Study - Knauer, Kira; Chaudry, Oliver; Uder, Michael; Kohl, Matthias; Kemmler, Wolfgang; Bickelhaupt, Sebastian; Engelke, Klaus (Clinical Interventions in Aging, 2023)
Purpose: To evaluate the effect of a high-intensity resistance training (HIT-RT) on visceral adipose tissue (VAT) and abdominal aortic calcifications (AAC). Patients and Methods: We conducted a post hoc analysis of the Franconian Osteopenia and Sarcopenia Trial (FrOST). 43 community-dwelling men with osteosarcopenia aged 72 years and older were randomly allocated to a supervised high-intensity resistance training (HIT-RT) twice weekly for 18 months (EG; n=21) and a non-training control group (CG; n=22). Non-contrast enhanced 2-point Dixon MRI scans covering mid L2 to mid L3 were acquired to measure VAT volume inside the abdominal cavity. Volume of AAC and hard plaques in renal arteries, truncus celiacus and superior mesenteric artery was measured by computed tomography (CT) scans covering mid T12 to mid L3. Intention-to-treat analysis with imputation for missing data was used to determine longitudinal changes in VAT and AAC volume. Correlations were used to determine associations between VAT and AAC. Results: Significant reduction of VAT volume in the EG (−7.7%; p<0.001) combined with no change in the CG (−1.3%; p=0.46) resulted in a significant 6.4% between group effect (p=0.022). We observed a significant increase of AAC volume in EG (+10.3%; p<0.001) and CG (12.0%; p<0.001). AAC differences between groups were not significant (p=0.57). In vascular outlets increases in volume of the hard plaques were observed in both groups, however, not all of them were significant. There was no significant correlation between changes in VAT and AAC volumes. Conclusion: The study confirmed a positive impact of HIT-RT on the metabolic and cardiovascular risk profile with respect to reduction of VAT volume. No positive exercise effect on AAC was observed. However, there was a further progression of AAC volume independent of group affiliation. Whether different exercise regimen may show a positive effect on AAC remains subject to further studies.
CRIS-Team Scopus Importer:2023-02-03
Keywords: AAC; HIT-RT; osteopenia; sarcopenia; VAT

Effects of high-intensity training on fatty infiltration in paraspinal muscles in elderly males with osteosarcopenia – the randomized controlled FrOST study - Kircher, Kaja; Chaudry, Oliver; Nagel, Armin Michael; Ghasemikaram, Mansour; Uder, Michael; Jakob, Franz; Kohl, Matthias; Kemmler, Wolfgang; Engelke, Klaus (BMC Geriatrics, 2024)
Background: Osteosarcopenia is a common geriatric syndrome with an increasing prevalence with age, leading to secondary diseases and complex consequences such as falls and fractures, as well as higher mortality and frailty rates. There is a great need for prevention and treatment strategies. Methods: In this analysis, we used magnetic resonance imaging (MRI) data from the randomised controlled FrOST trial, which enrolled community-dwelling osteosarcopenic men aged > 72 years randomly allocated to 16 months of twice-weekly high-intensity resistance training (HIRT) or a non-training control group. MR Dixon imaging was used to quantify the effects of HIRT on muscle fat infiltration in the paraspinal muscles, determined as changes in muscle tissue, fat faction and intermuscular adipose tissue (IMAT) in the erector spinae and psoas major muscles. Intention-to-treat analysis with multiple imputation was used to analyse the data set. Results: After 16 months of intervention, 15 men from the HIRT and 16 men from the CG were included in the MRI analysis. In summary, no positive effects on the fat infiltration of the erector spinae and psoas major muscles were observed. Conclusions: The previously reported positive effects on lumbar spine bone mineral density (BMD) suggest that mechanotransduction induces tropic effects on bone, but that fat infiltration of the erector spinae and psoas major muscles are either irreversible or, for some unknown reason, resistant to exercise. Because of the beneficial effects on spinal BMD, HIRT is still recommended in osteosarcopenic older men, but further research is needed to confirm appropriate age-specific training exercises for the paraspinal muscles. The potential of different MRI sequences to quantify degenerative and metabolic changes in various muscle groups must be better characterized. Trial registrations: FrOST was approved by the University Ethics Committee of the Friedrich-Alexander University of Erlangen-Nürnberg (number 67_15b and 4464b) and the Federal Office for Radiation Projection (BfS, number Z 5–2,246,212 – 2017–002). Furthermore, it fully complies with the Declaration of Helsinki and is registered at ClinicalTrials.gov: NCT03453463 (05/03/2018). JAMA 310:2191–2194, 2013.
CRIS-Team Scopus Importer:2024-02-23
Keywords: BMD; Dixon imaging; HIRT; IMAT; MRI; Osteosarcopenia

Effects of odanacatib on the radius and tibia of postmenopausal women: improvements in bone geometry, microarchitecture, and estimated bone strength - Cheung, Angela M.; Majumdar, Sharmila; Brixen, Kim; Chapurlat, Roland; Fuerst, Thomas; Engelke, Klaus; Dardzinski, Bernard; Cabal, Antonio; Verbruggen, Nadia; Ather, Shabana; Rosenberg, Elizabeth; De Papp, Anne E. (Journal of Bone and Mineral Research, 2014)
The cathepsin K inhibitor odanacatib (ODN), currently in phase 3 development for postmenopausal osteoporosis, has a novel mechanism of action that reduces bone resorption while maintaining bone formation. In phase 2 studies, odanacatib increased areal bone mineral density (aBMD) at the lumbar spine and total hip progressively over 5 years. To determine the effects of ODN on cortical and trabecular bone and estimate changes in bone strength, we conducted a randomized, double-blind, placebo-controlled trial, using both quantitative computed tomography (QCT) and high-resolution peripheral (HR-p)QCT. In previously published results, odanacatib was superior to placebo with respect to increases in trabecular volumetric BMD (vBMD) and estimated compressive strength at the spine, and integral and trabecular vBMD and estimated strength at the hip. Here, we report the results of HR-pQCT assessment. A total of 214 postmenopausal women (mean age 64.0 ± 6.8 years and baseline lumbar spine T-score -1.81 ± 0.83) were randomized to oral ODN 50 mg or placebo, weekly for 2 years. With ODN, significant increases from baseline in total vBMD occurred at the distal radius and tibia. Treatment differences from placebo were also significant (3.84% and 2.63% for radius and tibia, respectively). At both sites, significant differences from placebo were also found in trabecular vBMD, cortical vBMD, cortical thickness, cortical area, and strength (failure load) estimated using finite element analysis of HR-pQCT scans (treatment differences at radius and tibia = 2.64% and 2.66%). At the distal radius, odanacatib significantly improved trabecular thickness and bone volume/total volume (BV/TV) versus placebo. At a more proximal radial site, odanacatib attenuated the increase in cortical porosity found with placebo (treatment difference = -7.7%, p = 0.066). At the distal tibia, odanacatib significantly improved trabecular number, separation, and BV/TV versus placebo. Safety and tolerability were similar between treatment groups. In conclusion, odanacatib increased cortical and trabecular density, cortical thickness, aspects of trabecular microarchitecture, and estimated strength at the distal radius and distal tibia compared with placebo.
EVALuna2:10094

Effects of Romosozumab Compared With Teriparatide on Bone Density and Mass at the Spine and Hip in Postmenopausal Women With Low Bone Mass - Genant, Harry K.; Engelke, Klaus; Bolognese, Michael A.; Mautalen, Carlos; Brown, Jacques P.; Recknor, Chris; Goemaere, Stefan; Fuerst, Thomas; Yang, Yu-Ching; Grauer, Andreas; Libanati, Cesar (Journal of Bone and Mineral Research, 2017)
Romosozumab, a monoclonal antibody that binds sclerostin, has a dual effect on bone by increasing bone formation and reducing bone resorption, and thus has favorable effects in both aspects of bone volume regulation. In a phase 2 study, romosozumab increased areal BMD at the lumbar spine and total hip as measured by DXA compared with placebo, alendronate, and teriparatide in postmenopausal women with low bone mass. In additional analyses from this international, randomized study, we now describe the effect of romosozumab on lumbar spine and hip volumetric BMD (vBMD) and BMC at month 12 as assessed by QCT in the subset of participants receiving placebo, s.c. teriparatide (20 µg once daily), and s.c. romosozumab (210 mg once monthly). QCT measurements were performed at the lumbar spine (mean of L1and L2entire vertebral bodies, excluding posterior processes) and hip. One year of treatment with romosozumab significantly increased integral vBMD and BMC at the lumbar spine and total hip from baseline, and compared with placebo and teriparatide (all p < 0.05). Trabecular vertebral vBMD improved significantly and similarly from baseline (p < 0.05) with both romosozumab (18.3%) and teriparatide (20.1%), whereas cortical vertebral vBMD gains were larger with romosozumab compared with teriparatide (13.7% versus 5.7%, p < 0.0001). Trabecular hip vBMD gains were significantly larger with romosozumab than with teriparatide (10.8% versus 4.2%, p = 0.01), but were similar for cortical vBMD (1.1% versus -0.9%, p = 0.12). Cortical BMC gains were larger with romosozumab compared with teriparatide at both the spine (23.3% versus 10.9%, p < 0.0001) and hip (3.4% versus 0.0%, p = 0.03). These improvements are expected to result in strength gains and support the continued clinical investigation of romosozumab as a potential therapy to rapidly reduce fracture risk in ongoing phase 3 studies. © 2016 American Society for Bone and Mineral Research.
EVALuna2:33268

Effekte eines Ganzkörpervibrationstrainings auf Parameter des Frakturrisikos - von Stengel, Simon; Kemmler, Wolfgang; Mayer, Sabine; Engelke, Klaus; Klarner, Andreas; Kalender, Willi Alfred (Deutsche Medizinische Wochenschrift, 2009)

Effekte sportlichen Trainings auf gesundheitliche Risikofaktoren und Gesundheitskosten über 65jährigen Frauen - Kemmler, Wolfgang; von Stengel, Simon; Engelke, Klaus; Mayer, Sabine; Kalender, Willi Alfred (Deutsche Zeitschrift für Sportmedizin, 2009)

Einfluss körperlichen Trainings auf Risikofaktoren der Fraktur bei älteren Frauen - vorläufige Ergebnisse der Senioren Fitness und Präventionsstudie (SEFIP) - Kemmler, Wolfgang; von Stengel, Simon; Mayer, Sabine; Engelke, Klaus; Kalender, Willi Alfred (Osteologie, 2007)
UnivIS-Import:2015-04-14:Pub.2007.phil.dps.iss.psbg.einflu_7

Erste Ergebnisse der Erlanger Longitudinalen Vibrationsstudie (ELVIS) - von Stengel, Simon; Kemmler, Wolfgang; Mayer, Sabine; Engelke, Klaus; Kalender, Willi Alfred (Osteologie, 2007)
UnivIS-Import:2015-03-09:Pub.2007.phil.dps.iss.psbg.erstee

Evaluation of 2-point, 3-point, and 6-point Dixon magnetic resonance imaging with flexible echo timing for muscle fat quantification - Grimm, Alexandra; Meyer, Heiko; Nickel, Marcel D.; Nittka, Mathias; Raithel, Esther; Chaudry, Oliver; Friedberger, Andreas; Uder, Michael; Kemmler, Wolfgang; Quick, Harald H.; Engelke, Klaus (European Journal of Radiology, 2018)
The purpose of this study is to evaluate and compare 2-point (2pt), 3-point (3pt), and 6-point (6pt) Dixon magnetic resonance imaging (MRI) sequences with flexible echo times (TE) to measure proton density fat fraction (PDFF) within muscles. Two subject groups were recruited (G1: 23 young and healthy men, 31 ± 6 years; G2: 50 elderly men, sarcopenic, 77 ± 5 years). A 3-T MRI system was used to perform Dixon imaging on the left thigh. PDFF was measured with six Dixon prototype sequences: 2pt, 3pt, and 6pt sequences once with optimal TEs (in- and opposed-phase echo times), lower resolution, and higher bandwidth (optTE sequences) and once with higher image resolution (highRes sequences) and shortest possible TE, respectively. Intra-fascia PDFF content was determined. To evaluate the comparability among the sequences, Bland-Altman analysis was performed. The highRes 6pt Dixon sequences served as reference as a high correlation of this sequence to magnetic resonance spectroscopy has been shown before. The PDFF difference between the highRes 6pt Dixon sequence and the optTE 6pt, both 3pt, and the optTE 2pt was low (between 2.2% and 4.4%), however, not to the highRes 2pt Dixon sequence (33%). For the optTE sequences, difference decreased with the number of echoes used. In conclusion, for Dixon sequences with more than two echoes, the fat fraction measurement was reliable with arbitrary echo times, while for 2pt Dixon sequences, it was reliable with dedicated in- and opposed-phase echo timing.
EVALuna2:34695

Evolution of an Acute COVID-19 Pulmonary Infection - Necker, Fabian; Petkov, Kaloian; Engelke, Klaus; Scholz, Michael (Radiology, 2024)
CRIS-Team Scopus Importer:2024-03-01

Executive Summary of the 2015 ISCD Position Development Conference on Advanced Measures From DXA and QCT: Fracture Prediction Beyond BMD - Shepherd, John A.; Schousboe, John T.; Broy, Susan B.; Engelke, Klaus; Leslie, William D. (Journal of Clinical Densitometry, 2015)
There have been many scientific advances in fracture risk prediction beyond bone density. The International Society for Clinical Densitometry (ISCD) convened a Position Development Conference (PDC) on the use of dual-energy X-ray absorptiometry beyond measurement of bone mineral density for fracture risk assessment, including trabecular bone score and hip geometry measures. Previously, no guidelines for nonbone mineral density DXA measures existed. Furthermore, there have been advances in the analysis of quantitative computed tomography (QCT) including finite element analysis, QCT of the hip, DXA-equivalent hip measurements, and opportunistic screening that were not included in the previous ISCD positions. The topics and questions for consideration were developed by the ISCD Board of Directors and the Scientific Advisory Committee and were designed to address the needs of clinical practitioners. Three task forces were created and asked to conduct comprehensive literature reviews to address specific questions. The task forces included participants from many countries and a variety of interests including academic institutions and private health care delivery organizations. Representatives from industry participated as consultants to the task forces. Task force reports with proposed position statements were then presented to an international panel of experts with backgrounds in bone densitometry. The PDC was held in Chicago, Illinois, USA, contemporaneously with the Annual Meeting of the ISCD, February 26 through February 28, 2015. This Executive Summary describes the methodology of the 2015 PDC on advanced measures from DXA and QCT and summarizes the approved official positions. Six separate articles in this issue will detail the rationale, discussion, and additional research topics for each question the task forces addressed.
EVALuna2:10113

Exercise, Body Composition, and Functional Ability. A Randomized Controlled Trial - Kemmler, Wolfgang; von Stengel, Simon; Engelke, Klaus; Häberle, Lothar; Mayhew, Jerry; Kalender, Willi Alfred (American Journal of Preventive Medicine, 2010)
Context In women, age and the menopausal transition contribute to an increase of body fat and a reduction of lean body mass associated with functional decline, affecting independent living. Background Sarcopenia and adiposity in the elderly has been associated with increased mortality and functional decline affecting independent living. Purpose This study was conducted to determine the effect of a multipurpose exercise program on the body composition and functional ability of elderly women living in a community. Design An 18-month single-blinded RCT comparing participants in an exercise program with an active control group was conducted from May 2005 through December 2007. Analyses were conducted from January 2008 to July 2008. Setting/participants Two hundred forty-six women (aged 69.1±4.0 years) living independently in the area of Erlangen–Nürnberg (Germany) participated in the study. Intervention Subjects (n=123) performed a multipurpose exercise program with special emphasis on exercise intensity but with low-level requirements for training facilities and materials. The 123 women in the control group focused primarily on well-being. Main outcome measures Body composition was assessed by dual-energy x-ray absorptiometry. Further, strength was evaluated using isometric techniques for the back and legs. Aerobic fitness was determined from a progressive-intensity treadmill test. Results After 18 months, significant effects in favor of the exercise program for body composition were increases in appendicular skeletal muscle mass and lean body mass along with reductions in abdominal fat and total body fat. Significant performance effects also favored the exercise program and included enhanced isometric maximum trunk-extensor and leg press strength, leg press power, timed up-and-go test, and aerobic fitness. Conclusions A high-intensity multipurpose exercise program produced significant improvements in body composition and functional ability in a cohort of elderly women living in a community.

Exercise effects on fall risk and bone integrity. Preliminary results of the Senior Fitness and Prevention Study (SEFIP) - Kemmler, Wolfgang; von Stengel, Simon; Bebenek, Michael; Mayer, Sabine; Engelke, Klaus; Kalender, Willi Alfred; Mayhew, Jerry (Medicine and science in sports and exercise, 2008)
UnivIS-Import:2015-04-14:Pub.2008.phil.dps.iss.psbg.exerci

Feasibility of Dixon magnetic resonance imaging to quantify effects of physical training on muscle composition-A pilot study in young and healthy men - Grimm, Alexandra; Nickel, Marcel D.; Chaudry, Oliver; Uder, Michael; Jakob, Franz; Kemmler, Wolfgang; Quick, Harald H.; Engelke, Klaus (European Journal of Radiology, 2019)
Changes in muscle-fat-composition affect physical performance and muscular function, like strength and power. The purpose of the present study was to investigate whether changes in soft tissue composition of the thigh and changes in muscle size and composition resulting from physical training were detectable with Dixon magnetic resonance imaging (MRI).
CRIS-Team WoS Importer:2019-05-03

Femoral and vertebral strength improvements in postmenopausal women with osteoporosis treated with denosumab - Keaveny, Tony M.; Mcclung, Michael R.; Genant, Harry K.; Zanchetta, Jose R.; Kendler, David; Brown, Jacques P.; Goemaere, Stefan; Recknor, Chris; Brandi, Maria L.; Eastell, Richard; Kopperdahl, David L.; Engelke, Klaus; et al. (Journal of Bone and Mineral Research, 2014)
In the randomized, placebo-controlled FREEDOM study of women aged 60 to 90 years with postmenopausal osteoporosis, treatment with denosumab once every 6 months for 36 months significantly reduced hip and new vertebral fracture risk by 40% and 68%, respectively. To gain further insight into this efficacy, we performed a nonlinear finite element analysis (FEA) of hip and spine quantitative computed tomography (QCT) scans to estimate hip and spine strength in a subset of FREEDOM subjects (n = 48 placebo; n = 51 denosumab) at baseline, 12, 24, and 36 months. We found that, compared with baseline, the finite element estimates of hip strength increased from 12 months (5.3%; p < 0.0001) and through 36 months (8.6%; p < 0.0001) in the denosumab group. For the placebo group, hip strength did not change at 12 months and decreased at 36 months (-5.6%; p < 0.0001). Similar changes were observed at the spine: strength increased by 18.2% at 36 months for the denosumab group (p < 0.0001) and decreased by -4.2% for the placebo group (p = 0.002). At 36 months, hip and spine strength increased for the denosumab group compared with the placebo group by 14.3% (p < 0.0001) and 22.4% (p < 0.0001), respectively. Further analysis of the finite element models indicated that strength associated with the trabecular bone was lost at the hip and spine in the placebo group, whereas strength associated with both the trabecular and cortical bone improved in the denosumab group. In conclusion, treatment with denosumab increased hip and spine strength as estimated by FEA of QCT scans compared with both baseline and placebo owing to positive treatment effects in both the trabecular and cortical bone compartments. These findings provide insight into the mechanism by which denosumab reduces fracture risk for postmenopausal women with osteoporosis.
EVALuna2:10068

Focal bone defects in type 2 diabetes mellitus patients with acute hip fractures - Yuan, Yi; Zhang, Rui; Yang, Minghui; Xia, Wei; Su, Yongbin; Jian, Junming; Liu, Yandong; Guo, Zhe; Zhao, Xingyu; Zhu, Shiwen; Cheng, Xiaoguang; Wu, Xinbao; et al. (Quantitative Imaging in Medicine and Surgery, 2025)
Background: Osteoporotic hip fractures are associated with low bone strength, which is usually explained by low bone mineral density (BMD). However, even though type 2 diabetes mellitus (T2DM) participants have an increased incidence of osteoporotic hip fractures, paradoxically, there is increasing evidence indicating that T2DM patients have higher BMD than those without T2DM. The detection of focal osteoporosis could help us understand the bone quality of the proximal femur in participants with and without T2DM. This study aims to investigate whether focal bone defects are associated with hip fracture in those with and without T2DM by using statistical atlases. Methods: Four hundred and nineteen low-energy acute hip fracture cases and 288 controls with hip computed tomography (CT) scans were included in the case-control study. Differences in the spatial distributions of volumetric bone mineral density (vBMD), cortical bone thickness, cortical vBMD, and vBMD in a layer adjacent to the endosteal surface were investigated using voxel-based morphometry (VBM) and surface-based statistical parametric mapping (SPM). Results: For both with and without T2DM groups, there is a clear bone defect at the femoral neck and intertrochanteric region in cortical thickness variables for cases. The endocortical trabecular bone mineral density (ECTD) and vBMD distributions show quite dramatic differences between fractures and controls in both with and without T2DM groups. In particular, in the women’s comparison results, the significantly different region between cases and controls in the T2DM cohort was larger than that in the without T2DM cohort. After adjustment for the covariates of age, height, and weight, the risk of hip fracture among people with diabetes was higher overall than among participants without diabetes, in both men and women. The spatial distribution of trabecular vBMD and focal areas of endocortical bone defect both result in an increased risk of hip fracture in T2DM patients. Conclusions: The spatial distribution of trabecular vBMD and focal areas of endocortical bone defect both result in increased risk of hip fracture in T2DM patients.
CRIS-Team Scopus Importer:2025-10-17
Keywords: Acute hip fracture; bone mineral density (BMD); statistical parametric mapping (SPM); type 2 diabetes mellitus (T2DM); voxel-based morphometry (VBM)

Greater Gains in Spine and Hip Strength for Romosozumab Compared With Teriparatide in Postmenopausal Women With Low Bone Mass - Keaveny, Tony M.; Crittenden, Daria B.; Bolognese, Michael A.; Genant, Harry K.; Engelke, Klaus; Oliveri, Beatriz; Brown, Jacques P.; Langdahl, Bente L.; Yan, Chris; Grauer, Andreas; Libanati, Cesar (Journal of Bone and Mineral Research, 2017)
Romosozumab is a monoclonal antibody that inhibits sclerostin and has been shown to reduce the risk of fractures within 12 months. In a phase II, randomized, placebo-controlled clinical trial of treatment-naïve postmenopausal women with low bone mass, romosozumab increased bone mineral density (BMD) at the hip and spine by the dual effect of increasing bone formation and decreasing bone resorption. In a substudy of that trial, which included placebo and teriparatide arms, here we investigated whether those observed increases in BMD also resulted in improvements in estimated strength, as assessed by finite element analysis. Participants received blinded romosozumab s.c. (210 mg monthly) or placebo, or open-label teriparatide (20 μg daily) for 12 months. CT scans, obtained at the lumbar spine (n = 82) and proximal femur (n = 46) at baseline and month 12, were analyzed with finite element software (VirtuOst, O.N. Diagnostics) to estimate strength for a simulated compression overload for the spine (L1vertebral body) and a sideways fall for the proximal femur, all blinded to treatment assignment. We found that, at month 12, vertebral strength increased more for romosozumab compared with both teriparatide (27.3% versus 18.5%; p = 0.005) and placebo (27.3% versus -3.9%; p < 0.0001); changes in femoral strength for romosozumab showed similar but smaller changes, increasing more with romosozumab versus teriparatide (3.6% versus -0.7%; p = 0.027), and trending higher versus placebo (3.6% versus -0.1%; p = 0.059). Compartmental analysis revealed that the bone-strengthening effects for romosozumab were associated with positive contributions from both the cortical and trabecular bone compartments at both the lumbar spine and hip. Taken together, these findings suggest that romosozumab may offer patients with osteoporosis a new bone-forming therapeutic option that increases both vertebral and femoral strength within 12 months. © 2017 American Society for Bone and Mineral Research.
EVALuna2:33269

Guidelines for the assessment of bone density and microarchitecture in vivo using high-resolution peripheral quantitative computed tomography - Whittier, D. E.; Boyd, S. K.; Burghardt, A. J.; Paccou, J.; Ghasem-Zadeh, A.; Chapurlat, R.; Engelke, Klaus; Bouxsein, M. L. (Osteoporosis international, 2020)
Introduction: The application of high-resolution peripheral quantitative computed tomography (HR-pQCT) to assess bone microarchitecture has grown rapidly since its introduction in 2005. As the use of HR-pQCT for clinical research continues to grow, there is an urgent need to form a consensus on imaging and analysis methodologies so that studies can be appropriately compared. In addition, with the recent introduction of the second-generation HrpQCT, which differs from the first-generation HR-pQCT in scan region, resolution, and morphological measurement techniques, there is a need for guidelines on appropriate reporting of results and considerations as the field adopts newer systems. Methods: A joint working group between the International Osteoporosis Foundation, American Society of Bone and Mineral Research, and European Calcified Tissue Society convened in person and by teleconference over several years to produce the guidelines and recommendations presented in this document. Results: An overview and discussion is provided for (1) standardized protocol for imaging distal radius and tibia sites using HR-pQCT, with the importance of quality control and operator training discussed; (2) standardized terminology and recommendations on reporting results; (3) factors influencing accuracy and precision error, with considerations for longitudinal and multi-center study designs; and finally (4) comparison between scanner generations and other high-resolution CT systems. Conclusion: This article addresses the need for standardization of HR-pQCT imaging techniques and terminology, provides guidance on interpretation and reporting of results, and discusses unresolved issues in the field.
CRIS-Team Scopus Importer:2020-06-05
Keywords: Bone microarchitecture; Guidelines; High-resolution peripheral quantitative computed tomography; Imaging protocol

Heterogenous bone response to biologic DMARD therapies in rheumatoid arthritis patients and their relationship to functional indices - Brunet, S. C.; Tse, J. J.; Kuczynski, M. T.; Engelke, Klaus; Boyd, S. K.; Barnabe, C.; Manske, S. L. (Scandinavian Journal of Rheumatology, 2021)
Objectives: Previous studies of high-resolution peripheral quantitative computed tomography (HR-pQCT) imaging of hand joints in patients with rheumatoid arthritis (RA) have suggested that erosion healing may occur. Our objective was to examine changes in erosion volume, joint space width (JSW), bone mineral density (BMD), and bone remodelling, and their association with clinical outcomes and measures of patient hand function. Method: We examined 48 patients who achieved a good response to a newly initiated biologic therapy. HR-pQCT images of the dominant hands’ second and third metacarpophalangeal joints were obtained 3 and 12 months after therapy initiation. Bone erosion volume, JSW, BMD, and bone remodelling were quantified from HR-pQCT images, with improvement, no change (unchanged), or progression in these measures determined by least significant change. Disease activity and hand function measures were collected. Results: There were no significant group changes in HR-pQCT outcomes over the 9 month period. Twenty-two patients had total erosion volumes that remained unchanged, nine showed improvement, and two progressed. The majority of JSW and BMD measures remained unchanged. There was a significant association between the baseline Health Assessment Questionnaire score and the change in minimum JSW, but no other significant associations between HR-pQCT outcomes and function were observed. Conclusions: The vast majority of patients maintained unchanged JSW and BMD over the course of follow-up. Significant improvements in total erosion volume occurred in 27% of patients, suggesting that biologic therapies may lead to erosion healing in some patients, although this did not have an impact on self-reported and demonstrated hand function.
CRIS-Team Scopus Importer:2021-04-09

Hyperglycemia Is Not Associated With Higher Volumetric BMD in a Chinese Health Check-up Cohort - Wang, Ling; Zhao, Kaiping; Zha, Xiaojuan; Ran, Limei; Su, Heng; Yang, Yingying; Shuang, Qing; Liu, Yandong; Xu, Li; Blake, Glen M.; Cheng, Xiaoguang; Engelke, Klaus; et al. (Frontiers in Endocrinology, 2022)
Background and Purpose: Type 2 diabetes mellitus patients have an increased fracture risk despite having higher areal bone mineral density (aBMD) measured by DXA. This apparent paradox might be explained by the overestimation of BMD by DXA due to the higher fat mass in type 2 diabetes mellitus patients. Volumetric BMD (vBMD) as assessed by quantitative CT (QCT) is not influenced by fat mass. We assessed the association of vBMD and fasting plasma glucose in a large cohort of Chinese subjects and compared the vBMD in healthy and diabetic subjects. In addition, we compared the relation between aBMD, vBMD, glucose and fat mass in a subset of this cohort. Materials and Methods: 10309 participants from the China Biobank project underwent QCT based on chest low dose CT to compute vBMD of L1 and L2 vertebrae and FPG measurements between 2018 and 2019. Among them, 1037 subjects also had spine DXA scans. Data was analyzed using linear regression models. Results: In the total cohort (5889 men and 4420 women, mean age 53 years, range 30-96), there was no significant association between vBMD and FPG after adjustment for age (women: p=0.774; men: p=0.149). 291 women and 606 men fitted the diagnostic criteria of diabetes. Both women and men with diabetes had lower vBMD compared to non-diabetic subjects, but this became non-significant after adjusting for age in the total cohort (women: p=0.817; men: p=0.288) and after propensity score matching based on age (women: p=0.678; men: p=0.135). In the DXA subcohort, aBMD was significantly higher in men with diabetes after adjusting for age and this difference disappeared after further adjusting for total fat area (p=0.064). Conclusion: We did not find any effect of fasting plasma glucose or diabetes on the volumetric BMD measured with QCT after adjustment for age. Therefore, vBMD measured with QCT might be a more reliable measurement to diagnose osteoporosis and assess fracture risk than aBMD measured with DXA in diabetic patients.
CRIS-Team Scopus Importer:2022-01-28
Keywords: areal bone mineral density (aBMD); fasting plasma glucose (FPG); osteoporosis; type 2 diabetes; volumetric bone mineral density (vBMD)

Impact of intravenous CT contrast agents on internal calibration techniques to determine trabecular BMD of the lumbar spine - Bartenschlager, Stefan; Cavallaro, Alexander Josef; Pogarell, Tobias; Uder, Michael; Chaudry, Oliver; Schett, Georg; Engelke, Klaus (European Journal of Radiology, 2025)
Objectives: Contrast agents are frequently administered in computed tomography (CT) scans used for opportunistic screening of osteoporosis. The objective of this study is to compare the impact of contrast-related bone mineral density (BMD) increase between phantom-based and internal CT calibration techniques. Materials and Methods: Phantom-based and internal CT calibration techniques were used to determine trabecular BMD in 93 existing clinical CT scans of the lumbar spine of 34 subjects, scanned before and after administration of contrast agents. BMD differences between native (Nat) and contrast-enhanced scans in arterial (Art) and portal venous (PV) phases were compared among calibration methods. Three pairs of internal reference materials were investigated: blood/air, subcutaneous adipose tissue (SAT)/air and muscle tissue/air. Results: Contrast agents increased CT values of blood in the aorta and the inferior vena cava in the Art phase by 210 ± 99HU and 47 ± 35HU, respectively and in the PV phase by 110 ± 49HU and 73 ± 28HU, respectively. Effects on CT values of muscle and SAT were < 5HU in the Art phase and < 10HU in the PV phase. BMD obtained with phantom calibration increased significantly (p < 0.01) in Art and PV phases by 8.6 ± 14.7 mg/cm3 and 14.4 ± 16.3 mg/cm3, respectively. If SAT/air or muscle/air were used as internal reference materials, increases in internally calibrated BMD (<12 mg/cm3 in AT phase and < 17 mg/cm3 in PV phase) did not significantly differ (p > 0.1 for Art and PV phases) from increases of phantom-calibrated BMD. Conclusions: Although CT values of internal reference materials increased following the administration of contrast, internal calibration was unable to mitigate the contrast-related BMD increases observed in phantom-based calibration.
CRIS-Team Scopus Importer:2025-01-31
Keywords: Computed tomography; Contrast agents; Internal BMD calibration; Lumbar spine; Osteoporosis; Opportunistic screening

Impact of meniscal coverage on subchondral bone mineral density of the proximal tibia in female subjects – A cross-sectional in vivo study using QCT - Sannmann, Frederike; Laredo, Jean Denis; Chappard, Christine; Engelke, Klaus (Bone, 2020)
Objective: To verify earlier data in cadavers that in female subjects with OA meniscal coverage is associated with lowered bone mineral density of the underlying subchondral bone in the proximal tibia by investigating the local bone mineral density (BMD) distribution within the epiphysis. Methods: BMD of the subchondral bone of the tibia was measured by QCT in 67 elderly females diagnosed with OA (Kellgren-Lawrence grades 2–3). The epiphysis was subdivided along the axis of the tibia into a subchondral-epiphyseal VOI covering the first 5-6 mm below the subchondral bone plate, a mid-epiphyseal VOI covering the adjacent 7–8 and a juxtaphyseal VOI of another 7-8 mm that bordered the growth plate. These VIOs were further divided into lateral and medial and then into anterior, mid and posterior sub-VOIs. Finally, all subVOIs were divided in one subVOI covered by the menisci (CM) and another not covered by the menisci (nCM). BMD ratios of these two subVOIs were compared. Results: In the subchondral epiphysis BMD was significantly lower (Medial: mean BMDdiff = 125 mg/cm3, p<0.001; Lateral: mean BMDdiff = 56 mg/cm3p < 0.001) in subVOIs covered by the meniscus compared to subVOIs not covered by the meniscus. The BMD difference was no longer significant in the mid epiphysis (Medial: mean BMDdiff = 10 mg/cm3, p>0.82; Lateral: mean BMDdiff = 7 mg/cm3, p=0.99) and was reversed in the juxtaphysis. With a few exceptions these BMD differences were independent of the lateral-medial and the anterior-mid-posterior position. BMD significantly (p<0.05) decreased with age independent on whether the location was covered or uncovered by the meniscus, however the BMD ratio of the corresponding nCM and CM subVOIs did not significantly (p>0.1) change with age. Conclusion: In-vivo QCT measurements of the BMD distribution in the proximal tibia indicate a protective effect of the menisci in the subchondral bone close to the joint. This protective effect is age independent despite the overall age-related decrease of BMD.
CRIS-Team Scopus Importer:2020-03-10
Keywords: BMD; Knee; Meniscus; Osteoarthritis; QCT; Subchondral bone; Tibia

Impact of reference point selection on DXA-based measurement of forearm bone mineral density - Yu, Wei; Ying, Qifeng; Guan, Wenmin; Lin, Qiang; Zhang, Zaizhu; Chen, Jianfeng; Engelke, Klaus; Hsieh, Evelyn (Archives of Osteoporosis, 2019)
Summary: Few studies have systematically evaluated the technical aspects of forearm bone mineral density (BMD) measurement. We found that BMD remained stable regardless of the reference point; however, the ROI identified was not always consistent. Our study highlights the importance of using the same reference point for serial measurements of forearm BMD. Background: Forearm fractures are clinically important outcomes from the perspective of morbidity, health care costs, and interruption of work. BMD of the forearm, as derived by dual-energy x-ray absorptiometry (DXA), is a better predictor of fracture at the forearm compared with BMD measured at other sites. However, very few studies have evaluated the technical aspects of selecting the ROI for forearm BMD measurement. This study aimed to compare the BMD values measured at the 1/3 radius site using three different reference points: the ulnar styloid process, the radial endplate, and the bifurcation of the ulna and radius. Methodology: Healthy Chinese patients participating in the control group of an ongoing study at Zhejiang Provincial People’s Hospital were recruited for this study. For each patient, a DXA scan (GE Lunar Prodigy) of the forearm was performed and BMD values were separately calculated using each of the three reference points to identify the ROI. Pearson correlation coefficients were calculated to examine the correlation between the BMD measures derived from each reference point. The F test and independent t test were applied for more robust analysis of the differences in the variances and means. Results: Sixty-eight healthy Chinese volunteers agreed to participate in this study. The root mean square standard deviation (RMS-SD) percentages of BMD values measured at the 1/3 radius site were 2.19%, 2.23%, and 2.20% when using the ulnar styloid process, radial endplate, and the bifurcation of the ulna and radius as the reference points, respectively. Pearson’s correlation coefficients for all pairwise comparisons among these three groups were greater than 0.99. F tests and independent t tests showed p values ranging from 0.92 to 0.99. However, we observed that among 10% of patients, choosing an ROI at the ulnar styloid process led to an inability to accurately determine the BMD at the ultra-distal radius. Conclusions: Given equal ability to determine BMD at the 1/3 radius accurately, the radial endplate or the bifurcation of the ulna and radius should be preferentially selected as the reference point for routine forearm BMD measurements in order to avoid situations in which the ultra-distal radius BMD cannot be determined.
CRIS-Team Scopus Importer:2019-11-19
Keywords: Bone mineral density; Dual-energy X-ray absorptiometry; Forearm; One-third radius; Precision; Regions of interest

Impact of whole-body electromyostimulation on body composition in elderly women at risk for sarcopenia: the Training and ElectroStimulation Trial (TEST-III) - Kemmler, Wolfgang; Bebenek, Michael; Engelke, Klaus; von Stengel, Simon (Age, 2014)
Most studies have confirmed the positive impact of resistance training on muscle mass and functional capacity in aging adults. However, due to physical limitation or a simple aversion against regular exercise, the majority of elderly subjects do not reach the exercise doses recommended for impacting strength or muscle mass. This led us to evaluate the effect of whole-body electromyostimulation (WB-EMS), a novel, time-efficient and smooth training technology, on body composition with special regard to sarcopenia. Seventy-six lean, non-sportive women (75 ± 4 years) were randomly assigned to either a WB-EMS group (WB-EMS, n = 38) that performed 18 min of WB-EMS (bipolar, 85 Hz) 3 sessions in 14 days (1.5 sessions/week) or a semi-active control group (aCG, n = 38). Body composition was assessed by dual-energy X-ray absorptiometry and maximum strength was evaluated using isometric techniques for trunk and legs. After 54 weeks of intervention, significant inter-group differences were determined for appendicular skeletal muscle mass (WB-EMS, 0.4 ± 2.2 % vs. aCG, -1.5 ± 3.1 %; p = 0.009), lean body mass (WB-EMS, 0.8 ± 1.8 % vs. aCG, -0.8 ± 2.7 %; p = 0.008) and maximum isometric strength (leg extensors, 9.8 ± 12.9 % vs. 0.2 ± 10.4 %; p = 0.003; trunk extensors, 10.1 ± 12.7 vs. -1.6 ± 8.6 %; p = 0.001). Although borderline significant for abdominal fat mass (WB-EMS, -2.9 ± 8.3 vs. aCG, 1.5 ± 10.7 %; p = 0.069), differences did not reach statistically significant levels for body fat parameters. Considering the clinical effectiveness for impacting sarcopenia and the good acceptance of this technology by this non-sportive cohort of elderly women, we conclude that for elderly subjects unable or unwilling to perform dynamic strength exercises, electromyostimulation may be a less off-putting alternative to maintain lean body mass and strength.
EVALuna2:10049

Impact of whole body electromyostimulation on cardiometabolic risk factors in older women with sarcopenic obesity: the randomized controlled FORMOsA-sarcopenic obesity study - Wittmann, Katharina; Sieber, Cornel; von Stengel, Simon; Kohl, Matthias; Freiberger, Ellen; Jakob, Franz; Lell, Michael; Engelke, Klaus; Kemmler, Wolfgang (Clinical Interventions in Aging, 2016)
Sarcopenic obesity (SO) is characterized by a combination of low muscle and high fat mass with an additive negative effect of both conditions on cardiometabolic risk. The aim of the study was to determine the effect of whole-body electromyostimulation (WB-EMS) on the metabolic syndrome (MetS) in community-dwelling women aged >=70 years with SO.The study was conducted in an ambulatory university setting. Seventy-five community-dwelling women aged >=70 years with SO living in Northern Bavaria, Germany, were randomly allocated to either 6 months of WB-EMS application with (WB-EMS&P) or without (WB-EMS) dietary supplementation (150 kcal/day, 56% protein) or a non-training control group (CG). WB-EMS included one session of 20 min (85 Hz, 350 ?s, 4 s of strain-4 s of rest) per week with moderate-to-high intensity. The primary study endpoint was the MetS Z-score with the components waist circumference (WC), mean arterial pressure (MAP), triglycerides, fasting plasma glucose, and high-density lipoprotein cholesterol (HDL-C); secondary study endpoints were changes in these determining variables.MetS Z-score decreased in both groups; however, changes compared with the CG were significant (P=0.001) in the WB-EMS&P group only. On analyzing the components of the MetS, significant positive effects for both WB-EMS groups (P<=0.038) were identified for MAP, while the WB-EMS group significantly differed for WC (P=0.036), and the WB-EMS&P group significantly differed for HDL-C (P=0.006) from the CG. No significant differences were observed between the WB-EMS groups.The study clearly confirms the favorable effect of WB-EMS application on the MetS in community-dwelling women aged >=70 years with SO. However, protein-enriched supplements did not increase effects of WB-EMS alone. In summary, we considered this novel technology an effective and safe method to prevent cardiometabolic risk factors and diseases in older women unable or unwilling to exercise conventionally.
EVALuna2:14654

Inactivation of autophagy ameliorates glucocorticoid-induced and ovariectomy-induced bone loss - Lin, Neng-Yu; Chen, Chih-Wei; Kagwiria, Rosebeth; Liang, Ruifang; Beyer, Christian; Distler, Alfiya; Luther, Julia; Engelke, Klaus; Schett, Georg; Distler, Jörg (Annals of the Rheumatic Diseases, 2016)
Autophagy has recently been shown to regulate osteoclast activity and osteoclast differentiation. Here, we aim to investigate the impact of autophagy inhibition as a potential therapeutic approach for the treatment of osteoporosis in preclinical models.Systemic bone loss was induced in mice by glucocorticoids and by ovariectomy (OVX). Autophagy was targeted by conditional inactivation of autophagy-related gene 7 (Atg7) and by treatment with chloroquine (CQ). Bone density was evaluated by microCT. The role of autophagy on osteoclastogenesis was analysed by osteoclastogenesis and bone resorption assays. The quantification of receptor activator of nuclear factor ? B ligand and osteoprotegerin proteins in cocultures was performed using ELISA whereas that of osteoclast and osteoblast differentiation markers was by qPCR.Selective deletion of Atg7 in monocytes from Atg7(fl/fl)_x_LysM-Cre mice mitigated glucocorticoid-induced and OVX-induced osteoclast differentiation and bone loss compared with Atg7(fl/fl) littermates. Pharmacological inhibition of autophagy by treatment with CQ suppressed glucocorticoid-induced osteoclastogenesis and protected mice from bone loss. Similarly, inactivation of autophagy shielded mice from OVX-induced bone loss. Inhibition of autophagy led to decreased osteoclast differentiation with lower expression of osteoclast markers such as NFATc1, tartrate-resistant acid phosphatase, OSCAR and cathepsin K and attenuated bone resorption in vitro. In contrast, osteoblast differentiation was not affected by inhibition of autophagy.Pharmacological or genetic inactivation of autophagy ameliorated glucocorticoid-induced and OVX-induced bone loss by inhibiting osteoclastogenesis. These findings may have direct translational implications for the treatment of osteoporosis, since inhibitors of autophagy such as CQ are already in clinical use.
EVALuna2:10103

Increased bone density and resistance to ovariectomy-induced bone loss in FoxP3-transgenic mice based on impaired osteoclast differentiation. - Zaiss, Mario; Sarter, Kerstin; Heß, Andreas; Engelke, Klaus; Boehm, Christina; Nimmerjahn, Falk; Voll, Reinhard; Schett, Georg; David, Jean-Pierre (Arthritis and Rheumatism, 2010)
OBJECTIVE Immune activation triggers bone loss. Activated T cells are the cellular link between immune activation and bone destruction. The aim of this study was to determine whether immune regulatory mechanisms, such as naturally occurring Treg cells, also extend their protective effects to bone homeostasis in vivo. METHODS Bone parameters in FoxP3-transgenic (Tg) mice were compared with those in their wild-type (WT) littermate controls. Ovariectomy was performed in FoxP3-Tg mice as a model of postmenopausal osteoporosis, and the bone parameters were analyzed. The bones of RAG-1(-/-) mice were analyzed following the adoptive transfer of isolated CD4+CD25+ T cells. CD4+CD25+ T cells and CD4+ T cells isolated from FoxP3-Tg mice and WT mice were cocultured with monocytes to determine their ability to suppress osteoclastogenesis in vitro. RESULTS FoxP3-Tg mice developed higher bone mass and were protected from ovariectomy-induced bone loss. The increase in bone mass was found to be the result of impaired osteoclast differentiation and bone resorption in vivo. Bone formation was not affected. Adoptive transfer of CD4+CD25+ T cells into T cell-deficient RAG-1(-/-) mice also increased the bone mass, indicating that Treg cells directly affect bone homeostasis without the need to engage other T cell lineages. CONCLUSION These data demonstrate that Treg cells can control bone resorption in vivo and can preserve bone mass during physiologic and pathologic bone remodeling.

INCREASE OF CORTICAL MICRO-CHANNELS (COMICS) AS A NEW FEATURE OF STRUCTURAL DAMAGE IN PAIENTS WITH RHEUMATOID ARTHRITIS - Werner, David; Simon, David; Englbrecht, Matthias; Stemmler, F.; Berlin, Andreas; Haschka, J.; Renner, Nina; Buder, Thomas; Rech, Jürgen; Engelke, Klaus; Hueber, Axel; Schett, Georg; et al. (2017)
EVALuna2:34454

Inferior mesenteric artery embolization for persistent postpartum hemorrhage after sufficient bilateral iliac arteries embolization: safety and efficacy in eight patients - Engelke, Klaus; Keaveny, Tony M. (British Journal of Radiology, 2019)
CRIS-Team WoS Importer:2019-07-09

Inflammatory bone spur formation in psoriatic arthritis is different from bone spur formation in hand osteoarthritis - Finzel, Stephanie; Sahinbegovic, Enijad; Kocijan, Roland; Engelke, Klaus; Englbrecht, Matthias; Schett, Georg (Arthritis and Rheumatology, 2014)
To investigate the different patterns of bone spur formation in psoriatic arthritis (PsA) and hand osteoarthritis (OA), using high-resolution peripheral quantitative computed tomography (QCT).The study group comprised 70 subjects (25 patients with PsA, 25 patients with hand OA, and 20 healthy controls). The 2 patient groups were similar with regard to age and sex distribution and clinical involvement of the metacarpophalangeal (MCP) joints. All patients underwent high-resolution peripheral QCT scanning of the second, third, and fourth MCP joints of the dominantly affected hand. Demographic and disease-specific data were recorded, and the number, size, and distribution of bone spurs were assessed and compared between patients with PsA and patients with hand OA.The overall number and size of bone spurs were similar in patients with PsA and patients with hand OA. However, localization of lesions within individual joints was substantially different between patients with PsA and those with hand OA. In PsA, bone spurs dominated the radial sides of the joints (for the metacarpal head of the second joint, P < 0.001 versus hand OA; for the base of the second phalangeal joint, P < 0.001 versus hand OA), whereas the palmar and dorsal quadrants were the predilection sites in hand OA. Detailed anatomic analysis showed that bone spurs in the entheseal regions were prominent in patients with PsA but rare in patients with hand OA, and that bone spurs in patients with hand OA typically emerged at the cartilage-bone interphase and the joint margins.Our findings show that the overall number and size of bone spurs are similar in patients with PsA and patients with hand OA. Nonetheless, the anatomic sites of bone proliferation are different between these 2 groups of patients.
EVALuna2:10082

Influence of 3D QCT scan protocol on the QCT-based finite element models of human vertebral cancellous bone - Lu, Yongtao; Engelke, Klaus; Pueschel, Klaus; Morlock, Michael M.; Huber, Gerd (Medical Engineering & Physics, 2014)
Quantitative computed tomography (QCT)-based finite element (FE) models provide a better prediction of vertebral strength than dual-energy X-ray absorptiometry. However, FE models are often created from datasets acquired at different CT scan protocols and it is unclear whether this influences the FE results. The aim of this paper was to investigate whether there was an effect of the CT scan protocol on the FE models. 12 human thoracolumbar vertebrae were scanned on top of a calcium hydroxyapatite calibration phantom using a standard QCT scan protocol - 120kV, 100mAs (PA); and a low dose protocol - 90kV, 150mAs (PB). FE cancellous models with cuboid volume of interest and inhomogeneous nonlinear bone properties were created. Axial compression was simulated. The apparent BMD, modulus and yield strength showed significant differences between the two scan protocols. The apparent BMD, the modulus and yield strength between the two groups were highly linearly correlated. This paper indicated that the FE models created from image datasets acquired at different X-ray tube voltage settings would give significantly different results and this effect could be possibly corrected using a linear correction approach.
EVALuna2:10095

Influence of meniscus on cartilage and subchondral bone features of knees from older individuals: A cadaver study - Touraine, Sebastien; Bouhadoun, Hamid; Engelke, Klaus; Laredo, Jean Denis; Chappard, Christine (PLoS ONE, 2017)
OBJECTIVE: Cartilage and subchondral bone form a functional unit. Here, we aimed to examine the effect of meniscus coverage on the characteristics of this unit in knees of older individuals. METHODS: We assessed the hyaline cartilage, subchondral cortical plate (SCP), and subchondral trabecular bone in areas covered or uncovered by the meniscus from normal cadaver knees (without degeneration). Bone cores harvested from the medial tibial plateau at locations uncovered (central), partially covered (posterior), and completely covered (peripheral) by the meniscus were imaged by micro-CT. The following were measured on images: cartilage volume (Cart.Vol, mm3) and thickness (Cart.Th, mm); SCP thickness (SCP.Th, μm) and porosity (SCP.Por, %); bone volume to total volume fraction (BV/TV, %); trabecular thickness (Tb.Th, μm), spacing (Tb.Sp, μm), and number (Tb.N, 1/mm); structure model index (SMI); trabecular pattern factor (Tb.Pf); and degree of anisotropy (DA). RESULTS: Among the 28 specimens studied (18 females) from individuals with mean age 82.8±10.2 years, cartilage and SCP were thicker at the central site uncovered by the meniscus than the posterior and peripheral sites, and Cart.Vol was greater. SCP.Por was highest in posterior samples. In the upper 1-5 mm of subchondral bone, central samples were characterized by higher values for BV/TV, Tb.N, Tb.Th, and connectivity (Tb.Pf), a more plate-like trabecular structure and lower anisotropy than with other samples. Deeper down, at 6-10 mm, the differences were slightly higher for Tb.Th centrally, DA peripherally and SMI posteriorly. CONCLUSIONS: The coverage or not by meniscus in the knee of older individuals is significantly associated with Cart.Th, SCP.Th, SCP.Por and trabecular microarchitectural parameters in the most superficial 5 mm and to a lesser extent the deepest area of subchondral trabecular bone. These results suggest an effect of differences in local loading conditions. In subchondral bone uncovered by the meniscus, the trabecular architecture resembles that of highly loaded areas.
EVALuna2:33270

Interactions between Muscle and Bone-Where Physics Meets Biology - Herrmann, Marietta; Engelke, Klaus; Ebert, Regina; Müller-Deubert, Sigrid; Rudert, Maximilian; Ziouti, Fani; Jundt, Franziska; Felsenberg, Dieter; Jakob, Franz (Biomolecules, 2020)
Muscle and bone interact via physical forces and secreted osteokines and myokines. Physical forces are generated through gravity, locomotion, exercise, and external devices. Cells sense mechanical strain via adhesion molecules and translate it into biochemical responses, modulating the basic mechanisms of cellular biology such as lineage commitment, tissue formation, and maturation. This may result in the initiation of bone formation, muscle hypertrophy, and the enhanced production of extracellular matrix constituents, adhesion molecules, and cytoskeletal elements. Bone and muscle mass, resistance to strain, and the stiffness of matrix, cells, and tissues are enhanced, influencing fracture resistance and muscle power. This propagates a dynamic and continuous reciprocity of physicochemical interaction. Secreted growth and differentiation factors are important effectors of mutual interaction. The acute effects of exercise induce the secretion of exosomes with cargo molecules that are capable of mediating the endocrine effects between muscle, bone, and the organism. Long-term changes induce adaptations of the respective tissue secretome that maintain adequate homeostatic conditions. Lessons from unloading, microgravity, and disuse teach us that gratuitous tissue is removed or reorganized while immobility and inflammation trigger muscle and bone marrow fatty infiltration and propagate degenerative diseases such as sarcopenia and osteoporosis. Ongoing research will certainly find new therapeutic targets for prevention and treatment.
CRIS-Team Scopus Importer:2020-03-27
Keywords: bone; mechanosensing; mechanotransduction; muscle; myokines; osteokines adaptation

Interaktion zwischen Muskel und Knochen – ein Wechselspiel zwischen Physik und Biologie - Jakob, Franz; Müller-Deubert, Sigrid; Ebert, Regina; Engelke, Klaus; Felsenberg, Dieter; Rudert, Maximilian; Herrmann, Marietta (Osteologie, 2020)
Balanced and reciprocal adaptive interaction between muscle and bone is essential for locomotion and for the maintenance of integrity of the organism in order to avoid ruptures and fractures. Contracting muscles produce physical forces that influence both the musculature itself and the stabilizing skeleton. Gravity and body mass define the power of forces. Escalation of power and repetitions of physical stimuli lead to anabolic effects in both tissues while immobilization, disuse and simulation of micro-gravity produce muscle and bone loss. The impact of physical strain on cells is translated into biochemical signals and generates biological effects. During the last 2-3 decades, the molecular mechanisms of mechanosensing and mechanotransduction have been intensely explored. Stretching, compression and fluid flow respectively set strain on adhesion molecules between cells and the extracellular matrix as well as on cell-cell interactions, thereby causing cell deformations and activation of calcium influx, cAMP and cGMP production and activation of kinases. In consequence, transcription factors acquire nucleotropy, bind to DNA-response elements and modulate transcription. Consecutive changes in the proteome result in enhanced production of structural proteins to fortify the architecture of the cytoskeleton and of cell adhesion. This enhances the stiffness and viscoelasticity of both the cell and the tissue composition in order to adapt to the higher level of power without injury. Besides the mere physical interaction through muscle forces both tissues also exchange information via secretory products of both muscle and bone. These products initiate and regulate interactive adaptation and regeneration with a great deal of functional overlap between tissues. Besides a tonic secretion of polypeptides with secretory domains, both tissues are also capable of secreting vesicles upon exercise that transport pre-synthesized receptors, growth and differentiation factors and miRNAs as a cargo. Since neither of both tissues is capable of producing true endocrine vesicles, they deliver exosomes into the circulation. One adequate stimulus for exosome delivery is calcium influx upon mechanical strain or exercise, respectively. With our steadily increasing knowledge, the evolving picture is an unexpectedly strong influence of mechanical forces on cellular biochemistry and cell biology of tissues. While we just begin to understand the physiology of mechanosensing and mechanotransduction as perfect tools for adaptation to environmental needs, our knowledge about the impact of alterations in this field, e.g. overload and exercise resistance, on chronic diseases like osteoporosis and osteoarthritis is still in its infancy.
CRIS-Team Scopus Importer:2020-06-16
Keywords: exercise; locomotion; mechanobiology; Mechanotransduction; osteoporosis; sarcopenia

Interleukin-6 receptor blockade induces limited repair of bone erosions in rheumatoid arthritis: A micro CT study - Finzel, Stephanie; Rech, Jürgen; Schmidt, Sarah; Engelke, Klaus; Englbrecht, Matthias; Schett, Georg (Annals of the Rheumatic Diseases, 2013)
Introduction: Interleukin-6 receptor (IL-6R) blockade improves the signs and symptoms of rheumatoid arthritis (RA) and retards bone damage. Whether IL-6R blockade allows repair of existing bone erosions is so far unclear. Methods: This study examined bone erosions in the metacarpophalangeal joints of 20 patients receiving treatment with the IL-6R blocker tocilizumab using micro CT (μCT). The maximal width and depth of individual bone erosions was measured at baseline and after 1 year of treatment. Results: 133 bone erosions were identified at baseline with a mean (±SD) size of 2.23±1.26 mm and depth of 2.16±1.50 mm. Distribution analysis showed predominant involvement of the second compared with the third and fourth metacarpophalangeal joints, the metacarpal heads compared with the phalangeal bases and the radial quadrants compared with all other surfaces. Repair of bone erosions during tocilizumab treatment was confined to those lesions showing sclerosis at baseline and/or at follow-up and those with a width larger than 1.6 mm. The mean decrease in width of sclerosed erosions was thus 0.14±0.05 mm (p=0.0086) and 0.20±0.08 mm (p=0.019) for sclerosing lesions after 1 year of treatment. Conclusions: Blockade of IL-6R by tocilizumab can induce limited repair in a subset of erosions, particularly in large lesions with sclerosis. Repair of erosions during tocilizumab treatment reflects the favourable impact of IL-6R blockade on local bone remodelling in patients with RA.
CRIS-Team Scopus Importer:2021-02-03

Joint Repair While Initiating Biologic Therapy in Rheumatoid Arthritis - Brunet, Scott; Manske, Sarah; Engelke, Klaus; Boyd, Steven K.; Barnabe, Cheryl (2018)
EVALuna2:36398

Körperliches Training und Frakturparameter - Kemmler, Wolfgang; von Stengel, Simon; Mayer, Sabine; Engelke, Klaus; Kalender, Willi Alfred (Bewegungstherapie und Gesundheitssport, 2009)
UnivIS-Import:2015-04-14:Pub.2009.phil.dps.iss.psbg.krperl

Körperliches Training zur Frakturprophylaxe des älteren Menschen: Evidenz und trainingsmethodische Umsetzung am Beispiel der Erlanger Fitness und Osteoporose-Präventions-Studie (EFOPS) - Kemmler, Wolfgang; Kohl, Matthias; Engelke, Klaus; von Stengel, Simon (Osteologie, 2019)
Exercise might be one of the most effective therapies to prevent low-traumatic fractures. However, there is still no definite evidence for fracture-preventing effects of exercise on bone. Further, the multiple training aims (i. e. bone strengthening, fall- and fall-impact reduction), corresponding types of exercise and proper composition of exercise parameters, designing effective, safe and customized exercise protocols makes this far from trivial. Moreover, bearing in mind that subjects should maintain exercise life-long, the attractiveness of the exercise program is highly relevant. The aim of the present article is to (a) provide evidence for the fracture-preventing effect of exercise and (b) discuss the generation of effective exercise strategies based on the Erlanger Fitness and Osteoporosis Prevention Study (EFOPS), a 16-year intervention study focusing on low-traumatic clinical fractures. Hundred thirty-seven (137) early postmenopausal women with osteopenia were included in the EFOPS project in 1998. Due to the long-term approach of the study, we applied a non-randomized design with a non-equally balanced distribution of the exercise (EG: n = 86) vs. control (CG). The primary endpoint was the fracture rate of low-traumatic clinical fractures; secondary endpoints were rate of major osteoporotic fractures and development of bone mineral density (BMD). However, apart from these main study aims, several exercise-related issues were addressed in sub-studies particularly during the first six study years. After 16 years, 105 participants with 1680 participant years were included in the final analysis. The fracture rates of low-traumatic fractures (0.42; 95 % CI: 0.20-0.86) and osteoporotic main fractures (0.37; 95 % CI: 0.14-0.88) were significantly lower in the EG compared to the CG. The exercise effect on BMD at the lumbar spine (EG: -1.5 ± 5.0 % vs. CG: -5.8 ± 6.4 %; p <.001) and femoral neck (-6.5 ± 4.6 % vs.-9.6 ± 5.0 %, p <.001) consistently increased during the study course. Sub-studies focusing on BMD and strength effects indicated among others that (a) power trainings is superior to strength training to affect BMD; (b) periodized approaches might be more effective for increasing strength and BMD and maintaining compliance compared with strategies relying on progression only; (c) exercise frequency below 2 sessions/week did not affect BMD even with high strain magnitude and rates. In summary, a sport-scientific approach that clearly scheduled exercise type, exercise parameters and exercise principles and adequately incorporating basic principles of bone metabolism and fall risk might be the most promising strategy to address fracture risk in older people. Apart from sport-science and medicine, however, it is essential to implement the program in an attractive social setting that enables regular, individualized and effective, but also safe and pleasurable exercise training to facilitate subjects' adherence.
CRIS-Team Scopus Importer:2019-09-27
Keywords: Exercise; exercise strategy; low-traumatic fracture; osteoporotic main fracture

Lack of periosteal apposition in the head and neck of femur after menopause in Chinese women with high risk for hip fractures — A cross-sectional study with QCT - Su, Yongbin; Wang, Ling; Liu, Xiaoyan; Yang, Minghui; Yi, Chen; Liu, Yandong; Huang, Pengju; Guo, Zhe; Yu, Aihong; Cheng, Xiaoguang; Wu, Xinbao; Blake, Glen M.; et al. (Bone, 2020)
In elderly subjects and in particular in those with osteoporosis the evidence on age related volume changes of the hip is still very limited. Even less is known about bone changes of the femoral head. The aim of this study is to explore associations of bone size of the femoral head and neck with age in postmenopausal women with very high risk of hip fracture and to investigate associations of femoral head and neck bone mineral density. MIAF (medical image analysis framework)-Femur was used for the analysis of CT datasets from 319 females with acute hip fractures age 50 to 98. Integral BMD and volume of the head and neck were assessed. The femoral head was divided into four quadrants to address differential vBMD and volume responses of its superior, inferior, posterior and anterior parts. Areal BMD (aBMD) of femoral neck was also obtained. In this population of postmenopausal women we did not observe age-related changes in bone volume of the femoral head or neck between ages 50 and 98 years. Integral vBMD in the head in the 90–98 year group was 48.0 mg/cm3 lower than that in 50–59 year group, which accounts for nearly 30% decrease in vBMD with 40 years increase. Age-related vBMD changes in the head quadrants were similar to that in total. With age, the trend line correlation coefficients for vBMD in quadrants were relatively small, but significant (p < 0.001) for all. The femoral head integral vBMD correlates well with neck vBMD and FN aBMD. FN aBMD explained 45% of head integral vBMD variance (p < 0.0001). Elderly women had relative preservation of femoral head and neck bone volume from 50 yrs. over four decades but markedly lower integral vBMD of proximal femur. The findings of our study call in question about the concept of bone expansion with aging even in elderly age.
CRIS-Team Scopus Importer:2020-08-14
Keywords: Age; Femoral head; Femoral neck; Hip fracture; Quantitative computed tomography

Long-Term Exercise and Bone Mineral Density Changes in Postmenopausal Women - Are There Periods of Reduced Effectiveness? - Kemmler, Wolfgang; Engelke, Klaus; von Stengel, Simon (Journal of Bone and Mineral Research, 2016)
There is increasing evidence that physical exercise can prevent fractures in postmenopausal women. However, even with careful adaptation of the exercise program to subjects' changing bone, health, and fitness status, effectivity may still decrease over the time. This could be specifically the case where the limitations of higher age collide with the specification of the exercise program. Thus, the aim of this study was to monitor bone mineral density (BMD) changes over a 16-year period of supervised exercise. Our hypothesis was that BMD differences at lumbar spine (LS) and femoral neck (FN) between exercisers (EG) and nontraining controls (CG) increased throughout the intervention with significant differences for each of the four 4-year observation periods. Sixty-seven (EG, n = 39 versus CG, n = 28) initially early-postmenopausal osteopenic women of the Erlangen Fitness and Osteoporosis Prevention Study (EFOPS) with complete BMD data sets for baseline (1998) and 4-, 8-, 12-, and 16-year follow-up were included in the analysis. The exercise protocol initially focused on a high-intensity strategy that addressed bone but increasingly shifted to a more comprehensive intervention. LS-BMD differences between the EG and CG continuously increased (year 4: 2.4% (95%- Confidence Interval 1.0% to 3.8%), year 8: 3.1% (1.6% to 4.7%), year 12: 3.9% (1.9% to 5.8), year 16: 4.5% (2.5% to 6.6%). Correspondingly, rising differences for FN-BMD (0.9% (-0.2% to 2.1%) versus 1.9% (0.4% to 3.3%) versus 2.0% (0.5% to 3.8%) versus 3.0% (1.0% to 5.0%)) were observed. However, in contrast to our hypothesis, group differences within the four 4-year periods were not consistently significant (LS, p = 0.001 to 0.097; FN, p = 0.026 to 0.673); further, BMD kinetics among the groups varied between LS and FN. Of particular importance, significant differences (p ≤ 0.030) for both regions were still found in the final period. We conclude that exercise-even when adapted for subjects' decreasing bone, health, and fitness status-is consistently effective in favorably affecting BMD in (initially) early-postmenopausal osteopenic women without any leveling-off effect after 16 years of exercise.
EVALuna2:33283

Magnetic Resonance Imaging and Bioelectrical Impedance Analysis to Assess Visceral and Abdominal Adipose Tissue - Chaudry, Oliver; Grimm, Alexandra; Friedberger, Andreas; Kemmler, Wolfgang; Uder, Michael; Jakob, Franz; Quick, Harald H.; von Stengel, Simon; Engelke, Klaus (Obesity, 2020)
Objective This study aimed to compare a state-of-the-art bioelectrical impedance analysis (BIA) device with two-point Dixon magnetic resonance imaging (MRI) for the quantification of visceral adipose tissue (VAT) as a health-related risk factor. Methods A total of 63 male participants were measured using a 3-T MRI scanner and a segmental, multifrequency BIA device. MRI generated fat fraction (FF) maps, in which VAT volume, total abdominal adipose tissue volume, and FF of visceral and total abdominal compartments were quantified. BIA estimated body fat mass and VAT area. Results Coefficients of determination between abdominal (r(2) = 0.75) and visceral compartments (r(2) = 0.78) were similar for both groups, but slopes differed by a factor of two. The ratio of visceral to total abdominal FF was increased in older men compared with younger men. This difference was not detected with BIA. MRI and BIA measurements of the total abdominal volume correlated moderately (r(2) = 0.31-0.56), and visceral measurements correlated poorly (r(2) = 0.13-0.44). Conclusions Visceral BIA measurements agreed better with MRI measurements of the total abdomen than of the visceral compartment, indicating that BIA visceral fat area assessment cannot differentiate adipose tissue between visceral and abdominal compartments in young and older participants.
CRIS-Team WoS Importer:2020-01-14

Magnetic resonance imaging techniques for the quantitative analysis of skeletal muscle: State of the art. - Engelke, Klaus; Chaudry, Oliver; Gast, Lena; Eldib, Mootaz AB; Wang, Ling; Laredo, Jean Denis; Schett, Georg; Nagel, Armin Michael (Journal of Orthopaedic Translation, 2023)
BACKGROUND: Magnetic resonance imaging (MRI) is the dominant 3D imaging modality to quantify muscle properties in skeletal muscle disorders, in inherited and acquired muscle diseases, and in sarcopenia, in cachexia and frailty. METHODS: This review covers T1 weighted and Dixon sequences, introduces T2 mapping, diffusion tensor imaging (DTI) and non-proton MRI. Technical concepts, strengths, limitations and translational aspects of these techniques are discussed in detail. Examples of clinical applications are outlined. For comparison 31P-and 13C-MR Spectroscopy are also addressed. RESULTS: MRI technology provides a rich toolset to assess muscle deterioration. In addition to classical measures such as muscle atrophy using T1 weighted imaging and fat infiltration using Dixon sequences, parameters characterizing inflammation from T2 maps, tissue sodium using non-proton MRI techniques or concentration or fiber architecture using diffusion tensor imaging may be useful for an even earlier diagnosis of the impairment of muscle quality. CONCLUSION: Quantitative MRI provides new options for muscle research and clinical applications. Current limitations that also impair its more widespread use in clinical trials are lack of standardization, ambiguity of image segmentation and analysis approaches, a multitude of outcome parameters without a clear strategy which ones to use and the lack of normal data.
EVALuna2:540329

Methods for segmentation of rheumatoid arthritis bone erosions in high-resolution peripheral quantitative computed tomography (HR-pQCT) - Figueiredo, Camille P.; Kleyer, Arnd; Simon, Dominic; Stemmler, Fabian; d'Oliveira, Isabelle; Weißenfels, Anja; Museyko, Oleg; Friedberger, Andreas; Hueber, Axel; Haschka, Judith; Englbrecht, Matthias; Pereira, Rosa M.R.; et al. (Seminars in Arthritis and Rheumatism, 2017)
The comparison between different techniques to quantify the 3-dimensional size of inflammatory bone erosions in rheumatoid arthritis(RA) patients.Anti-cyclic citrullinated peptide antibody(ACPA) positive RA patients received high-resolution peripheral quantitative computed tomography (HR-pQCT) scans of the metacarpophalangeal joints (MCP). Erosions were measured by three different segmentation techniques: (1) manual method with calculation by half-ellipsoid formula, (2) semi-automated modified Evaluation Script for Erosions (mESE), and (3) semi-automated Medical Image Analysis Framework (MIAF) software. Bland & Altman plots were used to describe agreement between methods. Furthermore, shape of erosions was classified as regular or irregular and then compared to the sphericity obtained by MIAF.A total of 76 erosions from 65 RA patients (46 females/19 males), median age 57 years, median disease duration 6.1 years and median disease activity score 28 of 2.8 units were analyzed. While mESE and MIAF showed good agreement in the measurement of erosion size, the manual method with calculation by half-ellipsoid formula underestimated erosions size, particularly with larger erosions. Accurate segmentation is particularly important in larger erosions, which are irregularly shaped. In all three segmentation techniques irregular erosions were larger in size than regular erosions (MIAF: 19.7 vs. 3.4mm(3); mESE: 15.5 vs. 2.3mm(3); manual = 7.2 vs. 1.52mm(3); all p < 0.001). In accordance, sphericity of erosions measured by MIAF significantly decreased with their size (p < 0.001).MIAF and mESE allow segmentation of inflammatory bone erosions in RA patients with excellent inter reader reliability. They allow calculating erosion volume independent of erosion shape and therefore provide an attractive tool to quantify structural damage in individual joints of RA patients.
EVALuna2:13514

Microcracks in subchondral bone plate is linked to less cartilage damage - Zarka, M.; Hay, E.; Ostertag, A.; Marty, C.; Chappard, C.; Oudet, F.; Engelke, Klaus; Laredo, J. D.; Cohen-Solal, M. (Bone, 2019)
Objectives: Osteoarthritis (OA) is a disease of the whole joint characterized by cartilage loss and subchondral bone remodeling. The role of microcracks in cartilage integrity and subchondral bone homeostasis is not fully understood. The main goal of this work was to evaluate microcrack density in both calcified cartilage and subchondral bone plate in relation to cartilage damage in humans and to better define the association of microcracks and osteocyte density in subchondral bone. Methods: We investigated 18 bone cores from cadaveric human knees that were stained with En-Bloc Basic Fuchsin. We quantified microcrack density, osteocyte density, cartilage surfaces and cartilage damage. The presence of microcracks was confirmed for each bone core by scanning electron microscopy. Finally, trabecular subchondral bone parameters were measured by micro-CT. Results: Microcracks were detected in both calcified cartilage and subchondral bone plate. The density of microcracks in both calcified cartilage (CC) and subchondral bone plate (SBP) was negatively correlated with cartilage damage (r = −0.45, p < 0.05). The presence of microcracks in SBP was associated with a lower histological OA score. Osteocytes formed a dendrite network that abruptly stopped at the border of calcified cartilage. Osteocyte density in subchondral bone plate was increased in the presence of microcracks in calcified cartilage. Conclusions: Subchondral bone plate microcracks might be required for maintaining cartilage homeostasis. Microcracks in calcified cartilage may trigger osteocyte density in subchondral bone plate with subsequent regulation of subchondral bone remodeling to prevent cartilage damage.
CRIS-Team Scopus Importer:2019-05-21
Keywords: Bone; Mechanical loading; Microcracks; Osteoarthritis; Osteocytes

MRI of Potassium and Sodium Enables Comprehensive Analysis of Ion Perturbations in Skeletal Muscle Tissue After Eccentric Exercise. - Gast, Lena; Baier, Laura Marie; Meixner, Christian; Chaudry, Oliver; Engelke, Klaus; Uder, Michael; Nagel, Armin Michael; Heiß, Rafael (Investigative Radiology, 2023)
OBJECTIVES: The aims were to investigate if potassium ( 39 K) magnetic resonance imaging (MRI) can be used to analyze changes in the apparent tissue potassium concentration (aTPC) in calf muscle tissue after eccentric exercise and in delayed-onset muscle soreness, and to compare these to corresponding changes in the apparent tissue sodium concentration (aTSC) measured with sodium ( 23 Na) MRI. MATERIALS AND METHODS: Fourteen healthy subjects (7 female, 7 male; 25.0 ± 2.8 years) underwent 39 K and 23 Na MRI at a 7 T MR system, as well as 1 H MRI at a 3 T MR system. Magnetic resonance imaging data and blood samples were collected at baseline (t0), directly after performing eccentric exercise (t1) and 48 hours after exercise (t2). Self-reported muscle soreness was evaluated using a 10-cm visual analog scale for pain (0, no pain; 10, worst pain) at t0, t1, and t2. Quantification of aTPC/aTSC was performed after correcting the measured 39 K/ 23 Na signal intensities for partial volume and relaxation effects using 5 external reference phantoms. Edema volume and 1 H T 2 relaxation times were determined based on the 1 H MRI data. Participants were divided according to their increase in creatine kinase (CK) level into high (CK t2 ≥ 10·CK t0 ) and low CK (CK t2 < 10·CK t0 ) subjects. RESULTS: Blood serum CK and edema volume were significantly increased 48 hours after exercise compared with baseline ( P < 0.001). Six participants showed a high increase in blood serum CK level at t2 relative to baseline, whereas 8 participants had only a low to moderate increase in blood serum CK. All participants reported increased muscle soreness both at rest and when climbing stairs at t1 (0.4 ± 0.7; 1.4 ± 1.2) and t2 (1.6 ± 1.4; 4.8 ± 1.9) compared with baseline (0 ± 0; 0 ± 0). Moreover, aTSC was increased at t1 in exercised muscles of all participants (increase by 57% ± 24% in high CK, 73% ± 33% in low CK subjects). Forty-eight hours after training, subjects with high increase in blood serum CK still showed highly increased aTSC (increase by 79% ± 57% compared with t0). In contrast, aTPC at t2 was elevated in exercised muscles of low CK subjects (increase by 19% ± 11% compared with t0), in which aTSC had returned to baseline or below. Overall, aTSC and aTPC showed inverse evolution, with changes in aTSC being approximately twice as high as in aTPC. CONCLUSIONS: Our results showed that 39 K MRI is able to detect changes in muscular potassium concentrations caused by eccentric exercise. In combination with 23 Na MRI, this enables a more holistic analysis of tissue ion concentration changes.
EVALuna2:520477

MRI UNDERESTIMATES PRESENCE AND SIZE OF KNEE OSTEOPHYTES USING CT AS A REFERENCE STANDARD - Roemer, Frank; Engelke, Klaus; Laredo, J. -D.; Li, L.; Guermazi, A. (OSTEOARTHRITIS AND CARTILAGE, 2022)
The radiographic diagnosis of knee osteoarthritis (OA) is based on the presence of a definite osteophyte (OP) on the a.p. or p.a. radiograph. OPs represent fibrocartilaginous and skeletal outgrowths that are frequently localized at the joint margins, but central osteophytes may also be observed, especially at the femoral notch. Epidemiologic studies and clinical trials commonly employ MRI using standard clinical sequences and OP assessment is one of the features included in whole organ ordinal OA grading. Commonly used sequence protocols in such studies are based on triplanar fat suppressed T2- or proton density-weighted sequences with bony features as well as fibrous and lipomatous tissues appearing hypointense. This may potentially result in underestimation of such features including osteophyte assessment. Computed tomography (CT), another tomographic technique is considered as the modality of choice for the analysis of mineralized structures such as OPs and may therefore be used as a reference standard for other modalities assessing these structures. Thus, the aim of the current study was to explore the diagnostic performance of routine MRI as used in observational studies and clinical trials of knee OA for the assessment of OPs in all three knee compartments and the femoral notch using CT as a reference standard.<br
CRIS-Team WoS Importer:2022-04-22

MRI underestimates presence and size of knee osteophytes using CT as a reference standard - Roemer, Frank; Engelke, Klaus; Li, L.; Laredo, J. D.; Guermazi, A. (Osteoarthritis and Cartilage, 2023)
Objective: To explore the diagnostic performance of routine magnetic resonance imaging (MRI) for the cross-sectional assessment of osteophytes (OPs) in all three knee compartments using computed tomography (CT) as a reference standard. Methods: The Strontium Ranelate Efficacy in Knee Osteoarthritis (SEKOIA) trial explored the effect of 3 years of treatment with strontium ranelate in patients with primary knee OA. OPs were scored for the baseline visit only using a modified MRI Osteoarthritis Knee Score (MOAKS) scoring system in the patellofemoral (PFJ), the medial tibiofemoral (TFJ) and the lateral TFJ. Size was assessed from 0 to 3 in 18 locations. Descriptive statistics were used to describe differences in ordinal grading between CT and MRI. In addition, weighted-kappa statistics were employed to assess agreement between scoring using the two methods. Sensitivity, specificity, positive predictive value and negative predictive value as well as area under the curve (AUC) measures of diagnostic performance were employed using CT as the reference standard. Results: Included were 74 patients with available MRI and CT data. Mean age was 62.9 ± 7.5 years. Altogether 1,332 locations were evaluated. For the PFJ, MRI detected 141 (72%) of 197 CT-defined OPs with a w-kappa of 0.58 (95% CI [0.52–0.65]). In the medial TFJ, MRI detected 178 (81%) of 219 CT-OPs with a w-kappa of 0.58 (95% CI [0.51–0.64]). For the lateral compartment these numbers were 84 (70%) of 120 CT-OPs with a w-kappa of 0.58 (95% CI [0.50–0.66]). Conclusion: MRI underestimates presence of osteophytes in all three knee compartments. CT may be helpful particularly regarding assessment of small osteophytes particularly in early disease.
CRIS-Team Scopus Importer:2023-03-24
Keywords: CT; Diagnostic performance; Knee; MRI; Osteoarthritis; Osteophytes

MUSCLE DENSITY, BUT NOT SIZE, CORRELATES WELL WITH MUSCLE PERFORMANCE - Wang, L. W.; Yin, Y. L.; Guglielmi, G. G.; Cheng, X. C.; Blake, G. M. B.; Engelke, Klaus (OSTEOPOROSIS INTERNATIONAL, 2020)
CRIS-Team WoS Importer:2021-05-14

Muscle Density, but Not Size, Correlates Well With Muscle Strength and Physical Performance - Wang, Ling; Yin, Lu; Zhao, Yue; Su, Yongbin; Sun, Wei; Chen, Shuo; Liu, Yandong; Yang, Minghui; Yu, Aihong; Guglielmi, Giuseppe; Blake, Glen M.; Cheng, Xiaoguang; et al. (Journal of the American Medical Directors Association, 2020)
Objectives: There is increasing evidence that muscle volume and mass are poor predictors of muscle strength and physical performance. Other assessments of muscle quality such as skeletal muscle density measured by computed tomography (CT) may be more important. The aim of this study was to explore associations of muscle size and density with handgrip strength (HGS) and the Timed Up and Go test (TUG). We also hypothesized that the strength of these associations would depend on the specific muscle of muscle group, namely trunk, hip, and mid-thigh muscles. Design: Cross-sectional study. Setting and Participants: University hospital; 316 volunteers aged 59 to 85 years. Methods: HGS, TUG, and quantitative CT imaging of the lumber, hip, and mid-thigh were performed in volunteers. From the CT images, cross-sectional area and attenuation were determined for the gluteus muscle, trunk muscle at vertebrae L2 level, and mid-thigh muscle. Results: In men and women, associations of muscle area with TUG were insignificant after adjustment for age, height, and weight. Associations with HGS were only significant in men for the gluteus maximus and the mid-thigh but slopes were rather low (β < 0.20). Associations between muscle density and TUG/HGS were more pronounced, in particular for HGS. After adjustment, associations with TUG were significant in women for the gluteus maximus and trunk muscle even (β −0.06, P.001 and β −0.07, P.031, respectively). Conclusions and Implications: Muscle density is more strongly associated with muscle strength than muscle size andin women muscle density was also more strongly associated than muscle size with physical performance. Therefore, muscle density may represent a more clinically meaningful surrogate of muscle performance than muscle size. Muscle density measurements of trunk and gluteus muscles can be easily obtained from routine CT scan and, therefore, may become an important measurement to diagnose and screen for sarcopenia.
CRIS-Team Scopus Importer:2020-08-14
Keywords: computed tomography; grip strength; Muscle density; muscle size; sarcopenia; Timed Up and Go test

Muscle density discriminates hip fracture better than computed tomography X-ray absorptiometry hip areal bone mineral density - Wang, Ling; Yin, Lu; Zhao, Yue; Su, Yongbin; Sun, Wei; Liu, Yandong; Yang, Minghui; Yu, Aihong; Blake, Glen Mervyn; Cheng, Xiaoguang; Wu, Xinbao; Veldhuis, Annegreet; et al. (Journal of Cachexia, Sarcopenia and Muscle, 2020)
Background: Muscle weakness is a key factor in the increase risk of falls and might also play a significant role in the increase of risk of hip fracture. Computed tomography-measured muscle size and muscle density are well-established imaging biomarkers used in studies of physical function, frailty or cancer, but limited to hip fracture. In particular, it is warranted to have a better understanding of the performance of muscle size and density in the discrimination of acute hip fractures. We also aim to determine age-related differences of muscle size and density in healthy controls and hip fracture patients. Methods: Four hundred thirty-eight low-energy acute hip fracture cases and 316 healthy controls from the China Action on Spine and Hip Status study were included in the study. Muscle cross-sectional area and density were measured for the gluteus maximus and gluteus medius and minimus. Areal bone mineral density (aBMD) of the femoral neck and total hip was measured. Using propensity score matching, we generated three samples with cases and controls matched for age, body mass index, and gender: femoral neck fracture (FNF), intertrochanteric fracture (ITF), and any hip fracture vs. controls, respectively. Results: Handgrip strength, gluteus muscle area and density, and bone parameters of the matched hip fracture groups were lower than those of the correspondence control groups, respectively (P < 0.05). The univariate analysis showed that associations of aBMD with FNF and with ITF were significantly weaker than associations between fracture and muscle parameters. Gluteus medius and minimus muscle density showed the highest areas under the curve (AUC) with FNF (0.88, 95% confidence interval, 0.85–0.92) and trochanteric fracture (0.95, 95% confidence interval, 0.92–0.97). The model including all muscle and bone parameters provided the highest AUC (FNF: AUC 0.912; ITF: AUC 0.958), and AUC results of another selected model without muscle density showed that association with fracture significantly dropped (FNF: AUC 0.755; ITF: AUC 0.858). Separate results for the two age groups younger and older than 70 years showed no age-related significant differences in discriminate models. Conclusions: Muscle density performs better than aBMD from hip computed tomography X-ray absorptiometry and muscle size in discrimination of hip fracture. Combination of aBMD and muscle density provided the best discrimination. The integration of muscle assessments may trigger a paradigm shift in hip fracture prediction. Gluteus muscle density should also be evaluated as treatment outcome.
CRIS-Team Scopus Importer:2020-09-25
Keywords: Acute hip fracture; Bone mineral density; Muscle density; Muscle size

Muscle density is an independent risk factor of second hip fracture: a prospective cohort study - Wang, Ling; Yin, Lu; Yang, Minghui; Ge, Yufeng; Liu, Yandong; Su, Yongbin; Guo, Zhe; Yan, Dong; Xu, Zhengyang; Huang, Pengju; Geng, Jian; Liu, Xingli; et al. (Journal of Cachexia, Sarcopenia and Muscle, 2022)
Background Patients with a first hip fracture are at high risk of fracturing their other hip. Despite this, preventive therapy is often not given. Because little is known about specific risk factors of a second hip fracture, we investigated the association with areal bone mineral density (aBMD), muscle size, and density. We also investigated whether muscle parameters predict the risk of a contralateral fracture independently of aBMD. Methods Three groups were included, one without hip fracture (a subcohort of the China Action on Spine and Hip Status study), one with a first, and one with a second hip fracture. Subjects with fractures were recruited from the longitudinal Chinese Second Hip Fracture Evaluation (CSHFE). Computed tomography scans of CSHFE patients, which were obtained immediately following their first fracture, were used to measure cross-sectional area and density of the gluteus maximus (G.MaxM) and gluteus medius and minimus (G.Med/MinM) muscles. Computed tomography X-ray absorptiometry was used to measure aBMD of the contralateral femur. Median follow-up time to second fracture was 4.5 years. Cox proportional hazards models were used to compute hazard ratios (HR) of second hip fracture risk in subjects with a first hip fracture. Multivariate logistic regressions were used to compare odds ratios (OR) for the risk of a first and second hip fracture. Results Three hundred and one participants (68.4 +/- 6.1 years, 64% female) without and 302 participants (74.6 +/- 9.9 years, 71% female) with a first hip fracture were included in the analysis. Among the latter, 45 (79.2 +/- 7.1 years) sustained a second hip fracture. ORs for first hip fracture were significant for aBMD and muscle size and density. ORs for a second fracture were smaller by a factor of 3 to 4 and no longer significant for femoral neck (FN) aBMD. HRs for predicting second hip fracture confirmed the results. G.Med/MinM density (HR, 1.68; CI, 1.20-2.35) and intertrochanter aBMD (HR, 1.62; CI, 1.13-2.31) were the most significant. FN aBMD was not significant. G.Med/MinM density remained significant for predicting second hip fracture after adjustment for FN (HR, 1.66; Cl, 1.18-2.30) or total hip aBMD (HR, 1.50; 95% Cl, 1.04-2.15). Conclusions Density of the G.Med/MinM muscle is an aBMD independent predictor of the risk of second hip fracture. Intertrochanteric aBMD is a better predictor of second hip fracture than FN and total hip aBMD. These results may trigger a paradigm shift in the assessment of second hip fracture risk and prevention strategies.
CRIS-Team WoS Importer:2022-04-29

MUSCLE DENSITY IS BETTER THAN BONE DENSITY IN THE DISCRIMINATION OF INCIDENT HIP FRACTURE: A PROPENSITY SCORE MATCHING STUDY - Wang, L. W.; Yin, Y. L.; Blake, G. M. B.; Cheng, X. C.; Engelke, Klaus (OSTEOPOROSIS INTERNATIONAL, 2020)
CRIS-Team WoS Importer:2021-05-14

Muscle size and density are independently associated with death after hip fracture: A prospective cohort study - Wang, Ling; Yang, Minghui; Ge, Yufeng; Liu, Yandong; Su, Yongbin; Guo, Zhe; Huang, Pengju; Geng, Jian; Wang, Gang; Blake, Glen M.; He, Bo; Yin, Lu; et al. (Journal of Cachexia, Sarcopenia and Muscle, 2023)
BackgroundMortality following hip fracture is high and incompletely understood. We hypothesize that hip musculature size and quality are related to mortality following hip fracture. This study aims to investigate the associations of hip muscle area and density from hip CT with death following hip fracture as well as assess the dependence of this association on time after hip fracture. MethodsIn this secondary analysis of the prospectively collected CT images and data from the Chinese Second Hip Fracture Evaluation, 459 patients were enrolled between May 2015 and June 2016 and followed up for a median of 4.5 years. Muscle cross-sectional area and density were measured of the gluteus maximus (G.MaxM) and gluteus medius and minimus (G.Med/MinM) and aBMD of the proximal femur. The Goutallier classification (GC) was used for qualitatively assessing muscle fat infiltration. Separate Cox models were used to predict mortality risk adjusted for covariates. ResultsAt the end of the follow-up, 85 patients were lost, 81 patients (64% women) had died, and 293 (71% women) survived. The mean age of non-surviving patients at death (82.0 +/- 8.1 years) was higher than that of the surviving patients (74.4 +/- 9.9 years). The Parker Mobility Score and the American Society of Anesthesiologists scores of the patients that died were respectively lower and higher compared to the surviving patients. Hip fracture patients received different surgical procedures, and no significant difference in the percentage of hip arthroplasty was observed between the dead and the surviving patients (P = 0.11). The cumulative survival was significantly lower for patients with low G.MaxM area and density and low G.Med/MinM density, independent of age and clinical risk scores. The GC grades were not associated with the mortality after hip fracture. Muscle density of both G.MaxM (adj. HR 1.83; 95% CI, 1.06-3.17) and G.Med/MinM (adj. HR 1.98; 95% CI, 1.14-3.46) was associated with mortality in the 1st year after hip fracture. G.MaxM area (adj. HR 2.11; 95% CI, 1.08-4.14) was associated with mortality in the 2nd and later years after hip fracture. ConclusionOur results for the first time show that hip muscle size and density are associated with mortality in older hip fracture patients, independent of age and clinical risk scores. This is an important finding to better understand the factors contributing to the high mortality in older hip fracture patients and to develop better future risk prediction scores that include muscle parameters.
CRIS-Team WoS Importer:2023-06-02

Next-generation imaging of the skeletal system and its blood supply - Grüneboom, Anika; Kling, Lasse; Christiansen, Silke; Mill, Leonid; Maier, Andreas; Engelke, Klaus; Quick, Harald H.; Schett, Georg; Gunzer, Matthias (Nature Reviews Rheumatology, 2019)
Bone is organized in a hierarchical 3D architecture. Traditionally, analysis of the skeletal system was based on bone mass assessment by radiographic methods or on the examination of bone structure by 2D histological sections. Advanced imaging technologies and big data analysis now enable the unprecedented examination of bone and provide new insights into its 3D macrostructure and microstructure. These technologies comprise ex vivo and in vivo methods including high-resolution computed tomography (CT), synchrotron-based imaging, X-ray microscopy, ultra-high-field magnetic resonance imaging (MRI), light-sheet fluorescence microscopy, confocal and intravital two-photon imaging. In concert, these techniques have been used to detect and quantify a novel vascular system of trans-cortical vessels in bone. Furthermore, structures such as the lacunar network, which harbours and connects osteocytes, become accessible for 3D imaging and quantification using these methods. Next-generation imaging of the skeletal system and its blood supply are anticipated to contribute to an entirely new understanding of bone tissue composition and function, from macroscale to nanoscale, in health and disease. These insights could provide the basis for early detection and precision-type intervention of bone disorders in the future.
CRIS-Team Scopus Importer:2019-08-27

NOVEL TRIPHASIC CALCIUM-BASED IMPLANT MATERIAL DELIVERED BY A MINIMALLY-INVASIVE LOCAL OSTEO-ENHANCEMENT PROCEDURE INCREASES LONG-TERM PROXIMAL FEMUR TRABECULAR DENSITY IN OSTEOPOROTIC WOMEN AS ASSESSED BY QCT - Engelke, Klaus; Hill, R.; Fuerst, T.; Huber, B.; Chin, M.; Howe, J.; Genant, H. (2018)
EVALuna2:36400

Odanacatib treatment affects trabecular and cortical bone in the femur of postmenopausal women: results of a two-year placebo-controlled trial - Engelke, Klaus; Fuerst, Thomas; Dardzinski, Bernard; Kornak, John; Ather, Shabana; Genant, Harry K.; De Papp, Anne (Journal of Bone and Mineral Research, 2015)
Odanacatib, a selective cathepsin K inhibitor, increases areal bone mineral density (aBMD) at the spine and hip of postmenopausal women. To gain additional insight into the effects on trabecular and cortical bone, we analyzed quantitative computed tomography (QCT) data of postmenopausal women treated with odanacatib using Medical Image Analysis Framework (MIAF; Institute of Medical Physics, University of Erlangen, Erlangen, Germany). This international, randomized, double-blind, placebo-controlled, 2-year, phase 3 trial enrolled 214 postmenopausal women (mean age 64 years) with low aBMD. Subjects were randomized to odanacatib 50 mg weekly (ODN) or placebo (PBO); all participants received calcium and vitamin D. Hip QCT scans at 24 months were available for 158 women (ODN: n = 78 women; PBO: n = 80 women). There were consistent and significant differential treatment effects (ODN-PBO) for total hip integral (5.4%), trabecular volumetric BMD (vBMD) (12.2%), and cortical vBMD (2.5%) at 24 months. There was no significant differential treatment effect on integral bone volume. Results for bone mineral content (BMC) closely matched those for vBMD for integral and trabecular compartments. However, with small but mostly significant differential increases in cortical volume (1.0% to 1.3%) and thickness (1.4% to 1.9%), the percentage cortical BMC increases were numerically larger than those of vBMD. With a total hip BMC differential treatment effect (ODN-PBO) of nearly 1000 mg, the proportions of BMC attributed to cortical gain were 45%, 44%, 52%, and 40% for the total, neck, trochanter, and intertrochanter subregions, respectively. In postmenopausal women treated for 2 years, odanacatib improved integral, trabecular, and cortical vBMD and BMC at all femur regions relative to placebo when assessed by MIAF. Cortical volume and thickness increased significantly in all regions except the femoral neck. The increase in cortical volume and BMC paralleled the increase in cortical vBMD, demonstrating a consistent effect of ODN on cortical bone. Approximately one-half of the absolute BMC gain occurred in cortical bone. © 2014 American Society for Bone and Mineral Research.
EVALuna2:10102

Once Weekly Whole-Body Electromyostimulation Enhances Muscle Quality in Men: Data of the Randomized Controlled Franconian Electromyostimulation and Golf Study - Zink-Rückel, Carina; Chaudry, Oliver; Engelke, Klaus; Ghasemikaram, Mansour; Kohl, Matthias; Uder, Michael; Kemmler, Wolfgang (Frontiers in Physiology, 2021)
Whole-body electromyostimulation (WB-EMS) is commercially advertised as a time-efficient resistance-type exercise technology. Indeed, the commercial, non-medical setting applies 20 min of WB-EMS only once a week. However, this setting conflicts with the approved scientific approach of higher training frequencies. Using data from an ongoing study on WB-EMS and golf performance as a vehicle, we evaluate the effect of once weekly WB-EMS on changes of fatty muscle infiltration, as a crucial parameter of muscle quality. Fifty-four moderately physically active male amateur golfers 18–70 years old were randomly allocated to a WB-EMS (n = 27) with a standard setting of once weekly 20 min and a non-WB-EMS control group (CG, n = 27). Intermuscular adipose tissue (IMAT) volume and intrafascial muscle tissue (MT) volume per unit of intrafascial volume as determined by magnetic resonance imaging were used to characterize muscle quality. Intention to treat analysis with multiple imputation was applied. WB-EMS was conducted at the participants’ homes; thus, the attendance rate was close to 100%. After 16 weeks of intervention, we observed increases in volume-adjusted IMAT (p = 0.040) and decreases in MT (p = 0.206) in the CG. IMAT decreased in the WB-EMS group (p = 0.215), while MT increased significantly (p = 0.032). Of importance, group difference (i.e., “effects”) for intra-group changes in volume-adjusted IMAT (effect size: d´ = 0.66; p = 0.028) and MT (d´ = 0.70; p = 0.020) was significant for both parameters. Once weekly WB-EMS application significantly affects muscle quality of the mid-thigh in moderately active, healthy men 18–70 years old.
CRIS-Team Scopus Importer:2021-08-13
Keywords: fatty muscle infiltration; men; muscle quality; muscle tissue; whole-body electromyostimulation

Open-source image analysis tool for the identification and quantification of cortical interruptions and bone erosions in high-resolution peripheral quantitative computed tomography images of patients with rheumatoid arthritis - Zhao, Mingjie; Tse, Justin J.; Kuczynski, Michael T.; Brunet, Scott C.; Yan, Ryan; Engelke, Klaus; Peters, Michiel; van den Bergh, Joop P.; van Rietbergen, Bert; Stok, Kathryn S.; Barnabe, Cheryl; Pauchard, Yves; et al. (Bone, 2022)
Identification of bone erosions and quantification of erosion volume is important for rheumatoid arthritis diagnosis, and can add important information to evaluate disease progression and treatment effects. High-resolution peripheral quantitative computed tomography (HR-pQCT) is well suited for this purpose, however analysis methods are not widely available. The purpose of this study was to develop an open-source software tool for the identification and quantification of bone erosions using images acquired by HR-pQCT. The collection of modules, Bone Analysis Modules (BAM) – Erosion, implements previously published erosion analysis techniques as modules in 3D Slicer, an open-source image processing and visualization tool. BAM includes a module to automatically identify cortical interruptions, from which erosions are manually selected, and a hybrid module that combines morphological and level set operations to quantify the volume of bone erosions. HR-pQCT images of the second and third metacarpophalangeal (MCP) joints were acquired in patients with RA (XtremeCT, n = 14, XtremeCTII, n = 22). The number of cortical interruptions detected by BAM-Erosion agreed strongly with the previously published cortical interruption detection algorithm for both XtremeCT (r2 = 0.85) and XtremeCTII (r2 = 0.87). Erosion volume assessment by BAM-Erosion agreed strongly (r2 = 0.95) with the Medical Image Analysis Framework. BAM-Erosion provides an open-source erosion analysis tool that produces comparable results to previously published algorithms, with improved options for visualization. The strength of the tool is that it implements multiple image processing algorithms for erosion analysis on a single, widely available, open-source platform that can accommodate future updates.
CRIS-Team Scopus Importer:2022-10-14
Keywords: Bone erosions; Cortical interruptions; High-resolution peripheral quantitative computed tomography; Image processing; Metacarpophalangeal joint; Open source software; Rheumatoid arthritis

Opportunistic Screening Techniques for Analysis of CT Scans - Engelke, Klaus; Chaudry, Oliver; Bartenschlager, Stefan (Current Osteoporosis Reports, 2022)
Purpose of Review: Opportunistic screening is a combination of techniques to identify subjects of high risk for osteoporotic fracture using routine clinical CT scans prescribed for diagnoses unrelated to osteoporosis. The two main components are automated detection of vertebral fractures and measurement of bone mineral density (BMD) in CT scans, in which a phantom for calibration of CT to BMD values is not used. This review describes the particular challenges of opportunistic screening and provides an overview and comparison of current techniques used for opportunistic screening. The review further outlines the performance of opportunistic screening. Recent Findings: A wide range of technologies for the automatic detection of vertebral fractures have been developed and successfully validated. Most of them are based on artificial intelligence algorithms. The automated differentiation of osteoporotic from traumatic fractures and vertebral deformities unrelated to osteoporosis, the grading of vertebral fracture severity, and the detection of mild vertebral fractures is still problematic. The accuracy of automated fracture detection compared to classical radiological semi-quantitative Genant scoring is about 80%. Accuracy errors of alternative BMD calibration methods compared to simultaneous phantom-based calibration used in standard quantitative CT (QCT) range from below 5% to about 10%. The impact of contrast agents, frequently administered in clinical CT on the determination of BMD and on fracture risk determination is still controversial. Summary: Opportunistic screening, the identification of vertebral fracture and the measurement of BMD using clinical routine CT scans, is feasible but corresponding techniques still need to be integrated into the clinical workflow and further validated with respect to the prediction of fracture risk.
CRIS-Team Scopus Importer:2022-12-02
Keywords: Computed tomography; Fracture risk; Internal BMD calibration; Opportunistic screening; Vertebral fracture assessment

Opportunistic Screening Using Low-Dose CT and the Prevalence of Osteoporosis in China: A Nationwide, Multicenter Study - Cheng, Xiaoguang; Zhao, Kaiping; Zha, Xiaojuan; Du, Xia; Li, Yongli; Chen, Shuang; Wu, Yan; Li, Shaolin; Lu, Yong; Zhang, Yuqin; Xiao, Xigang; Li, Yuehua; et al. (Journal of Bone and Mineral Research, 2020)
Opportunistic screening for osteoporosis can be performed using low-dose computed tomography (LDCT) imaging obtained for other clinical indications. In this study we explored the CT-derived bone mineral density (BMD) and prevalence of osteoporosis from thoracic LDCT in a large population cohort of Chinese men and women. A total of 69,095 adults (40,733 men and 28,362 women) received a thoracic LDCT scan for the purpose of lung cancer screening between 2018 and 2019, and data were obtained for analysis from the China Biobank Project, a prospective nationwide multicenter population study. Lumbar spine (L-1-L-2) trabecular volumetric bone mineral density (vBMD) was derived from these scans using quantitative computed tomography (QCT) software and the American College of Radiology QCT diagnostic criteria for osteoporosis were applied. Geographic regional differences in the prevalence of osteoporosis were assessed and the age-standardized, population prevalence of osteoporosis in Chinese men and women was estimated from the 2010 China census. The prevalence of osteoporosis by QCT for the Chinese population aged >50 years was 29.0% for women and 13.5% for men, equating to 49.0 million and 22.8 million, respectively. In women, this rate is comparable to estimates from dual-energy X-ray absorptiometry (DXA), but in men, the prevalence is double. Prevalence varied geographically across China, with higher rates in the southwest and lower rates in the northeast. Trabecular vBMD decreased with age in both men and women. Women had higher peak trabecular vBMD (185.4 mg/cm(3)) than men (176.6 mg/cm(3)) at age 30 to 34 years, but older women had lower trabecular vBMD (62.4 mg/cm(3)) than men (92.1 mg/cm(3)) at age 80 years. We show that LDCT-based opportunistic screening could identify large numbers of patients with low lumbar vBMD, and that future cohort studies are now required to evaluate the clinical utility of such screening in terms of fracture prevention and supporting national health economic analyses. (c) 2020 The Authors. Journal of Bone and Mineral Research published by Wiley Periodicals LLC on behalf of American Society for Bone and Mineral Research (ASBMR).
CRIS-Team WoS Importer:2020-11-20

Opportunistic Screening With CT: Comparison of Phantomless BMD Calibration Methods - Bartenschlager, Stefan; Cavallaro, Alexander Josef; Pogarell, Tobias; Chaudry, Oliver; Uder, Michael; Khosla, Sundeep; Schett, Georg; Engelke, Klaus (Journal of Bone and Mineral Research, 2023)
Opportunistic screening is a new promising technique to identify individuals at high risk for osteoporotic fracture using computed tomography (CT) scans originally acquired for an clinical purpose unrelated to osteoporosis. In these CT scans, a calibration phantom traditionally required to convert measured CT values to bone mineral density (BMD) is missing. As an alternative, phantomless calibration has been developed. This study aimed to review the principles of four existing phantomless calibration methods and to compare their performance against the gold standard of simultaneous calibration (ΔBMD). All methods were applied to a dataset of 350 females scanned with a highly standardized CT protocol (DS1) and to a second dataset of 114 patients (38 female) from clinical routine covering a large range of CT acquisition and reconstruction parameters (DS2). Three of the phantomless calibration methods must be precalibrated with a reference dataset containing a calibration phantom. Sixty scans from DS1 and 57 from DS2 were randomly selected for this precalibration. For each phantomless calibration method first the best combination of internal reference materials (IMs) was selected. These were either air and blood or subcutaneous adipose tissue, blood, and cortical bone. In addition, for phantomless calibration a fifth method based on average calibration parameters derived from the reference dataset was applied. For DS1, ΔBMD results (mean (Formula presented.) standard deviation) for the phantomless calibration methods requiring a precalibration ranged from 0.1 (Formula presented.) 2.7 mg/cm3 to 2.4 (Formula presented.) 3.5 mg/cm3 with similar means but significantly higher standard deviations for DS2. Performance of the phantomless calibration method, which does not require a precalibration was worse (ΔBMD DS1: 12.6 (Formula presented.) 13.2 mg/cm3, DS2: 0.5 (Formula presented.) 8.8 mg/cm3). In conclusion, phantomless BMD calibration performs well if precalibrated with a reference dataset. © 2023 The Authors. Journal of Bone and Mineral Research published by Wiley Periodicals LLC on behalf of American Society for Bone and Mineral Research (ASBMR).
CRIS-Team Scopus Importer:2023-10-20
Keywords: BONE MINERAL DENSITY; PERFORMANCE OF PHANTOMLESS CALIBRATION; OPPORTUNISTIC SCREENING; SIMULTANEOUS CALIBRATION

Osteitis and synovitis, but not bone erosion, is associated with proteoglycan loss and microstructure damage in the cartilage of patients with rheumatoid arthritis - Herz, Barbara; Albrecht, Andreas; Englbrecht, Matthias; Welsch, Götz; Uder, Michael; Renner, Nina; Schlechtweg, Philipp; Paul, Dominik; Lauer, Lars; Engelke, Klaus; Janka, Rolf Matthias; Rech, Jürgen; et al. (Annals of the Rheumatic Diseases, 2014)
To investigate the relation between anatomic changes of the synovium, the bone, the bone marrow and the cartilage to biochemical properties of the cartilage in patients with rheumatoid arthritis (RA).33 patients with RA received 3-T MRI scans of the metacarpophalangeal joints. Two independent methods, (A) the delayed gadolinium enhanced MRI of the cartilage (dGEMRIC, T2-mapping), which was used to assess the biochemical properties of the cartilage; (B) synovitis, osteitis and bone erosions were quantified according to the RA MRI scoring (RAMRIS) method and cartilage thickness (CT), interbone joint space (IBJS, distance between proximal and distal bone surface) and intercartilage joint space (ICJS, distance between proximal and distal cartilage surface) were measured.Biochemical changes of the cartilage, corresponding to low dGEMRIC and high T2 values, were more likely to be seen in joints with decreased IBJS and ICJS as well as decreased CT. For instance, dGEMRIC was directly correlated to the IBJS (p=0.001) and ICJS (p=0.001), whereas T2 mapping was inversely correlated to IBJS and ICJS (both p=0.017). Moreover, the degree of osteitis, and to some extent synovitis, was correlated to biochemical cartilage changes as measured by dGEMRIC (p=0.003) or the T2 mapping (p=0.013). By contrast, bone erosions did not correlate to the degree of biochemical cartilage changes.These data support the concept that synovitis and osteitis may be two main triggers for cartilage damage. Thus, the actual inflammatory state of a joint, but not so much the degree of bone erosion, appears to influence cartilage properties in RA.
EVALuna2:10039

Osteoporotic Fractures: Diagnosis, Evaluation, and Significance From the International Working Group on DXA Best Practices - Khan, Aliya A.; Slart, Riemer H.J.A.; Ali, Dalal S.; Bock, Oliver; Carey, John J.; Camacho, Pauline; Engelke, Klaus; Erba, Paola A.; Harvey, Nicholas C.; Lems, Willem F.; Morgan, Sarah; Moseley, Kendall F.; et al. (Mayo Clinic Proceedings, 2024)
Osteoporotic fractures, also known as fragility fractures, are reflective of compromised bone strength and are associated with significant morbidity and mortality. Such fractures may be clinically silent, and others may present clinically with pain and deformity at the time of the injury. Unfortunately, and even at the time of detection, most individuals sustaining fragility fractures are not identified as having underlying metabolic bone disease and are not evaluated or treated to reduce the incidence of future fractures. A multidisciplinary international working group with representation from international societies dedicated to advancing the care of patients with metabolic bone disease has developed best practice recommendations for the diagnosis and evaluation of individuals with fragility fractures. A comprehensive narrative review was conducted to identify key articles on fragility fractures and their impact on the incidence of further fractures, morbidity, and mortality. This document represents consensus among the supporting societies and harmonizes best practice recommendations consistent with advances in research. A fragility fracture in an adult is an important predictor of future fractures and requires further evaluation and treatment of the underlying osteoporosis. It is important to recognize that most fragility fractures occur in patients with bone mineral density T scores higher than −2.5, and these fractures confirm the presence of skeletal fragility even in the presence of a well-maintained bone mineral density. Fragility fractures require further evaluation with exclusion of contributing factors for osteoporosis and assessment of clinical risk factors for fracture followed by appropriate pharmacological intervention designed to reduce the risk of future fracture. Because most low-trauma vertebral fractures do not present with pain, dedicated vertebral imaging and review of past imaging is useful in identifying fractures in patients at high risk for vertebral fractures. Given the importance of fractures in confirming skeletal fragility and predicting future events, it is recommended that an established classification system be used for fracture identification and reporting.
CRIS-Team Scopus Importer:2024-07-05

Pitfalls in the measurement of muscle mass: a need for a reference standard - Buckinx, Fanny; Landi, Francesco; Cesari, Matteo; Fielding, Roger A.; Visser, Marjolein; Engelke, Klaus; Maggi, Stefania; Dennison, Elaine; Al-Daghri, Nasser M.; Allepaerts, Sophie; Bauer, Jurgen; Bautmans, Ivan; et al. (Journal of Cachexia, Sarcopenia and Muscle, 2018)
BACKGROUND: All proposed definitions of sarcopenia include the measurement of muscle mass, but the techniques and threshold values used vary. Indeed, the literature does not establish consensus on the best technique for measuring lean body mass. Thus, the objective measurement of sarcopenia is hampered by limitations intrinsic to assessment tools. The aim of this study was to review the methods to assess muscle mass and to reach consensus on the development of a reference standard. METHODS: Literature reviews were performed by members of the European Society for Clinical and Economic Aspects of Osteoporosis and Osteoarthritis working group on frailty and sarcopenia. Face-to-face meetings were organized for the whole group to make amendments and discuss further recommendations. RESULTS: A wide range of techniques can be used to assess muscle mass. Cost, availability, and ease of use can determine whether the techniques are better suited to clinical practice or are more useful for research. No one technique subserves all requirements but dual energy X-ray absorptiometry could be considered as a reference standard (but not a gold standard) for measuring muscle lean body mass. CONCLUSIONS: Based on the feasibility, accuracy, safety, and low cost, dual energy X-ray absorptiometry can be considered as the reference standard for measuring muscle mass.
EVALuna2:36403

PPARβ/δ governs Wnt signaling and bone turnover - Scholtysek, Carina; Katzenbeisser, Julia; Fu, He; Uderhardt, Stefan; Ipseiz, Natacha; Stoll, Cornelia; Zaiss, Mario; Stock, Michael; Donhauser, Laura-Robina; Boehm, Christina; Kleyer, Arnd; Heß, Andreas; et al. (Nature Medicine, 2013)
Peroxisome proliferator-activated receptors (PPARs) act as metabolic sensors and central regulators of fat and glucose homeostasis. Furthermore, PPAR? has been implicated as major catabolic regulator of bone mass in mice and humans. However, a potential involvement of other PPAR subtypes in the regulation of bone homeostasis has remained elusive. Here we report a previously unrecognized role of PPAR?/? as a key regulator of bone turnover and the crosstalk between osteoblasts and osteoclasts. In contrast to activation of PPAR?, activation of PPAR?/? amplified Wnt-dependent and ?-catenin-dependent signaling and gene expression in osteoblasts, resulting in increased expression of osteoprotegerin (OPG) and attenuation of osteoblast-mediated osteoclastogenesis. Accordingly, PPAR?/?-deficient mice had lower Wnt signaling activity, lower serum concentrations of OPG, higher numbers of osteoclasts and osteopenia. Pharmacological activation of PPAR?/? in a mouse model of postmenopausal osteoporosis led to normalization of the altered ratio of tumor necrosis factor superfamily, member 11 (RANKL, also called TNFSF11) to OPG, a rebalancing of bone turnover and the restoration of normal bone density. Our findings identify PPAR?/? as a promising target for an alternative approach in the treatment of osteoporosis and related diseases.
EVALuna2:8501

Prediction of Hip Failure Load: In Vitro Study of 80 Femurs Using Three Imaging Methods and Finite Element Models-The European Fracture Study (EFFECT) - Pottecher, Pierre; Engelke, Klaus; Duchemin, Laure; Museyko, Oleg; Moser, Thomas; Mitton, David; Vicaut, Eric; Adams, Judith; Skalli, Wafa; Laredo, Jean Denis; Bousson, Valerie (Radiology, 2016)
Purpose To evaluate the performance of three imaging methods (radiography, dual-energy x-ray absorptiometry [DXA], and quantitative computed tomography [CT]) and that of a numerical analysis with finite element modeling (FEM) in the prediction of failure load of the proximal femur and to identify the best densitometric or geometric predictors of hip failure load. Materials and Methods Institutional review board approval was obtained. A total of 40 pairs of excised cadaver femurs (mean patient age at time of death, 82 years ± 12 [standard deviation]) were examined with (a) radiography to measure geometric parameters (lengths, angles, and cortical thicknesses), (b) DXA (reference standard) to determine areal bone mineral densities (BMDs), and (c) quantitative CT with dedicated three-dimensional analysis software to determine volumetric BMDs and geometric parameters (neck axis length, cortical thicknesses, volumes, and moments of inertia), and (d) quantitative CT-based FEM to calculate a numerical value of failure load. The 80 femurs were fractured via mechanical testing, with random assignment of one femur from each pair to the single-limb stance configuration (hereafter, stance configuration) and assignment of the paired femur to the sideways fall configuration (hereafter, side configuration). Descriptive statistics, univariate correlations, and stepwise regression models were obtained for each imaging method and for FEM to enable us to predict failure load in both configurations. Results Statistics reported are for stance and side configurations, respectively. For radiography, the strongest correlation with mechanical failure load was obtained by using a geometric parameter combined with a cortical thickness (r(2) = 0.66, P < .001; r(2) = 0.65, P < .001). For DXA, the strongest correlation with mechanical failure load was obtained by using total BMD (r(2) = 0.73, P < .001) and trochanteric BMD (r(2) = 0.80, P < .001). For quantitative CT, in both configurations, the best model combined volumetric BMD and a moment of inertia (r(2) = 0.78, P < .001; r(2) = 0.85, P < .001). FEM explained 87% (P < .001) and 83% (P < .001) of bone strength, respectively. By combining (a) radiography and DXA and (b) quantitative CT and DXA, correlations with mechanical failure load increased to 0.82 (P < .001) and 0.84 (P < .001), respectively, for radiography and DXA and to 0.80 (P < .001) and 0.86 (P < .001) , respectively, for quantitative CT and DXA. Conclusion Quantitative CT-based FEM was the best method with which to predict the experimental failure load; however, combining quantitative CT and DXA yielded a performance as good as that attained with FEM. The quantitative CT DXA combination may be easier to use in fracture prediction, provided standardized software is developed. These findings also highlight the major influence on femoral failure load, particularly in the trochanteric region, of a densitometric parameter combined with a geometric parameter. (©) RSNA, 2016 Online supplemental material is available for this article.
EVALuna2:33284

Prevalence of sarcopenic obesity in Germany using established definitions: Baseline data of the FORMOsA study - Kemmler, Wolfgang; von Stengel, Simon; Engelke, Klaus; Sieber, Cornel; Freiberger, Ellen (Osteoporosis international, 2016)
The prevalence of sarcopenic obesity in community-dwelling women 70 years and older according to established sarcopenia and obesity definitions averaged between 0 and 2.3 % and can thus be considered as relatively low. However, the converse argument that sarcopenic obesity was incompatible with an independent life cannot be confirmed.The primary aim of the study was to determine the prevalence of sarcopenic obesity (SO) in community-dwelling (CD) older females in Germany. The secondary aim was to assess whether these females really live independently and autonomously.A total of 1325 CD females 70 years and older living in the area of Erlangen-Nürnberg, Germany were assessed. Sarcopenia as defined by (a) the European Working Group on Sarcopenia in older people (EWGSOP) and (b) the International working group on Sarcopenia (IWGS) combined with obesity defined as (a) BMI >= 30 kg/m(2) (NIH) or (b) body-fat >= 35 % (WHO) was determined. In participants with SO, Barthel Index, care level and social network were retrospectively evaluated via personal interview.Based on anthropometric data, family, education and social status, lifestyle, number and distribution of diseases and medication, the present cohort is representative for the corresponding German population. Sarcopenia prevalence was 4.5 % according to EWGSOP and 3.3 % according to the IWGS criteria. Obesity prevalence in our cohort averaged 19.8 % (BMI, NIH) and 63.8 % (body fat, WHO). The overlap between both factors (i.e. SO) ranged from 0 % (EWGSOP + NIH criteria) to 2.3 % (EWGSOP + WHO criteria). Factors that may represent limited autonomy or independence were very rarely identified in this SO cohort.The prevalence of sarcopenic obesity in the CD (female) German population 70 years + is relatively low. With respect to our second research aim, the hypothesis that SO was incompatible with independent life was rejected. However, the latter finding should be addressed with more dedicated study designs.
EVALuna2:10590

QCT of the femur: Comparison between QCTPro and MIAF Femur - Wang, Ling; Museyko, Oleg; Engelke, Klaus; Brown, Keenan; Cheng, Xiaoguang (2018)
EVALuna2:36394

QCT of the femur: Comparison between QCTPro CTXA and MIAF Femur - Wang, Ling; Museyko, Oleg; Su, Yongbin; Brown, Keenan; Yang, Ruopei; Zhang, Yong; Duanmu, Yangyang; Guo, Zhe; Zhang, Wei; Yan, Dong; Cheng, Xiaoguang; Engelke, Klaus (Bone, 2019)
QCT is commonly employed in research studies and clinical trials to measure BMD at the proximal femur. In this study we compared two analysis software options, QCTPro CTXA and MIAF-Femur, using CT scans of the semi-anthropometric European Proximal Femur Phantom (EPFP) and in vivo data from 130 Chinese elderly men and women aged 60-80 years.
CRIS-Team WoS Importer:2019-02-27

QCT of the proximal femur–which parameters should be measured to discriminate hip fracture? - Museyko, Oleg; Bousson, V.; Adams, J.; Laredo, J. -D.; Engelke, Klaus (Osteoporosis international, 2016)
SUMMARY: For quantitative computed tomography (QCT), most relevant variables to discriminate hip fractures were determined. A multivariate analysis showed that trabecular bone mineral density (BMD) of the trochanter with "cortical" thickness of the neck provided better fracture discrimination than total hip integral BMD. A slice-by-slice analysis of the neck or the inclusion of strength-based parameters did not improve fracture discrimination. INTRODUCTION: For QCT of the proximal femur, a large variety of analysis parameters describing bone mineral density, geometry, or strength has been considered. However, in each given study, generally just a small subset was used. The aim of this study was to start with a comprehensive set and then select a best subset of QCT parameters for discrimination of subjects with and without acute osteoporotic hip fractures. METHODS: The analysis was performed using the population of the European Femur Fracture (EFFECT) study (Bousson et al. J Bone Min Res: Off J Am Soc Bone Min Res 26:881-893, 2011). Fifty-six female control subjects (age 73.2 ± 9.3 years) were compared with 46 female patients (age 80.9 ± 11.1 years) with acute hip fractures. The QCT analysis software MIAF-Femur was used to virtually dissect the proximal femur and analyze more than 1000 parameters, predominantly in the femoral neck. A multivariate best-subset analysis was used to extract the parameters best discriminating hip fractures. All results were adjusted for age, height, and weight differences between the two groups. RESULTS: For the discrimination of all proximal hip fractures as well as for cervical fractures alone, the measurement of neck parameters suffices (area under the curve (AUC) = 0.84). Parameters characterizing bone strength are discriminators of hip fractures; however, in multivariate models, only "cortical" cross-sectional area in the neck center remained as a significant contributor. The combination of one BMD parameter, trabecular BMD of the trochanter, and one geometry parameter, "cortical" thickness of the neck discriminated hip fracture with an AUC value of 0.83 which was significantly better than 0.77 for total femur BMD alone. A comprehensive slice-based analysis of the neck along its axis did not significantly improve hip fracture discrimination. CONCLUSIONS: If QCT of the hip is performed, the analysis should include neck and trochanter. In particular, for fractures of any type, a comprehensive slice-based analysis of the neck along its axis did not significantly improve hip fracture discrimination nor did the inclusion of strength-related parameters other than "cortical" area or thickness. One BMD and one geometry parameter, in this study, the combination of trabecular BMD of the trochanter and of "cortical" thickness of the neck resulted in significant hip fracture discrimination.
EVALuna2:33285

Quantification of hand muscle volume and composition in patients with rheumatoid arthritis, psoriatic arthritis and psoriasis - Friedberger, Andreas; Figueiredo, Camille; Grimm, Alexandra; Oliveira, Isabelle; Bäuerle, Tobias; Rech, Jürgen; Kleyer, Arnd; Simon, David; Uder, Michael; Schett, Georg; Engelke, Klaus (BMC Musculoskeletal Disorders, 2020)
Background Psoriasis (Pso), psoriatic arthritis (PsA) and rheumatoid arthritis (RA) are inflammatory diseases. PsA and RA are characterized by bone and muscle loss. In RA, bone loss has been extensively characterized, but muscle loss has, to the best of our knowledge, not been quantified to date. Methods A random forest based segmentation method was used to analyze hand muscle volume in T1 weighted MRI images of 330 patients suffering from Pso, PsA or RA. In addition, fat volume was quantified using MRI Dixon sequences in a small subset (n = 32). Results Males had a higher relative muscle volume than females (14% for Pso, 11% for PsA, n.s. for RA). Between 40 and 80 years male Pso patients lost 13%, male PsA patients 16%, male RA patients 23% and female PsA patients 30% of their relative muscle volume. After adjustment for age, relative muscle volume in males RA patients was 16% and in female RA patients 9% lower than in Pso patients. In male RA patients relative muscle volume was 13% lower in than in male PsA patients. There was no difference in females. A significant negative correlation (R-2 = 0.18) between relative intramuscular fat content relative hand muscle volume was observed. Conclusion These preliminary data showed that relative hand muscle volume significantly decreased with age in male and female patients with Pso, PsA and RA patients. Independent of age, relative hand muscle volume was significantly smaller in patients with RA compared to the patients with Pso and the difference was twice as large in males compared to females. Also in male but not in female RA patients relative hand muscle volume was significantly smaller than in PsA patients.
CRIS-Team WoS Importer:2020-04-14

Quantitative analysis of skeletal muscle by computed tomography imaging-State of the art - Engelke, Klaus; Museyko, Oleg; Wang, Ling; Laredo, Jean-Denis (Journal of Orthopaedic Translation, 2018)
The radiological assessment of muscle properties-size, mass, density (also termed radiodensity), composition, and adipose tissue infiltration-is fundamental in muscle diseases. More recently, it also became obvious that muscle atrophy, also termed muscle wasting, is caused by or associated with many other diseases or conditions, such as inactivity, malnutrition, chronic obstructive pulmonary disorder, cancer-associated cachexia, diabetes, renal and cardiac failure, and sarcopenia and even potentially with osteoporotic hip fracture. Several techniques have been developed to quantify muscle morphology and function. This review is dedicated to quantitative computed tomography (CT) of skeletal muscle and only includes a brief comparison with magnetic resonance imaging. Strengths and limitations of CT techniques are discussed in detail, including CT scanner calibration, acquisition and reconstruction protocols, and the various quantitative parameters that can be measured with CT, starting from simple volume measures to advanced parameters describing the adipose tissue distribution within muscle. Finally, the use of CT in sarcopenia and cachexia and the relevance of muscle parameters for the assessment of osteoporotic fracture illustrate the application of CT in two emerging areas of medical interest.
EVALuna2:36397

Quantitative and Qualitative Changes of Bone in Psoriasis and Psoriatic Arthritis Patients - Kocijan, Roland; Englbrecht, Matthias; Haschka, Judith; Simon, David; Kleyer, Arnd; Finzel, Stephanie; Kraus, Sebastian; Resch, Heinrich; Muschitz, Christian; Engelke, Klaus; Sticherling, Michael; Rech, Jürgen; et al. (Journal of Bone and Mineral Research, 2015)
Psoriatic arthritis (PsA) is a chronic inflammatory disease characterized by periarticular bone loss and new bone formation. Current data regarding systemic bone loss and bone mineral density (BMD) in PsA are conflicting. The aim of this study was to evaluate bone microstructure and volumetric BMD (vBMD) in patients with PsA and psoriasis. We performed HR-pQCT scans at the ultradistal and periarticular radius in 50 PsA patients, 30 psoriasis patients, and 70 healthy, age- and sex-related controls assessing trabecular bone volume (BV/TV), trabecular number (Tb.N), inhomogeneity of the trabecular network, cortical thickness (Ct.Th), and cortical porosity (Ct.Po), as well as vBMD. Trabecular BMD (Tb.BMD, p = 0.021, 12.0%), BV/TV (p = 0.020, -11.9%), and Tb.N (p = 0.035, 7.1%) were significantly decreased at the ultradistal radius and the periarticular radius in PsA patients compared to controls. In contrast, bone architecture of the ultradistal radius and periarticular radius was similar in patients with psoriasis and healthy controls. Duration of skin disease was associated with low BV/TV and Tb.N in patients with PsA. These data suggest that trabecular BMD and bone microstructure are decreased in PsA patients. The observation that duration of skin disease determines bone loss in PsA supports the concept of subclinical musculoskeletal disease in psoriasis patients. © 2015 American Society for Bone and Mineral Research.
EVALuna2:10104

QUANTITATIVE ASSESSMENT AND ANALYSIS OF HAND MUSCLE VOLUME - Friedberger, Andreas; Figueiredo, C.; Museyko, Oleg; Grimm, Alexandra; D'Oliveira, I.; Bäuerle, Tobias; Rech, Jürgen; Chaudry, Oliver; Uder, Michael; Schett, Georg; Engelke, Klaus (2017)
EVALuna2:14726

Quantitative Computed Tomography-Current Status and New Developments - Engelke, Klaus (Journal of Clinical Densitometry, 2017)
This review focuses on new developments and current controversies in the field of quantitative computed tomography. Recent positions of the International Society for Clinical Densitometry acknowledged the clinical value of quantitative computed tomography of the spine and the hip using clinical whole-body computed tomography (CT) scanners. Opportunistic screening summarizes a number of new approaches describing the dual use of clinical CT scans. For example, CT scans may have been taken for tumor diagnosis but may also be used for the prediction of high or low fracture risks as an additional benefit for the patient. The assessment of the cortical parameters is another topic of current research. In CT images of the spine and the hip, a number of techniques have been developed to determine the thickness, mass, and bone density of the cortex. In higher-spatial resolution peripheral CT images of the radius and tibia obtained from special purpose scanners, 1 focus is the measurement of cortical porosity. Two different approaches, one based on the direct segmentation of the pores and one based on cortical density, will be reviewed.
EVALuna2:33271

Quantitative CT of the knee in the IMI-APPROACH osteoarthritis cohort: Association of bone mineral density with radiographic disease severity, meniscal coverage and meniscal extrusion - Heiß, Rafael; Laredo, Jean Denis; Wirth, Wolfgang; Jansen, Mylène P.; Marijnissen, Anne C.A.; Lafeber, Floris; Lalande, Agnes; Weinans, Harrie H.; Blanco, Francisco J.; Berenbaum, Francis; Kloppenburg, Margreet; Haugen, Ida K.; et al. (Bone, 2023)
Objective: Osteoarthritis (OA) is a highly prevalent chronic condition. The subchondral bone plays an important role in onset and progression of OA making it a potential treatment target for disease-modifying therapeutic approaches. However, little is known about changes of periarticular bone mineral density (BMD) in OA and its relation to meniscal coverage and meniscal extrusion at the knee. Thus, the aim of this study was to describe periarticular BMD in the Applied Public-Private Research enabling OsteoArthritis Clinical Headway (APPROACH) cohort at the knee and to analyze the association with structural disease severity, meniscal coverage and meniscal extrusion. Design: Quantitative CT (QCT), MRI and radiographic examinations were acquired in 275 patients with knee osteoarthritis (OA). QCT was used to assess BMD at the femur and tibia, at the cortical bone plate (Cort) and at the epiphysis at three locations: subchondral (Sub), mid-epiphysis (Mid) and adjacent to the physis (Juxta). BMD was evaluated for the medial and lateral compartment separately and for subregions covered and not covered by the meniscus. Radiographs were used to determine the femorotibial angle and were evaluated according to the Kellgren and Lawrence (KL) system. Meniscal extrusion was assessed from 0 to 3. Results: Mean BMD differed significantly between each anatomic location at both the femur and tibia (p < 0.001) in patients with KL0. Tibial regions assumed to be covered with meniscus in patients with KL0 showed lower BMD at Sub (p < 0.001), equivalent BMD at Mid (p = 0.07) and higher BMD at Juxta (p < 0.001) subregions compared to regions not covered with meniscus. Knees with KL2–4 showed lower Sub (p = 0.03), Mid (p = 0.01) and Juxta (p < 0.05) BMD at the medial femur compared to KL0/1. Meniscal extrusion grade 2 and 3 was associated with greater BMD at the tibial Cort (p < 0.001, p = 0.007). Varus malalignment is associated with significant greater BMD at the medial femur and at the medial tibia at all anatomic locations. Conclusion: BMD within the epiphyses of the tibia and femur decreases with increasing distance from the articular surface. Knees with structural OA (KL2–4) exhibit greater cortical BMD values at the tibia and lower BMD at the femur at the subchondral level and levels beneath compared to KL0/1. BMD at the tibial cortical bone plate is greater in patients with meniscal extrusion grade 2/3.
CRIS-Team Scopus Importer:2023-01-20
Keywords: Bone mineral density; Knee; Multicenter study; Osteoarthritis; Quantitative CT

Quantitative MR-Bildgebung zur Charakterisierung der Skelettmuskulatur - Engelke, Klaus; Chaudry, Oliver; Nagel, Armin Michael (Osteologie, 2020)
This article provides an overview of magnetic resonance imaging (MRI) based methods for the quantification of muscle degeneration. In addition to muscle volume, Dixon imaging can be used to determine the percentage of fat. In addition, there are approaches to visualize and quantify early signs of degeneration via the distribution of the degree of inflammation or the sodium concentration of the muscle. Except for sodium imaging, these methods are routinely used for diagnosis and follow-up in muscle diseases. In osteology and gerontology, the importance of the muscle-bone unit for fracture prediction and frailty in old age is routinely emphasized, but degeneration of the muscles is mainly recorded via extrinsic parameters such as muscle strength and function. Frequently used intrinsic parameters such as DXA lean mass or muscle volume determined with CT or MRI correlate only moderately with extrinsic parameters. However, a more precise characterization of muscle quality should remedy this shortcoming. Appropriate methods are available with CT and MRI, but these must now be used in studies on age-related muscle degeneration, in intervention studies and in studies on fracture risk assessment.
CRIS-Team Scopus Importer:2020-06-16
Keywords: adipose tissue; bone muscle unit; Dixon; inflammation; magnetic resonant imaging; Muscle

Regulatory T cells protect from local and systemic bone destruction in arthritis. - Zaiss, Mario; Frey, Benjamin; Heß, Andreas; Zwerina, Jochen; Luther, Julia; Nimmerjahn, Falk; Engelke, Klaus; Kollias, George; Huenig, Thomas; Schett, Georg; David, Jean-Pierre (Journal of Immunology, 2010)
We previously demonstrated the suppressive effects of regulatory T cells (Treg cells) on osteoclast differentiation in vitro. In this article, we show that blood markers of bone resorption inversely correlate with the amount of circulating Treg cells in healthy controls and rheumatoid arthritis patients, further suggesting that Treg cells may control bone destruction in vivo. Indeed, bone marrow from Foxp3-transgenic (Foxp3tg) mice fully protected human TNF transgenic (hTNFtg) mice from TNF-alpha-induced bone destruction, whereas Foxp3-deficient bone marrow enhanced local and systemic bone loss. The same protective effect was also obtained by treating hTNFtg mice with the CD28 superagonist mAb (CD28 SA), which increased Treg cell numbers. In both models, bone protection by Treg cells was associated with reduced osteoclast numbers, resulting in less bone-resorbing activity. Reduced osteoclast numbers were not caused by an intrinsic defect in osteoclast differentiation because osteoclast precursors from hTNFtg/Foxp3tg chimeras responded normally to M-CSF and receptor activator of NF-kappaB ligand. Although a decrease in the clinical signs of arthritis was observed in Foxp3tg bone marrow-transferred and CD28 SA-treated hTNFtg mice, the bone-protective effect of Treg cells was independent of the suppression of inflammation, as demonstrated by the increased systemic bone density observed in wild-type mice treated with CD28 SA. This work demonstrated that increasing Treg cell numbers improved clinical signs of arthritis and suppressed local and systemic bone destruction. Thus, enhancing the activity of Treg cells would be beneficial for the treatment of inflammation-induced bone loss observed in rheumatoid arthritis.

Reliability and change in erosion measurements by high-resolution peripheral quantitative computed tomography in a longitudinal dataset of rheumatoid arthritis patients - Finzel, Stephanie; Manske, Sarah L.; Barnabe, Cheryl C.M.; Burghardt, Andrew J.; Marotte, Hubert; Scharmga, Andrea; Hauge, Ellen Margrethe; Chapurlat, Roland; Engelke, Klaus; Li, Xiaojuan; van Teeffelen, Bente C.J.; Conaghan, Philip G.; et al. (Journal of Rheumatology, 2021)
Objective. The aim of this multireader exercise was to assess the reliability and change over time of erosion measurements in patients with rheumatoid arthritis (RA) using high-resolution peripheral quantitative computed tomography (HR-pQCT). Methods. HR-pQCT scans of 23 patients with RA were assessed at baseline and 12 months. Four experienced readers examined the dorsal, palmar, radial, and ulnar surfaces of the metacarpal head (MH) and phalangeal base (PB) of the second and third digits, blinded to time order. In total, 368 surfaces (23 patients' 16 surfaces) were evaluated per timepoint to characterize cortical breaks as pathological (erosion) or physiological, and to quantify erosion width and depth. Reliability was evaluated by intraclass correlation coefficients (ICC), percentage agreement, and Light k; change over time was defined by means ± SD of erosion numbers and dimensions. Results. ICC for the mean measurements of width and depth of the pathological breaks ranged between 0.819-0.883, and 0.771-0.907, respectively. Most physiological cortical breaks were found at the palmar PB, whereas most pathological cortical breaks were located at the radial MH. There was a significant increase in both the numbers and the dimensions of erosions between baseline and follow-up (P = 0.0001 for erosion numbers, width, and depth in axial plane; P = 0.001 for depth in perpendicular plane). Conclusion. This exercise confirmed good reliability of HR-pQCT erosion measurements and their ability to detect change over time.
CRIS-Team Scopus Importer:2021-04-02
Keywords: Computed tomography; Metacarpophalangeal joint; Outcomes; Rheumatoid arthritis

Reliability and Change in Erosion Measurements by High-resolution Peripheral Quantitative Computed Tomography in a Longitudinal Dataset of Rheumatoid Arthritis Patients. - Finzel, Stephanie; Manske, Sarah L.; Barnabe, Cheryl C. M.; Burghardt, Andrew J.; Marotte, Hubert; Scharmga, Andrea; Hauge, Ellen-Margrethe; Chapurlat, Roland; Engelke, Klaus; Li, Xiaojuan; Van Teeffelen, Bente C. J.; Conaghan, Philip G.; et al. (Journal of Rheumatology, 2021)
OBJECTIVE: The aim of this multireader exercise was to assess the reliability and change over time of erosion measurements in patients with rheumatoid arthritis (RA) using high-resolution peripheral quantitative computed tomography (HR-pQCT). METHODS: HR-pQCT scans of 23 patients with RA were assessed at baseline and 12 months. Four experienced readers examined the dorsal, palmar, radial, and ulnar surfaces of the metacarpal head (MH) and phalangeal base (PB) of the second and third digits, blinded to time order. In total, 368 surfaces (23 patients´ 16 surfaces) were evaluated per timepoint to characterize cortical breaks as pathological (erosion) or physiological, and to quantify erosion width and depth. Reliability was evaluated by intraclass correlation coefficients (ICC), percentage agreement, and Light k; change over time was defined by means ± SD of erosion numbers and dimensions. RESULTS: ICC for the mean measurements of width and depth of the pathological breaks ranged between 0.819-0.883, and 0.771-0.907, respectively. Most physiological cortical breaks were found at the palmar PB, whereas most pathological cortical breaks were located at the radial MH. There was a significant increase in both the numbers and the dimensions of erosions between baseline and follow-up (P = 0.0001 for erosion numbers, width, and depth in axial plane; P = 0.001 for depth in perpendicular plane). CONCLUSION: This exercise confirmed good reliability of HR-pQCT erosion measurements and their ability to detect change over time.
EVALuna2:465997

Repair of bone erosions in rheumatoid arthritis treated with tumour necrosis factor inhibitors is based on bone apposition at the base of the erosion - Finzel, Stephanie; Rech, Jürgen; Schmidt, Sarah; Engelke, Klaus; Englbrecht, Matthias; Stach, Christian; Schett, Georg (Annals of the Rheumatic Diseases, 2011)
Objectives: To investigate whether bone erosions in patients with rheumatoid arthritis (RA) show evidence of repair. Methods: 127 erosions were identified in metacarpophalangeal joints 2-4 of the right hands of 30 RA patients treated with tumour necrosis factor inhibitors (TNFi) and 21 sex, age and disease activity-matched patients treated with methotrexate. All erosions were assessed for their exact maximal width and depth by high-resolution μCT imaging at baseline and after 1 year. Results: All erosions detected at baseline could be visualised at follow-up after 1 year. At baseline, the mean width of bone erosions in the TNFi group was 2.0 mm;their mean depth was 2.3 mm, which was not significantly different from the methotrexate-treated group (width 2.4 mm;depth 2.4 mm). Mean depth of erosions significantly decreased after 1 year of treatment with TNFi (-0.1 mm; p=0.016), whereas their width remained unchanged. In contrast, mean depth and width of erosive lesions increased in the methotrexate-treated group. The reduction in the depth of lesions was confined to erosions showing evidence of sclerosis at the base of the lesion. Moreover, deeper lesions in the TNFi group were particularly prone to repair (-0.4 mm;p=0.02) compared with more shallow lesions. Conclusions: Bone erosions in RA patients treated with TNFi show evidence of limited repair in contrast to bone erosions in patients treated with methotrexate. Repair is associated with a decrease in the depth of lesions and sclerosis at the bases of the lesions. Repair thus emerges from the endosteal rather than periosteal bone compartment and probably involves the bone marrow.
CRIS-Team Scopus Importer:2021-02-03

Repeatability of Dixon magnetic resonance imaging and magnetic resonance spectroscopy for quantitative muscle fat assessments in the thigh - Grimm, Alexandra; Meyer, Heiko; Nickel, Marcel D.; Nittka, Mathias; Raithel, Esther; Chaudry, Oliver; Friedberger, Andreas; Uder, Michael; Kemmler, Wolfgang; Engelke, Klaus; Quick, Harald H. (Journal of Cachexia, Sarcopenia and Muscle, 2018)
BACKGROUND: Changes in muscle fat composition as for example observed in sarcopenia or muscular dystrophy affect physical performance and muscular function, like strength and power. The purpose of the present study is to measure the repeatability of Dixon magnetic resonance imaging (MRI) for assessing muscle volume and fat in the thigh. Furthermore, repeatability of magnetic resonance spectroscopy (MRS) for assessing muscle fat is determined. METHODS: A prototype 6-point Dixon MRI method was used to measure muscle volume and muscle proton density fat fraction (PDFF) in the left thigh. PDFF was measured in musculus semitendinosus of the left thigh with a T2-corrected multi-echo MRS method. For the determination of short-term repeatability (consecutive examinations), the root mean square coefficients of variation of Dixon MRI and MRS data of 23 young and healthy (29 ± 5 years) and 24 elderly men with sarcopenia (78 ± 5 years) were calculated. For the estimation of the long-term repeatability (13 weeks between examinations), the root mean square coefficients of variation of MRI data of seven young and healthy (31 ± 7 years) and 23 elderly sarcopenic men (76 ± 5 years) were calculated. Long-term repeatability of MRS was not determined. RESULTS: Short-term errors of Dixon MRI volume measurement were between 1.2% and 1.5%, between 2.1% and 1.6% for Dixon MRI PDFF measurement, and between 9.0% and 15.3% for MRS. Because of the high short-term repeatability errors of MRS, long-term errors were not determined. Long-term errors of MRI volume measurement were between 1.9% and 4.0% and of Dixon MRI PDFF measurement between 2.1% and 4.2%. CONCLUSIONS: The high degree of repeatability of volume and PDFF Dixon MRI supports its use to predict future mobility impairment and measures the success of therapeutic interventions, for example, in sarcopenia in aging populations and muscular dystrophy. Because of possible inhomogeneity of fat infiltration in muscle tissue, the application of MRS for PDFF measurements in muscle is more problematic because this may result in high repeatability errors. In addition, the tissue composition within the MRS voxel may not be representative for the whole muscle.
EVALuna2:36107

Reproducible Segmentation of the Fascia and Quantification of Muscle Fat Fraction in the Thigh - Chaudry, Oliver; Friedberger, Andreas; Grimm, Alexandra; Kemmler, Wolfgang; Engelke, Klaus (JOURNAL OF BONE AND MINERAL RESEARCH, 2019)
CRIS-Team WoS Importer:2020-02-07

Response to the editor of JBMR regarding the letter related to "Opportunistic screening with CT: comparison of phantomless BMD calibration methods". - Bartenschlager, Stefan; Cavallaro, Alexander Josef; Pogarell, Tobias; Chaudry, Oliver; Uder, Michael; Khosla, Sundeep; Schett, Georg; Engelke, Klaus (Journal of Bone and Mineral Research, 2024)
EVALuna2:570800

Rheumatoid arthritis is characterized by early changes of the cortical micro-channel (CoMiC) system in the bare area of the joints - Werner, David; Simon, David; Englbrecht, Matthias; Stemmler, Fabian; Simon, Christoph; Berlin, Andreas; Haschka, Judith; Renner, Nina; Buder, Thomas; Engelke, Klaus; Hueber, Axel; Rech, Jürgen; et al. (Arthritis and Rheumatology, 2017)
To characterize the specific structural properties of the erosion-prone bare area of the human joint and to search for early microstructural changes in this region during rheumatoid arthritis Methods: An initial cadaveric study was used for exact localization of the bare area of the metacarpal heads, detection of cortical micro-channels (CoMiCs) in this region by high-resolution peripheral computed tomography (HR-pQCT) and, after anatomical dissection, their validation by micro-computed tomography (?CT). In the second part, number and distribution of CoMiCs were analyzed in 105 healthy individuals and 107 RA patients with similar sex and age distribution.HR-pQCT investigation combined with adaptive thresholding allowed detection of CoMiCs in the bare area of cadaveric joints. Their existence in the bare area was additionally validated by ?CT. In healthy individuals, the number of CoMiCs increased with age. RA patients showed significantly (p<0.001) more CoMiCs (112.9±54.7/joint) than healthy individuals (75.2±41.9/joint) with 20-49 years old RA patients exhibiting similar CoMiC numbers as observed in over 65 year old healthy individuals. Importantly, CoMiCs were found in RA patients already very early in their disease course with enrichment in the erosion-prone radial side of the joint.CoMiCs represent a new form of structural change in the joints of patients with RA. While CoMiCs increase with age, RA patients develop such changes much earlier in life and already at the onset of the disease. CoMiCs therefore represent an interesting new opportunity to assess structural changes in RA. This article is protected by copyright. All rights reserved.
EVALuna2:13409

Riskfactors of Osteoporosis - Baum, Erika; Rintelen, Bernhard; Siggelkow, Heide; Engelke, Klaus; Glueer, Claus-C.; Thomasius, Friederike (Osteologie, 2023)
Aim In the context of the development of the guideline update on prophylaxis, diagnosis and therapy of osteoporosis in postmeopausal women and in men for German-speaking countries, the osteoporosis-typical fracture risk should be quantified as accurately as possible and according to new data.Methods Based on a systematic literature search, the author group identified risk factors for typical osteoporotic fractures-in this case, explicitly hip fractures and vertebral fractures. The results were pooled, evaluated, and prioritized with respect to their relevance for risk calculation, which in the future should be possible electronically in the form of a risk calculator.Results Particularly strong risk factors for hip fracture include previous fractures of various locations, as well as type 1 diabetes, glucocorticoid therapy, and some neurologic diseases. In persons older than 75 years, a timed-up-and-go test>15 seconds reflects very well the increased risk for several conditions that correlate with an increased propensity to fall. After fractures, the risk of further fractures in the following year is greatly increased, so the imminent fracture risk must also be considered. Here we report the current status of the fracture risk assessment and inclusion in the guideline, which reflects work in progress.Conclusion Due to the complexity of the individual influencing factors, risk estimation is best achieved with a validated, electronically available risk calculator. Interim results are presented here, and a paper version will also be provided in the guideline update for the transition phase.
CRIS-Team WoS Importer:2023-05-19

Risk prediction of second hip fracture by bone and muscle density of the hip varies with time after first hip fracture: A prospective cohort study - Wang, Ling; Yang, Minghui; Ge, Yufeng; Liu, Yandong; Wang, Gang; Su, Yongbin; Guo, Zhe; Yin, Lu; Huang, Pengju; Geng, Jian; Blake, Glen M.; He, Bo; et al. (Bone Reports, 2024)
Purpose: Predictors of ‘imminent’ risk of second hip fracture are unknown. The aims of the study were to explore strength of hip areal bone mineral density (aBMD), and muscle area and density for predicting second hip fracture at different time intervals. Methods: Data of the Chinese Second Hip Fracture Evaluation were analyzed, a longitudinal study to evaluate the risk of second hip fracture (of the contralateral hip) by using CT images obtained immediately after first hip fracture. Muscle cross-sectional area and density were measured of the gluteus maximus (G.MaxM) and gluteus medius and minimus (G.Med/MinM) and aBMD of the proximal femur at the contralateral unfractured side. Patients were followed up for a median time of 4.5 years. Separate Cox models were used to predict second hip fracture risk at different time intervals after first event adjusted for age, sex, BMI and diabetes. Results: The mean age of subjects with imminent (within 1st or 2nd year) second hip fracture was 79.80 ± 5.16 and 81.56 ± 3.64 years. In the 1st year after the first hip fracture, femoral neck (FN) aBMD predicted second hip fracture (HR 5.88; 95 % CI, 1.32–26.09). In the remaining years of follow-up after 2nd year, muscle density predicted second hip fracture (G.MaxM HR 2.13; 95 % CI, 1.25–3.65,G.Med/MinM HR 2.10; 95 % CI, 1.32–3.34). Conclusions: Our results show that femoral neck aBMD is an important predictor for second hip fracture within the first year and therefore suggest supports the importance concept of early and rapid-acting bone-active drugs to increase hip BMD. In addition, the importance of muscle density predicting second hip fracture after the second year suggest post hip fracture rehabilitation and exercise programs could also be important to reduce muscle fatty infiltration.
CRIS-Team Scopus Importer:2024-01-05
Keywords: Bone mineral density; Muscle density; Risk predictor; Second hip fracture

Romosozumab (sclerostin monoclonal antibody) versus teriparatide in postmenopausal women with osteoporosis transitioning from oral bisphosphonate therapy: a randomised, open-label, phase 3 trial - Langdahl, Bente L.; Libanati, Cesar; Crittenden, Daria B.; Bolognese, Michael A.; Brown, Jacques P.; Daizadeh, Nadia S.; Dokoupilova, Eva; Engelke, Klaus; Finkelstein, Joel S.; Genant, Harry K.; Goemaere, Stefan; Hyldstrup, Lars; et al. (Lancet, 2017)
BACKGROUND: Previous bisphosphonate treatment attenuates the bone-forming effect of teriparatide. We compared the effects of 12 months of romosozumab (AMG 785), a sclerostin monoclonal antibody, versus teriparatide on bone mineral density (BMD) in women with postmenopausal osteoporosis transitioning from bisphosphonate therapy. METHODS: This randomised, phase 3, open-label, active-controlled study was done at 46 sites in North America, Latin America, and Europe. We enrolled women (aged ≥55 to ≤90 years) with postmenopausal osteoporosis who had taken an oral bisphosphonate for at least 3 years before screening and alendronate the year before screening; an areal BMD T score of -2·5 or lower at the total hip, femoral neck, or lumbar spine; and a history of fracture. Patients were randomly assigned (1:1) via an interactive voice response system to receive subcutaneous romosozumab (210 mg once monthly) or subcutaneous teriparatide (20 μg once daily). The primary endpoint was percentage change from baseline in areal BMD by dual-energy x-ray absorptiometry at the total hip through month 12 (mean of months 6 and 12), which used a linear mixed effects model for repeated measures and represented the mean treatment effect at months 6 and 12. All randomised patients with a baseline measurement and at least one post-baseline measurement were included in the efficacy analysis. This trial is registered with ClinicalTrials.gov, number NCT01796301. FINDINGS: Between Jan 31, 2013, and April 29, 2014, 436 patients were randomly assigned to romosozumab (n=218) or teriparatide (n=218). 206 patients in the romosozumab group and 209 in the teriparatide group were included in the primary efficacy analysis. Through 12 months, the mean percentage change from baseline in total hip areal BMD was 2·6% (95% CI 2·2 to 3·0) in the romosozumab group and -0·6% (-1·0 to -0·2) in the teriparatide group; difference 3·2% (95% CI 2·7 to 3·8; p<0·0001). The frequency of adverse events was generally balanced between treatment groups. The most frequently reported adverse events were nasopharyngitis (28 [13%] of 218 in the romosozumab group vs 22 [10%] of 214 in the teriparatide group), hypercalcaemia (two [<1%] vs 22 [10%]), and arthralgia (22 [10%] vs 13 [6%]). Serious adverse events were reported in 17 (8%) patients on romosozumab and in 23 (11%) on teriparatide; none were judged treatment related. There were six (3%) patients in the romosozumab group compared with 12 (6%) in the teriparatide group with adverse events leading to investigational product withdrawal. INTERPRETATION: Transition to a bone-forming agent is common practice in patients treated with bisphosphonates, such as those who fracture while on therapy. In such patients, romosozumab led to gains in hip BMD that were not observed with teriparatide. These data could inform clinical decisions for patients at high risk of fracture. FUNDING: Amgen, Astellas, and UCB Pharma.
EVALuna2:33272

Segmentation and quantification of bone erosions in high-resolution peripheral quantitative computed tomography datasets of the metacarpophalangeal joints of patients with rheumatoid arthritis - Toepfer, Dominique; Finzel, Stephanie; Museyko, Oleg; Schett, Georg; Engelke, Klaus (Rheumatology, 2014)
Objective. To develop a precise three-dimensional (3D) segmentation technique for bone erosions in high-resolution peripheral quantitative CT (HR-pQCT) datasets to measure their volume, surface area and shape parameters. Assessment of bone erosions in patients with RA is important for diagnosis and evaluation of treatment efficacy. HR-pQCT allows quantifying periarticular bone loss in arthritis. Methods. HR-pQCT scans with a spatial resolution of about 120 µm of the second to fourth metacarpophalangeal joints were acquired in patients with RA. Erosions were identified by placing a seed point in each of them. After applying 3D segmentation, the volume, surface area and sphericity of erosions were calculated. Results were compared with an approximation method using manual measurements. Intra- and interoperator precision analysis was performed for both the 3D segmentation and the manual technique. Results. Forty-three erosions were assessed in 18 datasets. Intra- and interoperator precisions (RMSCV/RMSSD) for erosion volume were 5.66%/0.49 mm(3) and 7.76%/0.76 mm(3), respectively. The correlation between manual measurements and their simulation using segmentation volumes was r = 0.87. Precision errors for the manual method were 15.39% and 0.36 mm(3), respectively. Conclusion. We developed a new precise 3D segmentation technique for quantification of bone erosions in HR-pQCT datasets that correlates to the volume, shape and surface area of the erosion. The technique allows fast and effective measurement of the erosion size and could therefore be helpful for rapid and quantitative assessment of erosion size.
EVALuna2:10057

Segmentation of the fascia lata and reproducible quantification of intermuscular adipose tissue (IMAT) of the thigh - Chaudry, Oliver; Friedberger, Andreas; Grimm, Alexandra; Uder, Michael; Nagel, Armin Michael; Kemmler, Wolfgang; Engelke, Klaus (Magnetic Resonance Materials in Physics Biology and Medicine, 2020)
Objective: To develop a precise semi-automated segmentation of the fascia lata (FL) of the thigh to quantify IMAT volume in T1w MR images and fat fraction (FF) in Dixon MR images. Materials and methods: A multi-step segmentation approach was developed to identify fibrous structures of the FL and combining them into a closed 3D surface. 23 healthy young men with low and 50 elderly sarcopenic men with moderate levels of IMAT were measured by T1w and 6pt Dixon MRI at 3T. 20 datasets were used to determine reanalysis precision errors. IMAT volume was compared using the new FL segmentation versus an easier to segment but less accurate, tightly fitting envelope of the thigh muscle ensemble. Results: The segmentation was successfully applied to all 73 datasets and took about 7 min per 28 slices. In particular, in elderly subjects, it includes a large amount of adipose tissue below the FL typically not accounted for in other segmentation approaches. Inter- and intra-operator RMS-CVs were 0.33% and 0.14%, respectively, for IMAT volume and 0.04% and 0.02%, respectively, for FFMT. Discussion: The FL segmentation is an important step to quantify IMAT with high precision and may be useful to investigate effects of aging and treatment on changes of IMAT and FF. ClinicalTrials.gov identifier NCT2857660, August 5, 2016. Trial registration: ClinicalTrials.gov identifier NCT2857660, August 5, 2016.
CRIS-Team Scopus Importer:2020-08-14
Keywords: Adipose tissue; Fascia lata; MRI

Segmentation of the Fascia Lata in Magnetic Resonance Images of the Thigh: Comparison of an Unsupervised Technique with a U-Net in 2D and Patch-wise 3D - Louise P, Lis J.; Engelke, Klaus; Chaudry, Oliver (Informatik aktuell, 2021)
To quantify muscle properties in the thigh, the segmentation of the fascia lata is crucial. For this purpose, the U-Net architecture was implemented and compared for 2D images and patched 3D image stacks in magnetic resonance images (MRI). The training data consisted of T1 MRI data sets from elderly men. To test the performance of the models, they were applied on other data sets of different age groups and gender. The U-Net approaches were superior to an unsupervised semiautomatic method and reduced post-processing time.
CRIS-Team Scopus Importer:2021-04-19

Structural effects of whole body electromyostimulation on knee osteoarthritis: the EMSOAT Study - Roemer, Frank; Kast, Stephanie; Kemmler, Wolfgang; Collins, Jamie E.; Engelke, Klaus; Guermazi, Ali; Uder, Michael; von Stengel, Simon (Skeletal Radiology, 2025)
Objective: Whole-body electromyostimulation (WB-EMS) might be an alternative option to conventional strength training for patients with knee osteoarthritis (OA). Our aim was to compare structural changes of knee OA between patients treated with WB-EMS and a control group (CG) treated with a standard of care approach. Material and methods: Seventy-two overweight participants with symptomatic knee OA were assigned to either WB-EMS or CG. MRIs were acquired at baseline and 7 months using a 3 T system. MRIs were read according to the MRI Osteoarthritis Knee Score (MOAKS) instrument. Between-group differences in regard to change in cartilage, bone marrow lesions (BMLs), osteophytes, meniscus damage and extrusion, and markers of inflammation were analyzed using Fisher’s Exact and Wilcoxon Rank Sum tests. Results: Fewer knees in the WB-EMS groups showed cartilage worsening compared to the CG (18% vs. 40%, p = 0.046). There were fewer knees in the WB-EMS group showing an increase in BML size score of ≥ 1 (30% vs 46%, p = 0.43). Regarding prevalent BMLs that showed improvement, no change, or worsening, no differences were seen (p = 0.56). Little osteophyte and meniscal changes were observed during the observational period. Differences regarding change in inflammatory markers were not significant. Conclusion: While there was a difference with fewer subregions showing worsening cartilage damage in the WB-EMS group, no significant differences were observed for change in BMLs, inflammation, osteophytes, and meniscal parameters. The observed improvement in clinical outcome parameters in favor of the WB-EMS group is likely due to other effects than improvement or less worsening of structural changes.
CRIS-Team Scopus Importer:2025-08-01
Keywords: Clinical trial; Knee osteoarthritis; MOAKS; MRI; Whole body electromyostimulation

Systemic and local bone loss in Psoriasis and Psoriatic Arthritis - Kocijan, Roland; Englbrecht, Matthias; Kleyer, Arnd; Haschka, Judith; Simon, David; Finzel, Stephanie; Kraus, Sebastian; Muschitz, Christian; Resch, Heinrich; Engelke, Klaus; Rech, Jürgen; Schett, Georg (2014)
EVALuna2:13062

Technical Methods in the Context of the DVO Guideline - New Developments Messtechnische Verfahren im Kontext der DVO Leitlinie - neue Entwicklungen - Engelke, Klaus; Müller, Dirk; Bühring, Bjoern; Thomasius, Friederike (Osteologie, 2023)
Osteodensitometry, the determination of bone density and biochemical bone remodeling parameters are an integral part of the DVO guideline. This article gives an overview of new studies and new technical developments as far as they are relevant especially in the context of the guideline, i. e. for diagnosis, determination of fracture risk and follow-up. The focus is in particular on those techniques that have directly led to the adaptation of recommendations. Other techniques, such as opportunistic screening of routine CT scans, have not yet found their way into the guideline, but their potential to significantly improve the identification of patients at high risk of fracture seems to justify an overview of these methods in the context of this article.
CRIS-Team Scopus Importer:2023-07-14
Keywords: DVO Leitlinie; DXA; HR-pQCT; Knochendichte und Struktur; messtechnische Verfahren; QCT; VFA

The Authors reply: "Dual energy X-ray absorptiometry: gold standard for muscle mass?" by Scafoglieri et al - Buckinx, Fanny; Landi, Francesco; Cesari, Matteo; Fieding, Roger A.; Visser, Marjolein; Engelke, Klaus; Maggi, Stefania; Dennison, Elaine; Al-Daghri, Nasser M.; Allepaerts, Sophie; Bauer, Jurgen; Bautmans, Ivan; et al. (Journal of Cachexia, Sarcopenia and Muscle, 2018)
EVALuna2:36399

The authors reply: Letter on: "Pitfalls in the measurement of muscle mass: a need for a reference standard" by Clark et al - Buckinx, Fanny; Landi, Francesco; Cesari, Matteo; Fieding, Roger A.; Visser, Marjolein; Engelke, Klaus; Maggi, Stefania; Dennison, Elaine; Al-Daghri, Nasser M.; Allepaerts, Sophie; Bauer, Jurgen; Bautmans, Ivan; et al. (Journal of Cachexia, Sarcopenia and Muscle, 2018)
However, semantics aside, we think that DXA can indeed serve as a reference standard for measuring muscle mass. Obviously, CT and MRI are advanced techniques that can and have been used to obtain important information such as muscle size/volume and more recently amount and distribution of intra- and intermuscular adipose tissue. Also individual muscles can be assessed separately. However, with respect to muscle mass, the comparison of DXA with CT/MRI is rather difficult because DXA and QCT/MRI measure different physical parameters.
EVALuna2:36393

The clinical application of high-resolution peripheral computed tomography (HR-pQCT) in adults: state of the art and future directions - Van Den Bergh, J. P.; Szulc, P.; Cheung, A. M.; Bouxsein, M.; Engelke, Klaus; Chapurlat, R. (Osteoporosis international, 2021)
High-resolution peripheral computed tomography (HR-pQCT) was developed to image bone microarchitecture in vivo at peripheral skeletal sites. Since the introduction of HR-pQCT in 2005, clinical research to gain insight into pathophysiology of skeletal fragility and to improve prediction of fractures has grown. Meanwhile, the second-generation HR-pQCT device has been introduced, allowing novel applications such as hand joint imaging, assessment of subchondral bone and cartilage thickness in the knee, and distal radius fracture healing. This article provides an overview of the current clinical applications and guidance on interpretation of results, as well as future directions. Specifically, we provide an overview of (1) the differences and reference data for HR-pQCT variables by age, sex, and race/ethnicity; (2) fracture risk prediction using HR-pQCT; (3) the ability to monitor response of anti-osteoporosis therapy with HR-pQCT; (4) the use of HR-pQCT in patients with metabolic bone disorders and diseases leading to secondary osteoporosis; and (5) novel applications of HR-pQCT imaging. Finally, we summarize the status of the application of HR-pQCT in clinical practice and discuss future directions. From the clinical perspective, there are both challenges and opportunities for more widespread use of HR-pQCT. Assessment of bone microarchitecture by HR-pQCT improves fracture prediction in mostly normal or osteopenic elderly subjects beyond DXA of the hip, but the added value is marginal. The prospects of HR-pQCT in clinical practice need further study with respect to medication effects, metabolic bone disorders, rare bone diseases, and other applications such as hand joint imaging and fracture healing. The mostly unexplored potential may be the differentiation of patients with only moderately low BMD but severe microstructural deterioration, which would have important implications for the decision on therapeutical interventions.
CRIS-Team WoS Importer:2021-05-28

The Concept of the DVO Fracture Risk Calculator - Glueer, Claus-C.; Engelke, Klaus; Thomasius, Friederike (Osteologie, 2023)
The estimation of fracture risk is a core task in the care of patients at risk of osteoporosis. Various risk calculators have been developed for this purpose. Despite this, there is a considerable treatment gap of osteoporosis patients, which is also due to insufficient identification of those affected. The DVO Fracture Risk Calculator was developed to improve this situation. In this contribution, the shortcomings of previous risk calculators are listed in order to derive the concept of the DVO Fracture Risk Calculator. Core aspects comprise i) a broad Casefinding strategy via 33 evidence based validated fracture risk factors, ii) the focus on hip and vertebral fracture risk, iii) a calculation of the 3-year fracture risk, optionally with 1-year data in case of high imminent fracture risk, along with iv) bone densitometry at lumbar spine and proximal femur. The risk assessment is based on German reference data. The fracture risk is based on the risk of individuals who do not have any of the clinical risk factors assessed and it is calculated via a sex-specific multiplicative model that takes into account age, the relative risks of the two strongest clinical risk factors and bone densitometry results. The goal is to implement this as an app that will be made available free of charge to DVO osteologists. Until this app is certified, a simplified model in tabular form will be offered for a transitional period. Risk calculators can only support medical expertise of physicians, not replace it, but the DVO Fracture Risk Calculator will hopefully help to reduce the diagnostic gap of osteoporosis patients by helping to identify at-risk patients in an effective way.
CRIS-Team WoS Importer:2023-05-26

The effect of ageing on fat infiltration of thigh and paraspinal muscles in men - Engelke, Klaus; Ghasemikaram, Mansour; Chaudry, Oliver; Uder, Michael; Nagel, Armin Michael; Jakob, Franz; Kemmler, Wolfgang (Aging Clinical and Experimental Research, 2022)
Background Myosteatosis, skeletal muscle fat infiltration, is associated with inflammation and fibrosis. The age-related increase of myosteatosis is an important characteristic of sarcopenia and contributes to fragility. Aims To investigate the impact of healthy aging on intermuscular adipose tissue (IMAT) and muscle fat fraction (FF) in the thigh and the paraspinal muscles in males. Methods In 54 healthy males (age 20-70), all active hobby golfers, magnetic resonance imaging was performed to determine volume of IMAT, volume of muscle tissue (MT) and of percentage of FF. Results Between ages 20-70, at the thigh, IMAT/MT volume and MT FF increased annually by 2.9% and 1.3%, respectively. At the psoas IMAT/Psoas volume did not change with age. MT FF increased by 1.5% annually. At the erector spinae IMAT/Erector volume decreased by 0.3% and MT FF increased by 2.8% annually. Discussion With increasing age, in males, thigh muscle atrophied, muscle tissue was partly replaced by adipose tissue and remaining muscle tissue also contained more fat. Similar effects were observed in the erector spinae. The psoas muscle did not atrophy, although MT FF also increased with age. Overall correlations with age were weak to moderate with higher correlations observed in the paraspinal muscles. Conclusions Age-related increases of muscle fat infiltration were observed in the thigh and in the spine. Muscle atrophy did not occur in the psoas. In cross-sectional studies, an adjustment of volumetric parameters by muscle volume is advisable when comparing age-dependent results.
CRIS-Team WoS Importer:2022-06-10
Keywords: MRI; Thigh; Erector spinae; Psoas; IMAT; Muscle fat fraction

The effect of in situ/in vitro three-dimensional quantitative computed tomography image voxel size on the finite element model of human vertebral cancellous bone - Lu, Yongtao; Engelke, Klaus; Glueer, Claus-C; Morlock, Michael M.; Huber, Gerd (Proceedings of the Institution of Mechanical Engineers Part H-Journal of Engineering in Medicine, 2014)
Quantitative computed tomography-based finite element modeling technique is a promising clinical tool for the prediction of bone strength. However, quantitative computed tomography-based finite element models were created from image datasets with different image voxel sizes. The aim of this study was to investigate whether there is an influence of image voxel size on the finite element models. In all 12 thoracolumbar vertebrae were scanned prior to autopsy (in situ) using two different quantitative computed tomography scan protocols, which resulted in image datasets with two different voxel sizes (0.29 × 0.29 × 1.3 mm(3) vs 0.18 × 0.18 × 0.6 mm(3)). Eight of them were scanned after autopsy (in vitro) and the datasets were reconstructed with two voxel sizes (0.32 × 0.32 × 0.6 mm(3) vs. 0.18 × 0.18 × 0.3 mm(3)). Finite element models with cuboid volume of interest extracted from the vertebral cancellous part were created and inhomogeneous bilinear bone properties were defined. Axial compression was simulated. No effect of voxel size was detected on the apparent bone mineral density for both the in situ and in vitro cases. However, the apparent modulus and yield strength showed significant differences in the two voxel size group pairs (in situ and in vitro). In conclusion, the image voxel size may have to be considered when the finite element voxel modeling technique is used in clinical applications.
EVALuna2:10097

The Effect of the Cathepsin K Inhibitor ONO-5334 on Trabecular and Cortical Bone in Postmenopausal Osteoporosis: The OCEAN Study - Engelke, Klaus; Nagase, Shinichi; Fuerst, Thomas; Small, Maria; Kuwayama, Tomohiro; Deacon, Stephen; Eastell, Richard; Genant, Harry K. (Journal of Bone and Mineral Research, 2014)
ONO-5334 (Ono Pharmaceutical Co., Ltd., Osaka, Japan) inhibits cathepsin K and has been shown to increase areal bone mineral density (BMD) at the hip and spine in postmenopausal osteoporosis. Quantitative computed tomography (QCT) allows the study of the cortical and trabecular bone separately and provides structural information such as cortical thickness. We investigated the impact of 2 years of cathepsin K inhibition on these different bone compartments with ONO-5334. The clinical study was a randomized, double-blind, placebo, and active controlled parallel group study conducted in 13 centers in six European countries. The original study period of 12 months was extended by another 12 months. A total of 147 subjects (age 55-75 years) of the QCT substudy who participated in the extension period were included. Subjects had been randomized into one of five treatment arms: placebo; ONO-5334 50 mg twice per day (BID); ONO-5334 100 mg once daily (QD); ONO-5334 300 mg QD; or alendronate 70 mg once weekly (QW). QCT was obtained to evaluate bone structure at the lumbar spine and proximal femur. After 24 months ONO-5334 showed statistically significant increases versus placebo for integral, trabecular, and cortical BMD at the spine and the hip (for ONO-5334 300 mg QD, BMD increases were 10.5%, 7.1%, and 13.4% for integral, cortical, and trabecular BMD at the spine, respectively, and 6.2%, 3.4%, and 14.6% for integral, cortical, and trabecular total femur BMD, respectively). Changes in cortical and trabecular BMD in the spine and hip were similar for alendronate as for ONO-5334. Integral volume did not demonstrate statistically significant changes under ONO-5334 treatment, thus there was no evidence of periosteal apposition, neither at the spine nor at the femur. Cortical thickness changes were not statistically significant for ONO-5334 in the spine and hip, with exception of a 2.1% increase after month 24 in the intertrochanter for ONO-5334 300 mg QD. Over 2 years ONO-5334 showed a statistically significant and persistent increase of trabecular and integral BMD at the spine and the hip. Cortical BMD also progressively increased but at a lower rate. Changes in bone size and of periosteal apposition were not observed. © 2014 American Society for Bone and Mineral Research.
EVALuna2:10070

THE PHYSIOLOGICAL FINGER JOINT ARCHITECTURE - AGE-RELATED INCREASE OF EROSIONS AND OSTEOPHYTES IN THE JOINTS OF HEALTHY INDIVIDUALS - Simon, David; Berlin, Andreas; Tascilar, Koray; Bayat, Sara; Engelke, Klaus; Rech, Jürgen; Figuereido, Camille; Hueber, Axel; Schett, Georg; Kleyer, Arnd (ANNALS OF THE RHEUMATIC DISEASES, 2019)
CRIS-Team WoS Importer:2019-07-12

The Relationship Between Subclinical Inflammation and Bone Damage in Patients with Rheumatoid Arthritis Using Multimodality Imaging - Brunet, Scott; Salat, Peter; Hazlewood, Glen; Engelke, Klaus; Barnabe, Cheryl; Manske, Sarah (ARTHRITIS & RHEUMATOLOGY, 2019)
CRIS-Team WoS Importer:2020-02-07

THREE DIMENSIONAL COMPARISONS BETWEEN QCTPRO AND MIAF FEMUR FOR THE PROXIMAL FEMUR MEASUREMENTS - Wang, L.; Museyko, Oleg; Brown, K.; Cheng, X.; Engelke, Klaus (2018)
EVALuna2:36402

Three-dimensional Distribution of Muscle and Adipose Tissue of the Thigh at CT: Association with Acute Hip Fracture - Mühlberg, Alexander; Museyko, Oleg; Bousson, Vallrie; Pottecher, Pierre; Laredo, Jean-Denis; Engelke, Klaus (Radiology, 2019)
Purpose: To evaluate determinants of hip fracture by assessing soft-tissue composition of the upper thigh at CT.
CRIS-Team WoS Importer:2019-02-21

Trabecular texture and paraspinal muscle characteristics for prediction of first vertebral fracture: a QCT analysis from the AGES cohort - Hummel, Jana; Engelke, Klaus; Freitag-Wolf, Sandra; Yilmas, Eren; Bartenschlager, Stefan; Sigurdsson, Sigurdur; Gudnason, Vilmundur; Glüer, Claus C.; Chaudry, Oliver (Frontiers in Endocrinology, 2025)
Introduction: Vertebral fractures (VFs) significantly increase risk of subsequent fractures. Areal bone mineral density (BMD) assessed by DXA and volumetric BMD by QCT, are strong predictors of VF. Nevertheless, risk prediction should be further improved. This study used data from the Age, Gene/Environment Susceptibility Reykjavik (AGES-Reykjavik) cohort to evaluate whether trabecular texture and paraspinal muscle assessments improve the prediction of the first incident VF. Methods: CT scans of the L1 and L2 vertebrae of 843 elderly subjects; including 167 subjects with incident, VFs occurring within a 5-year period and 676 controls without fractures. Image analysis included measurement of BMD, cortical thickness and of parameters characterizing trabecular architecture and the autochthonous muscles. Fifty variables were used as predictors, including a BMD, a trabecular texture and a muscle subset. Each included age, BMI and corresponding parameters of the QCT analysis. The number of variables in each subset was reduced using stepwise logistic regression to create multivariable fracture prediction models. Model accuracy was assessed using the likelihood ratio test (LRT) and the area under the curve (AUC) criteria. Bootstrap analyses were performed to assess the stability of the model selection process. Results: 96 women and 78 men with prior VF were excluded. Of 50 initial predictors, 17 were significant for women and 11 for men. Bone and texture models showed significantly better fracture prediction in women (p<0.001) and men (p<0.01) than the combination of age and BMI. The muscle model showed better fracture prediction in men only (p<0.03). Compared to the BMD model alone, LRT showed a significantly improved VF prediction of the combinations of BMD with texture (women and men) (p<0.05) or with muscle models (men only) (p=0.03) but no significant increases in AUC values (AUC women: Age&BMI: 0.57, BMD: 0.69, combined model: 0.69; AUC men: Age&BMI: 0.63, BMD: 0.71, combined models 0.73-0.77) Discussion: Trabecular texture and muscle parameters significantly improved prediction of first VF over age and BMI, but improvements were small compared to BMD, which remained the primary predictor for both sexes. Although muscle measures showed some predictive power, particularly in men, their clinical significance was marginal. Integral BMD should remain the focus for fracture risk assessment in clinical practice.
CRIS-Team Scopus Importer:2025-04-18
Keywords: BMD; computed tomography; fracture prediction; muscle; trabecular texture; vertebral fracture

Training, Risikofaktoren und Gesundheitskosten älterer Menschen: Senioren Fitness und Präventionsstudie (SEFIP) - Kemmler, Wolfgang; von Stengel, Simon; Mayer, Sabine; Engelke, Klaus; Kalender, Willi Alfred (Deutsche Zeitschrift für Sportmedizin, 2010)

Treatment of bone loss in proximal femurs of postmenopausal osteoporotic women with AGN1 local osteo-enhancement procedure (LOEP) increases hip bone mineral density and hip strength: a long-term prospective cohort study - Howe, J. G.; Hill, R. S.; Stroncek, J. D.; Shaul, J. L.; Fayell, D.; Cheng, R. R.; Engelke, Klaus; Genant, H. K.; Lee, D. C.; Keaveny, T. M.; Bouxsein, M. L.; Huber, B. (Osteoporosis international, 2019)
This first-in-human study of AGN1 LOEP demonstrated that this minimally-invasive treatment durably increased aBMD in femurs of osteoporotic postmenopausal women. AGN1 resorption was coupled with new bone formation by 12 weeks and that new bone was maintained for at least 5-7 years resulting in substantially increased FEA-estimated femoral strength. Introduction This first-in-human study evaluated feasibility, safety, and in vivo response to treating proximal femurs of postmenopausal osteoporotic women with a minimally-invasive local osteo-enhancement procedure (LOEP) to inject a resorbable triphasic osteoconductive implant material (AGN1). Methods This prospective cohort study enrolled 12 postmenopausal osteoporotic (femoral neck T-score <= - 2.5) women aged 56 to 89 years. AGN1 LOEP was performed on left femurs; right femurs were untreated controls. Subjects were followed-up for 5-7 years. Outcomes included adverse events, proximal femur areal bone mineral density (aBMD), AGN1 resorption, and replacement with bone by X-ray and CT, and finite element analysis (FEA) estimated hip strength. Results Baseline treated and control femoral neck aBMD was equivalent. Treated femoral neck aBMD increased by 68 +/- 22%, 59 +/- 24%, and 58 +/- 27% over control at 12 and 24 weeks and 5-7 years, respectively (p < 0.001, all time points). Using conservative assumptions, FEA-estimated femoral strength increased by 41%, 37%, and 22% at 12 and 24 weeks and 5-7 years, respectively (p < 0.01, all time points). Qualitative analysis of X-ray and CT scans demonstrated that AGN1 resorption and replacement with bone was nearly complete by 24 weeks. By 5-7 years, AGN1 appeared to be fully resorbed and replaced with bone integrated with surrounding trabecular and cortical bone. No procedure- or device-related serious adverse events (SAEs) occurred. Conclusions Treating femurs of postmenopausal osteoporotic women with AGN1 LOEP results in a rapid, durable increase in aBMD and femoral strength. These results support the use and further clinical study of this approach in osteoporotic patients at high risk of hip fracture.
CRIS-Team WoS Importer:2019-12-13

Updated practice guideline for dual-energy X-ray absorptiometry (DXA) - Slart, Riemer H.J.A.; Punda, Marija; Ali, Dalal S.; Bazzocchi, Alberto; Bock, Oliver; Camacho, Pauline; Carey, John J.; Colquhoun, Anita; Compston, Juliet; Engelke, Klaus; Erba, Paola A.; Harvey, Nicholas C.; et al. (European Journal of Nuclear Medicine and Molecular Imaging, 2024)
The introduction of dual-energy X-ray absorptiometry (DXA) technology in the 1980s revolutionized the diagnosis, management and monitoring of osteoporosis, providing a clinical tool which is now available worldwide. However, DXA measurements are influenced by many technical factors, including the quality control procedures for the instrument, positioning of the patient, and approach to analysis. Reporting of DXA results may be confounded by factors such as selection of reference ranges for T-scores and Z-scores, as well as inadequate knowledge of current standards for interpretation. These points are addressed at length in many international guidelines but are not always easily assimilated by practising clinicians and technicians. Our aim in this report is to identify key elements pertaining to the use of DXA in clinical practice, considering both technical and clinical aspects. Here, we discuss technical aspects of DXA procedures, approaches to interpretation and integration into clinical practice, and the use of non-bone mineral density measurements, such as a vertebral fracture assessment, in clinical risk assessment.
CRIS-Team Scopus Importer:2025-02-04
Keywords: Dual-energy X-ray absorptiometry (DXA); Practice guideline; Procedures

VALUE AND LIMITATIONS IN HR-PQCT IMAGING IN CHRONIC ARTHRITIS. CURRENT STATUS AND FUTURE DIRECTIONS - Engelke, Klaus; Figueiredo, C.; Kleyer, Arnd; Simon, David; Schett, Georg (OSTEOPOROSIS INTERNATIONAL, 2019)
CRIS-Team WoS Importer:2019-08-02

VERTEBRAL FRACTURE AS RISK FACTOR FOR SUBSEQUENT VERTEBRAL FRACTURE: ICD-10 BASED ANALYSIS OF A REAL-WORLD DATABASE - Glueer, C. -C.; Engelke, Klaus; Kistler, M.; Thomasius, F.; Hadji, P.; Schweikert, B.; Libanati, C.; Moayyeri, A. (AGING CLINICAL AND EXPERIMENTAL RESEARCH, 2022)
CRIS-Team WoS Importer:2022-10-14

Volumetric Bone Mineral Density in Cementless Total Hip Arthroplasty in Postmenopausal Women: Effects on Primary Femoral Stem Stability and Clinical Recovery - Aro, Hannu T.; Engelke, Klaus; Mattila, Kimmo; Löyttyniemi, Eliisa (Journal of Bone and Joint Surgery-American Volume, 2021)
BACKGROUND: In cementless total hip arthroplasty, femoral stems should preferably not migrate at all postoperatively. This goal is difficult to achieve in postmenopausal women with impaired bone quality. Here, we explored the clinical importance of initial stem migration, measured by radiostereometric analysis (RSA), in women who underwent quantitative computed tomography (CT) of the involved hip preoperatively. METHODS: A prospective cohort of 65 postmenopausal women (mean age, 69 years) with hip osteoarthritis and Dorr type-A or B femoral anatomy underwent total hip arthroplasty with implantation of a tapered, single-wedge femoral stem. Volumetric bone mineral density (BMD) was measured using quantitative CT. Femoral stem translation and rotation were measured using model-based RSA within 3 days after the surgical procedure and were repeated at 3, 5, and 11 months. Postoperative recovery parameters included walking speed, walking activity, and patient-reported outcome measures. Subjects were categorized into 2 groups according to the magnitude of initial 5-month stem subsidence (<2 mm or ≥2 mm); RSA outliers (n = 7) were analyzed separately. RESULTS: Subjects with stem subsidence of ≥2 mm (mean, 3.09 mm [95% confidence interval (CI), 2.70 to 3.47 mm]) had lower intertrochanteric volumetric BMD (p = 0.008). Subjects with subsidence of <2 mm (mean, 0.80 mm [95% CI, 0.51 to 1.09 mm]) had faster improvement of patient-reported outcome measures and exhibited faster walking speed (p = 0.007) and greater walking activity (p = 0.010) at 11 months as well as better Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) scores (p = 0.002) and RAND 36-Item Health Survey mental component scores (p = 0.006) at 2 years. All cohort stems were osseointegrated at 2 years. CONCLUSIONS: Femoral stem stability and resistance to subsidence were sensitive to adequate intertrochanteric volumetric BMD. Low intertrochanteric volumetric BMD was associated with greater stem migration. With initial migration, clinical recovery was slower and patient-reported outcome measures were less satisfactory. LEVEL OF EVIDENCE: Prognostic Level II. See Instructions for Authors for a complete description of levels of evidence.
CRIS-Team Scopus Importer:2021-06-25

WHOLE BODY ELECTROMYOSTIMULATION AND PROTEIN TO FIGHT SARCOPENIC OBESITY IN WOMEN 70 YEARS AND OLDER: PRELIMINARY DATA OF THE FORMOSASTUDY - Kemmler, Wolfgang; Engelke, Klaus; von Stengel, Simon; Jakob, F.; Sieber, Cornel (Osteoporosis international, 2016)

Whole-Body Electromyostimulation to Fight Osteopenia in Elderly Females: The Randomized Controlled Training and Electrostimulation Trial (TEST-III) - von Stengel, Simon; Bebenek, Michael; Engelke, Klaus; Kemmler, Wolfgang (Journal of Osteoporosis, 2015)
Whole-body electromyostimulation (WB-EMS) has been shown to be effective in increasing muscle strength and mass in elderly women. Because of the interaction of muscles and bones, these adaptions might be related to changes in bone parameters. 76 community-living osteopenic women 70 years and older were randomly assigned to either a WB-EMS group (n = 38) or a control group (CG: n = 38). The WB-EMS group performed 3 sessions every 14 days for one year while the CG performed gymnastics containing identical exercises without EMS. Primary study endpoints were bone mineral density (BMD) at lumbar spine (LS) and total hip (thip) as assessed by DXA. After 54 weeks of intervention, borderline nonsignificant intergroup differences were determined for LS-BMD (WB-EMS: 0.6 ± 2.5% versus CG -0.7 ± 2.5%, P = .051) but not for thip-BMD (WB-EMS: -1.1 ± 1.9% versus CG: -0.8 ± 2.3%, P = .771). With respect to secondary endpoints, there was a gain in lean body mass (LBM) of 1.5% (P = .006) and an increase in grip strength of 8.4% (P = .000) in the WB-EMS group compared to CG. WB-EMS effects on bone are less pronounced than previously reported effects on muscle mass. However, for subjects unable or unwilling to perform intense exercise programs, WB-EMS may be an option for maintaining BMD at the LS.
EVALuna2:10118

Whole-body electromyostimulation to fight sarcopenic obesity in community-dwelling older women at risk. Results of the randomized controlled FORMOsA-sarcopenic obesity study - Kemmler, Wolfgang; Teschler, Marc; Weißenfels, Anja; Bebenek, Michael; von Stengel, Simon; Kohl, Matthias; Freiberger, Ellen; Goisser, Sabine; Jakob, F.; Sieber, Cornel; Engelke, Klaus (Osteoporosis international, 2016)
The effect of whole body-electromyostimulation in community-dwelling women >= 70 with sarcopenic obesity was heterogeneous, with high effects on muscle mass, moderate effects on functional parameters, and minor effects on fat mass. Further, we failed to determine a supportive effect of additional protein-enriched dietary supplementation in this albeit predominately well-nourished group.Introduction The aim of the study was to determine the effect of whole-body electromyostimulation (WB-EMS) on sarcopenic obesity (SO) in community-dwelling women more than 70 years with sarcopenic obesity.Methods Seventy-five community-dwelling women >= 70 years with SO were randomly allocated to either a WB-EMS application with (WB-EMS & P; 24.9 +/- 1.9 kg/m(2)) or without (WB-EMS; 25.2 +/- 1.8 kg/m(2)) dietary supplementation (150 kcal/day, 56 % protein) or a non-training control group (CG; 24.7 +/- 1.4 kg/m(2)). WB-EMS consisted of one weekly session of 20 min (85 Hz, 350 mu s, 4 s of strain-4 s of rest) performed with moderate to high intensity. Primary study endpoint was the Sarcopenia Z-Score constituted by skeletal muscle mass index (SMI, as assessed by dual energy X-ray absorptiometry), grip strength, and gait speed, and secondary study endpoint was body fat (%).Results Sarcopenia Z-score comparably increases in the WB-EMS and the WB-EMS&P-group (p=.046). Both groups differ significantly (p=.001) from the CG which deteriorated significantly (p=.006). Although body fat changes were most pronounced in the WB-EMS (-0.9 +/- 2.1; p=.125) and WB-EMS&P (-1.4 +/- 2.5; p=.028), reductions did not statistically differ (p=.746) from the CG (-0.8 +/- 2.7; p=.179). Looking behind the covariates, the most prominent changes were determined for SMI, with a significant increase in both EMS-groups (2.0-2.5 %; p=.003) and a decrease in the CG (-1.2 +/- 3.1 %; p=.050) with significant between-group differences (p=.001).Conclusion WB-EMS is a safe and attractive method for increasing muscle mass and functional capacity in this cohort of women 70+ with SO; however, the effect on body fat is minor. Protein-enriched supplements did not increase effects of WB-EMS alone.
EVALuna2:33286
Keywords: Body fat; Community-dwelling older people; Sarcopenic obesity; Skeletal muscle mass; Whole-body electromyostimulation